Mechanical properties and micro-mechanism of coral concrete modified by mineral admixture combined with organic polymer - Wang Zhen; Mohamed Abdelmongy; Wu Qing; Muhammad Akbar; Han Zuoseung; Talal O. Alshammari; Ahmed. M. Yosri (European Journal of Environmental and Civil Engineering, 2026)

Interface evolution unlocks the anti-poisoning capability of trace B-site excessive medium-entropy air electrodes for tubular reversible solid oxide cells - Yuan Gao; Bo Wei; Yanan Liu; Tian Li; Xu Han; Abdalla M. Abdalla; Zhe Lv; Yihan Ling (Fuel, 2026)

Suppression of miR426 enhances photoprotection and chlorophyll stability via upregulation of ELIP2 in Arabidopsis thaliana - Arif Faisal Mustaffa; Syed Muhammad Iqbal Syed Othman; Nur Irdina Izzatie Mohd Zahid; M. Hafiz Che-Othman; Hoe-Han Goh; Muhammad Sajad; Ismanizan Ismail (Molecular Biology Reports, 2026)

Seismic performance of self-centering rocking bridge piers with external energy dissipation device considering pile-soil interaction - Guangming Fan; Huihui Dong; Xiuli Du; Qiang Han; M. Hesham El Naggar (Engineering Structures, 2026)

Stochastic analysis of horizontal dynamic response of offshore pipe piles considering hydrodynamic pressure - Bo Yu; Libo Chen; Guang Han; Lichen Li; M. Hesham El Naggar; Wenbing Wu (Ocean Engineering, 2026)

Cascade structure and event-level attribution of three-dimensional compound drought–heat events in China: contrasting meteorological and agricultural systems - Ben Niu; Yi Li; Shasha Han; Jinxuan Zhao; Darrell W.S. Tang; David M. Hannah (Journal of Hydrology, 2026)

Dehydration–induced 4D shape transformation in 3D printed egg yolk gels: Insights into the coupling between water redistribution and network restructuring - Jian Li; Dekun Meng; Siyao Han; Huajiang Zhang; Lina Xu; Jingwei Wu; Hanyu Li; Ning Xia; Mohamed Ghamry; Ahmed M. Rayan (Food Research International, 2026)

Drivers of ecosystem metabolism in temperate kelp forests: A high‐resolution aquatic eddy covariance study - Chang Hwa Lee; Karl M. Attard; Peter Berg; Yong‐Jae Baek; Jung‐Ho Hyun; Dong Mun Choi; Taihun Kim; Hyun Soo Rho; Sung‐Han Kim; Jae Seong Lee (Limnology and Oceanography, 2026)
Kelp forests are highly productive coastal ecosystems that sustain organic carbon cycling and diverse food webs; however, their ecosystem metabolism remains insufficiently quantified due to a lack of suitable in situ methods. In this study, the aquatic eddy covariance technique was used to quantify oxygen (O 2 ) flux and net ecosystem metabolism in Ecklonia cava forests along Jeju Island, Korea. We also applied partial least squares regression to assess the relative influence of environmental conditions and canopy‐structure metrics on O 2 flux variability. During the daytime, O 2 flux variability was primarily associated with hydrodynamic conditions and light, whereas at night, the relative importance of canopy density increased, together with temperature. This interplay between drivers was reflected in metabolic shifts of E. cava forests: net ecosystem metabolism was positive under dense canopies during periods of favorable light and hydrodynamic conditions but shifted toward negative values under elevated water temperature and canopy degradation. Our results demonstrate that metabolic regulation in structurally complex kelp forests is driven by a dynamic coupling of hydrodynamic forcing and biological phenology. These findings provide a critical mechanistic basis for assessing the metabolic resilience of temperate kelp forests and evaluating their potential role as nature‐based solutions for carbon sequestration in a rapidly changing ocean.

Temporal 2G–5G RF-EMF exposure assessment in ten European countries during one year - Han Van Bladel; Adriana Fernandes Veludo; Nicolas Loizeau; Martin Röösli; Milena Maule; Zsuzsanna Vecsei; Orsolya Molnár; Tanja Vrijkotte; Kinga Polanska; Piotr Politański; Paweł Mamrot; Shanshan Wang; et al. (Science of The Total Environment, 2026)

Linking ambient fire emissions to respiratory effects using gelatin filter sampling - Olivia C.G. Lampe; Tate J. Matthews; Akshat Verma; Bowie P. Lam; Eva C.M. Vitucci; Carolyn L. Cannon; Arum Han; Shankararaman Chellam; Natalie M. Johnson (Journal of Hazardous Materials, 2026)

Global perspectives on the curricular integration of nature-based solutions in hydrology and water resources management education - Mark Bryan Alivio; Kristina Potočki; Pavel Raška; Peter Ameh Adegede; Tanveer Mehedi Adyel; Hafzullah Aksoy; Mary Bourke; Yonca Cavus; Mariana Madruga de Brito; Moctar Dembélé; Ashraf M. Elmoustafa; Kristian Förster; et al. (Journal of Cleaner Production, 2026)

Spore inoculum size impacts substrate degradation and sporulation but not the secretome during colonization of whole yellow pea (Pisum sativum) by Aspergillus oryzae - Maaike Braat; Nienke Braat; Nadzeya Staliarova; Tomás Vellozo-Echevarría; Hania M. Siwek; Julius F. Kemmer; Kristian Barrett; Anne S. Meyer; Kelly E. Stecker; Han A.B. Wösten (International Journal of Food Microbiology, 2026)

Inhibiting electrostatic aggregation between ovalbumin/S-ovalbumin and lysozyme to enhance egg white thermal stability - Xiaohan Zhang; Dekun Meng; Siyao Han; Huajiang Zhang; Hanyu Li; Lina Xu; Xinyi Ju; Mohamed Ghamry; Ahmed M. Rayan (Food Hydrocolloids, 2026)

Management practices shape soil fungal diversity and functional traits in Swiss forests - Xingguo Han; Fabienne Kuhn; Flurin Leugger; Thibault Lachat; Nicolas Roth; Martin M. Gossner; Loïc Pellissier; Aline Frossard (European Journal of Soil Biology, 2026)

Abnormal spring climate and greener amplify impacts on ecosystem productivity and evapotranspiration under extreme summer drought - Shanshan Yang; Huadong Guo; Qi Liu; Jiaqi Han; Jingwen Wang; Yun Bai; Sha Zhang; Ayalkibet M. Seka; Jiahua Zhang (Environmental Impact Assessment Review, 2026)

Present-Day Sea Level Variations in Coastal Areas from Daily to Multidecadal Time Scales: Observations and Causes - A. Cazenave; R. Almar; P. Almeida; N. K. Ayoub; J. H. Bettencourt; F. Birol; W. Han; M. Herrmann; S. Jevrejeva; L. Leclercq; F. Niño; J. Oelsmann; et al. (Surveys in Geophysics, 2026)

Retraction notice to “Biochar-induced metal immobilization and soil biogeochemical process: An integrated mechanistic approach” [Sci. Total Environ. 698 (2020) 134112] - Ali El-Naggar; Mi-Hee Lee; Jin Hur; Young Han Lee; Avanthi Deshani Igalavithana; Sabry M. Shaheen; Changkook Ryu; Jörg Rinklebe; Daniel C.W. Tsang; Yong Sik Ok (Science of The Total Environment, 2026)

Retraction notice to “Spatial congruency or discrepancy? Exploring the spatiotemporal dynamics of built-up expansion patterns and flood risk” [Sci. Total Environ. 915 (2024) 170019] - Mahmoud Mabrouk; Haoying Han; Karim I. Abdrabo; Mahran Gamal N. Mahran; Salma Antar A. AbouKorin; Sarah Nasrallah; Guoqiang Shen; Chao Fan; Ahmed Yousry; Hisham M. Hafez (Science of The Total Environment, 2026)

Retraction notice to “Mitigation of the mobilization and accumulation of toxic metal(loid)s in ryegrass using sodium sulfide” [Sci. Total Environ. 909 (2024) 168387] - Han Zhang; You Li; Ronghua Li; Weilong Wu; Hamada Abdelrahman; Jianxu Wang; Samir G. Al-Solaimani; Vasileios Antoniadis; Jörg Rinklebe; Sang Soo Lee; Sabry M. Shaheen; Zengqiang Zhang (Science of The Total Environment, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Soil moisture information in Southeast Australia – A review of long-term field measurements toward enhanced monitoring and predictive applications - I.P. Senanayake; I.-Y. Yeo; M. Khaki; G.R. Hancock; P.G. Dahlhaus; N.J. Robinson; S.-C. Han; J.P. Walker (Geoderma Regional, 2026)

Effects of Antioxidant DI-3-N-Butylphthalide on Hemorrhagic Transformation Assessed by Propensity Score Matching in a Real-World Thrombolyzed Ischemic Stroke Patient Setting - Ziqi Han; He Liang; Tieping Fan; Mario Minor Murakami Junior; Shumin Li; Ruikang Sun; Daoyong Peng; Shiwei Du; Yu Hasegawa; Haojie Gao; Dong Chen; Dirk M. Hermann; et al. (Translational Stroke Research, 2026)

The role of rurality and area-level disadvantage in lifestyle risk factors and psychological well-being among cancer survivors: findings from the 2021 NCI HINTS-SEER - Anita M. Kumar; Carrie A. Miller; Reyna Han; D. Jeremy Barsell; Joseph Boyle; Bernard F. Fuemmeler (Cancer Causes & Control, 2026)
Background Rural cancer survivors consistently experience poorer health outcomes than their urban counterparts, yet the interplay between rurality and area-level disadvantage remains understudied. This study examines how rural versus urban residence and neighborhood disadvantage relate to obesity, smoking, and psychological well-being among cancer survivors. Methods Data from 1,062 HINTS-SEER participants across three registries were analyzed. Logistic regression models estimated associations between area-level factors (Social Deprivation Index (SDI) and Areas of Persistent Poverty) and health outcomes, adjusting for individual sociodemographic factors. Analyses accounted for complex survey design using Taylor series linearization. Results Urban residents showed lower odds of obesity compared with their rural counterparts (OR: 0.69; 95% CI: 0.50–0.95). In stratified analyses, area-level social deprivation demonstrated smaller statistically significant associations. Higher deprivation was associated with increased odds of obesity among urban cancer survivors (OR: 1.01; 95% CI: 1.00–1.02) and increased depression/anxiety among rural survivors (OR: 1.02; 95% CI: 1.00–1.04). Across all models, individual-level socioeconomic factors (education, income) showed stronger, more consistent protective associations than area-level indicators. Conclusions and implications Area-level disadvantage was a contributor to rural cancer survivors’ psychological well-being. Individual socioeconomic status remains the dominant determinant of lifestyle and mental health outcomes. Cancer survivors residing in socioeconomically disadvantaged rural areas may benefit from targeted mental health intervention. Future longitudinal research incorporating census tract–level geographic measures and residential histories is needed to clarify the mechanisms linking the geographic and socioeconomic context to survivorship outcomes.

Microbial Decomposition of Lignin to Methane Reduces Net Blue Carbon Benefit Across China's Saltmarshes - Leilei Xiao; Chuancheng Fu; Isaac R. Santos; Carlos M. Duarte; Jian Liu; Lifeng Zhou; Meng Zhou; Run Dang; Jinkuo Lin; Kai Xiao; Yongming Luo; Guangxuan Han (Global Change Biology, 2026)
CH 4 emissions from mangrove, saltmarsh, and seagrass ecosystems partially offset carbon sequestration, potentially diminishing the climate mitigation capacity of these blue carbon habitats. However, a mechanistic understanding of the processes governing CH 4 production potential across large spatial scales remains limited. By integrating incubation‐based measurements from 116 sites, we reveal significant ecosystem‐specific differences in CH 4 production potential, with saltmarshes emerging as CH 4 production hotspot relative to mangroves and seagrass meadows. Using an integrated analytical approach encompassing more than 30 environmental, biogeochemical, and microbial parameters, we demonstrate that CH 4 production potential converges on sediment organic carbon availability, particularly plant‐derived carbon, as a key regulatory axis. Additionally, metagenome‐assembled genomes (MAGs) recovered from saltmarshes show a functional bias toward lignin degradation, thereby fueling downstream CH 4 production via methylotrophic pathways. Lignin‐addition and stable carbon isotope experiments further provide supportive evidence that lignin decomposition enhances Chinese saltmarsh CH 4 production potential, revealing a pathway that may reduce net blue carbon benefit. Together, these findings underscore that saltmarsh plant‐derived lignin is less stable than conventionally assumed, as microbial processing redirects stored carbon toward CH 4 production, challenging current blue carbon accounting frameworks at a continental scale within China.

Using life-history information to identify management priorities within an emergent multi-species grey mullet fishery - Calum J. Pritchard; Ayşegül Tuğçe Han; Andrew Macleod; Rachel M. Turnbull; Jamie Small; Sarah Birchenough; Simon Pengelly; Benjamin J. Ciotti (Fisheries Research, 2026)

Mapping parcel-level Essential Urban Land Use Categories across global cities (EULUC-Globe) - Bin Chen; Ziming Li; Han Wang; Xuecao Li; Jing M. Chen; Bing Xu; Peng Gong (Science Bulletin, 2026)

Dopaminergic expression and the regulation of foraging in response to water stress - J. Frances Kamhi; Dajia Ye; Jason Chen; Han Lam Do; Corinne W. Marble; Jonathan Starcke; Ignacio Arganda-Carreras; Deborah M. Gordon (Journal of Insect Physiology, 2026)

Boosting aqueous Zn-ion battery performance with Co2+-doped δ-MnO2/Ti3C2Tx cathode through enhanced ion transport and structural stabilization - Shuo Li; Jing Zhu; Longkun Wu; Yasong Han; Ningning Zhao; Bin Li; Shaaban M. Shaaban; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2026)

Enhancing Rainfall-Runoff Simulation in Data-Scarce Watersheds: Integration of Satellite Observations, Physically-Based Hydrological Modeling, and Machine Learning - Khabat Khosravi; Aitazaz Farooque; Shasha Han; David M. Hannah (Water Resources Management, 2026)

Dynamic response and failure evolution of sandy slopes under ground motion before and after rainfall infiltration - Junyan Han; Jiasai Li; Xi Xu; M. Hesham El Naggar; Zhaohui Wang; Chengshun Xu; Xiuli Du (Landslides, 2026)

E-cigarette Aerosol Containing Nicotine Increases Aortic Stiffness in Young Mice - Pireyatharsheny Mulorz; Joscha Mulorz; Agnesa Mazrekaj; Hsiang-Han Liu; Wiebke Ibing; Joshua M. Spin; Lasse Bach Steffensen; Hans C. Beck; Uwe Raaz; Kensuke Toyama; Hubert Schelzig; Philip S. Tsao; et al. (Cardiovascular Toxicology, 2026)

Tapentadol induces progressive hepatic damage via disrupting Hippo–YAP and bile acid–FXR pathways: An integrated experimental and computational perspective - Han Hu; Salim Jamil; Muhammad Bilal Azmat; Mohammed Alissa; Ghfren S. Aloraini; Amal A. Albati; Ahmed Al-Emam; Hesham M. Hassan (Tissue and Cell, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Retraction notice to “Enhancing battery pack safety against cone impact using machine learning techniques and Gaussian noise” [Process Saf. Environ. Prot. 191 (2024) 448–465] - Qian Zhang; Shaoyong Han; Azher M. Abed; Ali Basem; Mohamed R. El-Sharkawy; Bashir Salah; Ibrahim Mahariq (Process Safety and Environmental Protection, 2026)

Competitive enzyme-linked immunosorbent assay to quantify hepcidin in horse serum - C.R. Gluck-Flynn; H. Han; M. Valenzuela; P. Routh; V.E. Ostland; S.E. Pratt-Phillips (Journal of Equine Veterinary Science, 2026)

Strategy of two birds with one stone: epigallocatechin-gallate assisted structuring of egg yolk granules multiphase gels for controlled release of blueberry anthocyanins - Xueying Wang; Dekun Meng; Siyao Han; Huajiang Zhang; Hanyu Li; Yunhe Xu; Lina Xu; Ning Xia; Peiyao Si; Mohamed Ghamry; Ahmed M. Rayan (Food Chemistry, 2026)

Early development of stem units and the modular organization of the branch in Norway spruce - Carol L. Wenzel; Anson Mo; Bonita Chan; Anny Xia; Chantelle Westgate; Rebecca Saunders; Han Han Ly; David M. Holloway (Trees, 2026)

Precipitation reduction mitigates the negative impact of nitrogen deposition on soil nitrogen fixation in subtropical Chinese fir plantations - Fengyi Han; Yongxin Lin; Maokui Lyu; Hang-Wei Hu; Xiangyin Ni; Qiufang Zhang; Jinsheng Xie; Ji-Zheng He; Peter M. Homyak (Science China Life Sciences, 2026)

Improved methods for determining maximum horizontal stress from borehole breakout - Yanhui Han; Khaqan Khan; Tameem M. Almani; Murtadha J. AlTammar; Osman Hamid (Computational Geosciences, 2026)

Quantification and visualization of 3D facial aging in individuals of European ancestry - Yi Fan; Harold Matthews; Chenda Meng; Nina Claessens; Seth M. Weinberg; Mary L. Marazita; Susan Walsh; Mark D. Shriver; Anthony Penington; Marie A. Cornelis; Paolo M. Cattaneo; Tianmin Xu; et al. (GeroScience, 2026)
Facial features undergo continuous transformations across the lifespan. This study quantified and visualized the effects of aging on facial morphology in individuals of European ancestry. Three-dimensional facial photographs of 4,038 individuals (1,455 males and 2,583 females), aged 5 to 85 years and of European descent, were analyzed. Morphological changes in the face were modeled using kernel linear regression, with a focus on age-related changes. Age- and sex-specific expected facial shapes were generated for individuals aged 10 to 60 years in 5-year intervals. Changes in the face were analyzed in the sagittal, vertical, and horizontal directions, with linear distances and angular variations in the upper, middle, and lower regions of the face evaluated. Our results show that facial shape changes decelerate progressively after the age of 25 for both males and females. Facial aging is characterized by the loss of fullness in the forehead, sunken temples, formation of eye bags, deepening nasolabial folds, cheek hollowness and thinning, lengthening, and retrusion of the lips. Notable changes begin in the 30s, with the most pronounced alterations occurring in the 40s and 50s, intensifying in the 50s and 60s. Although the overall aging trajectory is similar in males and females, the magnitude and rate of change demonstrate sexual dimorphism. This study provides comprehensive insights into age-related facial morphological changes in healthy individuals of European ancestry using 3D photogrammetric analysis. These findings have important implications for clinical disciplines such as dentistry, plastic and maxillofacial surgery, and forensic medicine.

A critical review of potential modifiers of air pollutant associations with dementia and related outcomes - JeongWon Han; Yina Li; Sangji Lee; Katie M. Lynch; Erin E. Bennett; Qi Ying; Eun Sug Park; Richard L. Smith; James D. Stewart; Eric A. Whitsel; Melinda C. Power; Xiaohui Xu (NeuroToxicology, 2026)

Dose-dependent cerebral metabolic impairment in a swine model of carbon monoxide poisoning - Alistair Lewis; Rodrigo M. Forti; Tiffany S. Ko; John C. Greenwood; Matthew Kelly; Frances S. Shofer; Shih-Han Kao; Samuel S. Shin; Devesh Bungatavula; Mckenna Mason; Jonathan Starr; Johannes K. Ehinger; et al. (NeuroToxicology, 2026)

Discrete artificial bee colony algorithm based on multiple neighborhood swaps for the hybrid flowshop scheduling problem with uncertain processing stages - Yang Yu; Xinbo Song; Zixiang Li; Liangliang Sun; Yuyan Han; Xinfu Pang; Zhujun Wang; Natalja M. Matsveichuk; Yuri N. Sotskov (Swarm and Evolutionary Computation, 2026)

A hybrid non-linear observer for maritime surface vessel state estimation using physics-based and data-driven modelling - Aksel Trentemøller Frafjord; Erlend M. Coates; Peihua Han; Tongtong Wang; Italo Aldo Campodonico Avendano; Øivind Kåre Kjerstad (Ocean Engineering, 2026)

Novel design of Fe0-and AC-doped hydroxyapatite-alginate composites for efficient arsenic clean-up: Mechanistic insights from batch and column tests - Behzad Murtaza; Farwah Shamshir; Muhammad Imran; Muhammad Shahid; Kifayat Ullah; Muhammad Nadeem; M. Asif Naeem; Noor Samad Shah; Jianxu Wang; Ajmal Khan; Changseok Han (Journal of Environmental Management, 2026)

Microbial valorization of lignin to malic acid by Aspergillus niger - Jiayuan Jia; Ziyu Dai; Yinglei Han; Hemant Choudhary; Guoliang Yuan; John M. Gladden; Blake A. Simmons; Scott E. Baker; Jon K. Magnuson; Joonhoon Kim (Bioresource Technology, 2026)

Construction of Synthetic Probiotic Bacteria for In Situ Delivery of Anti-SARS-CoV-2 Nanobodies - Carolina E. Portero; Claire Smith; Yuxi Zhou; M. Raquel Marchán-Rivadeneira; Shiyong Wu; Yong Han (Probiotics and Antimicrobial Proteins, 2026)
SARS-CoV-2 viral infection can be inhibited by blocking the interaction between the viral spike protein and the human receptor angiotensin-converting enzyme 2 (hACE2). The development of specific spike inhibitors using nanobodies, the antigen-binding region of llamas’ antibodies, arose as a promising therapeutic method against SARS-CoV-2. However, one limitation of nanobodies is that they cannot be used directly in the human body due to their susceptibility to degradation. Bacteria-based delivery systems provide site-specific targeted action that can circumvent nanobody degradation. Here, we report the development of a genetically modified bacterium expressing anti-SARS-CoV-2 nanobodies that can inhibit the interaction between the hACE2 receptor and the receptor-binding domain (RBD) of the spike protein. Lactococcus lactis , a human symbiont probiotic bacterium, was selected to express nanobodies attached to their cell surface. Our data shows that FLAG-tagged anti-SARS-CoV-2 nanobodies were detected on the cell surface of recombinant L. lactis strains by flow cytometry and immunofluorescence without permeabilization. Furthermore, nanobodies are functional and can bind the RBD region from the spike protein in a dose-dependent manner. Inhibition of the hACE2-RBD interaction in cellular assays was quantified using a pseudotype lentivirus that mimics SARS-CoV-2 in an adaptation of the neutralization assay. Our results suggested that the recombinant bacteria can inhibit viral infectivity in more than 50% compared with a control without bacteria in a neutralization assay. These outcomes suggest that the engineered strain can be used in the future as a new therapeutic tool in COVID-19 prevention.

National Poison Center Trends in GLP-1 Receptor Agonist Exposures Following FDA Approval for Weight Loss - Jordan Miller; Robert Miller; Shawn M. Varney; David Han (Journal of Medical Toxicology, 2026)
Introduction Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are therapies for type 2 diabetes whose use expanded sharply after semaglutide’s 2021 approval for obesity. Although gastrointestinal effects are well described, national patterns of acute GLP-1 RA exposures are poorly characterized. This study evaluated trends in GLP-1 RA exposures reported to U.S. poison centers, focusing on demographic shifts, exposure circumstances, and clinical outcomes before and after the 2021 FDA approval. Methods We analyzed human GLP-1 RA exposures reported to the National Poison Data System from 2012 to 2023, using July 1, 2021, to define pre- and post-approval periods. Demographics, exposure characteristics, therapies, and medical outcomes were compared using standardized statistical tests. Quarterly call counts were modeled with segmented Poisson regression to assess changes in reporting trajectory. Results A total of 10,033 exposures were identified (3,113 pre-approval; 6,920 post-approval). Semaglutide predominated post-approval (64.2%). The exposed population shifted younger and more female. Most cases were unintentional therapeutic errors with mild gastrointestinal symptoms. The proportion managed in or referred to a health care facility increased from 23.0% to 33.5% (RR = 1.46, [95% CI: 1.36, 1.57], p < 0.001). Segmented Poisson modeling demonstrated a significant inflection in call volume, with semaglutide exposures increasing an additional 9.9% per quarter after approval. Conclusions GLP-1 RA exposures rose sharply following semaglutide’s weight-loss approval, accompanied by increased health care utilization despite generally mild clinical effects. Although multiple factors likely contributed to these trends, improved patient counseling and clearer poison center guidance may help reduce preventable therapeutic errors and unnecessary emergency evaluation.

Early intestinal barrier changes in A53T transgenic Parkinson’s disease mice - Myat Noe Han; Olivia Artaiz; Matthew C. Rowe; David I. Finkelstein; Shanti Diwakarla; Rachel M. McQuade (Cell and Tissue Research, 2026)
Gut dysfunction commonly precedes motor symptoms in Parkinson’s disease (PD), but the mechanistic sequence of gut versus brain pathology remains unclear. This work aimed to define the timing of intestinal barrier dysfunction relative to central nervous system (CNS) changes in the A53T α-synuclein transgenic mouse model of PD. Functional and molecular assessments of the gastrointestinal tract (ileum and colon) were conducted at 12 and 36 weeks. We measured in vivo and ex vivo intestinal permeability, nutrient absorption, histomorphology, goblet cell density, and expression of MUC2 and Claudin-1. Inflammatory markers (CRP, TNF-α, CD45) were quantified in plasma and gut tissues. A53T mice exhibited increased intestinal permeability at 12 and 36 weeks, with transiently elevated ex vivo transepithelial electrical resistance (TER) at 12 weeks. Nutrient absorption remained intact. Morphological changes included widened villi and crypts, altered mucin expression, and early reductions in Claudin-1 in the ileum and the colon while inflammatory markers remained largely unchanged. These findings suggest that gut dysfunction precedes known central pathology in A53T mice, supporting further investigation into the gut as an early site of pathology and a potential therapeutic target in PD.

Analysis of Helium Monte Carlo Data for the ISS-CREAM Instrument - A. Bagga; S. Aggarwal; Y. Amare; D. Angelaszek; D.P. Bowman; Y.C. Chen; G.H. Choi; M. Copley; L. Derome; Z.M. Dorris; L. Eraud; J.H. Han; et al. (Advances in Space Research, 2026)

Microbial Responses to Warming Reduce Deep Blue Carbon Storage - Leilei Xiao; Jian Liu; Genevieve L. Noyce; Jaehyun Lee; Carlos M. Duarte; Meng Zhou; Min Luo; Ruifeng Sun; Run Dang; Lifeng Zhou; Lirong Zhang; Chuancheng Fu; et al. (Global Change Biology, 2026)
Coastal wetlands are critical blue carbon reservoirs, yet the depth‐resolved impacts of warming on belowground carbon dynamics remain poorly understood. Over the course of an 8‐year in situ experiment, we investigated plant‐derived carbon inputs, soil carbon losses via respiration, and microbially mediated carbon fixation across a 60 cm soil profile under a projected 2°C atmospheric warming scenario. Plant carbon fixation (above‐ and belowground net primary productivity) and soil respiration exhibited synchronized responses to warming, with an initial increase, followed by a decline in the mid‐term, and no significant response in the later stages. Soil and microbial respiration stabilized after prolonged exposure to elevated temperatures, as these processes were constrained by substrate availability. In contrast, phospholipid fatty acid profiling, amino sugar biomarkers, and metagenome‐assembled genomes consistently indicated a greater than one‐third reduction in microbial carbon fixation within subsoils (40–60 cm). Our fully factorial, depth‐stratified warming design reveals the particular vulnerability of deep soil microbial carbon retention to long‐term climate warming, independent of shifts in plant input or respiratory carbon loss. This work highlights underappreciated pathways influencing soil blue carbon dynamics in a changing world.

Active immunization against myostatin and activin A improves skeletal muscle performance in growth hormone-deficient mice - Mishfak A. M. Mansoor; Sarah A. Ashiqueali; Md Tanjim Alam; Fabrizzio Lijeron-Herrera; Xiang Zhu; Jash Trivedi; Amanda Lasseter; Augusto Schneider; Lisa Flores; Hu Wang; Xianlin Han; Yuji Ikeno; et al. (GeroScience, 2026)

Seasonal freeze-thaw modulates methane cycling in urban waters revealed by multiple isotopic constraints - Jiaxu Han; Xinchu Wang; Rob M. Ellam; Matthieu Clog; Zhiyong Pang; Heping Lu; Chenyang Shou; Lishan Ran; Si-Liang Li (Water Research, 2026)

A Next-Generation Recombinant Botulinum Toxin With Enhanced Activity and Longer Duration of Action - Mi Seon Shin; Laon Kim; Jae Yoon Byun; Hee Won Min; Su Hyeok Kim; Ui Beom Park; Deu John M Cruz; Seongsung Kwak; Kook-Han Kim (Toxicon, 2026)

Seismic response characteristics of inclined locally liquefied sites: A large-scale shaking table test - Xiaoqiang Wang; Junyan Han; M. Hesham El Naggar; Liyun Li; Chengshun Xu; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2026)

Effect of passive turbulence control parameters on flow-induced vibrations of a circular cylinder - Hongrae Park; Eun Soo Kim; Eun Jung Chae; Michael M. Bernitsas; Manbae Han; Gwang Goo Lee (Ocean Engineering, 2026)

Enhanced long-term oxidative remediation of calcium sulfate encapsulated KMnO4 for phenol-contaminated soil - Jia Shen; Yaxian Hu; Zeming Xie; Zili Jiang; Doaa M. Mustafa; Yang Liu; Yue Han; Xiuxiu Ruan (Journal of Hazardous Materials, 2026)

Bioinspired reaction engineering of CO2 mineralization assisted by tannic acid and ultrasonication - Leila Shahriari; Tyrus Antonson; Sang Eon Han; Sang M. Han; Maryam Hojati; Sungjin Kim (Chemical Engineering Journal, 2026)

Laboratory observations of long wave inundation of shorelines in the shadow of islands - John T. Goertz; Nikos Kalligeris; Sunghoon Han; James M. Kaihatu; Patrick J. Lynett; Costas E. Synolakis (Coastal Engineering, 2026)

3,3'-Dichlorobiphenyl (PCB 11) alters the hepatic expression of cytochrome P450 enzymes in the liver of mouse dams exposed orally during pregnancy and lactation - Crystal M. Roach; Nate R. Koester; Xueshu Li; Jeonghyeon Ahn; R. Marshall Pope; Rebecca J. Wilson; Rosalia Mendieta; Anthony Valenzuela; Weiguo Han; Xinxin Ding; Pamela J. Lein; Hans-Joachim Lehmler (Archives of Toxicology, 2026)
Healthy maternal metabolism is critical during pregnancy and lactation to support fetal development and protect against environmental toxins. Polychlorinated biphenyl 11 (PCB 11), a lower-chlorinated, non-legacy congener, is detected in human serum, including pregnant women and children; however, its impact during these sensitive life stages remains poorly understood. This study presents the first comprehensive hepatic proteome analysis of mouse dams exposed to PCB 11 during pregnancy and lactation. Female C57BL/6 J mice received daily oral doses of PCB 11 (0, 1.0 or 6.0 mg/kg) prior to conception through lactation. At postpartum day 21, brain, liver, and serum samples were analyzed for PCB 11 and its metabolites, and hepatic proteomic changes were assessed. Low detection of PCB 11 and its metabolites was observed in tissues, suggesting rapid clearance. Metabolite screening revealed OH-PCB 11, PCB 11 sulfate, and OH-PCB 11 sulfate metabolites in serum. Global proteomics identified significant alterations in hepatic protein expression, including downregulation of cytochrome P450 enzymes, solute carriers, and enzymes involved in fatty acid and steroid metabolism. Pathway enrichment analyses indicated disruptions in xenobiotic metabolism and endocrine pathways. These findings suggest that PCB 11 exposure during pregnancy and lactation impairs hepatic detoxification and metabolic capacity, potentially compromising maternal and offspring health. This work highlights the need for further investigation into the long-term consequences of PCB 11 exposure during pregnancy and lactation.

Corrigendum to “Loss of c-Met signaling sensitizes hepatocytes to lipotoxicity and induces cholestatic liver damage by aggravating oxidative stress” [Toxicology 361–362 (2016) 39–48] - Luis E. Gomez-Quiroz; Daekwan Seo; Yun-Han Lee; Mitsuteru Kitade; Timo Gaiser; Matthew Gillen; Seung-Bum Lee; Ma Concepcion Gutierrez-Ruiz; Elizabeth A. Conner; Valentina M. Factor; Snorri S. Thorgeirsson; Jens U. Marquardt (Toxicology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Functional analysis of wssv025 gene in the pathogenicity of white spot syndrome virus in Penaeus monodon - Shanel G. Manito; Cong-Yan Chen; Brandon Rafael de Jesús Castillo-Corea; Mary Nia M. Santos; Casiano H. Choresca; Fiona L. Pedroso; Christopher Marlowe Caipang; Han-Ching Wang; Fernand F. Fagutao (Fish & Shellfish Immunology, 2026)

A scalable machine learning approach for predicting wheat growth stages with a large national dataset - Harris D. Ledvinka; Si Yang Han; Rebecca J. Thistlethwaite; Richard M. Trethowan; Patrick Filippi (Field Crops Research, 2026)

Dissection of Fusarium head blight resistance in a modified nested association mapping panel of synthetic and bread wheat germplasm - Anil Karmacharya; Dhondup Lhamo; Krishna Acharya; Qijun Zhang; Han-Chang Chang; Shaobin Zhong; Andrew J. Green; Jason D. Fiedler; Mingcheng Luo; Kirk M. Anderson; Amanda R. Peters Haugrud; Elias M. Elias; et al. (Theoretical and Applied Genetics, 2026)

Deep Subdomain Adaptation Network for Three-Dimensional Mineral Prospectivity Modeling with Imbalanced Data: A Case Study of the Damiao–Hongshila Fe–V–Ti Belt, China - Zhiqiang Zhang; Wenliang Chen; Emmanuel John M. Carranza; Wei Han; Xinxing Liu; Yingjie Li; Juan Zhang; Feng Li; Ziyang Lu; Yongjun Su; Gongwen Wang (Natural Resources Research, 2026)

Application of the Keeling plot approach in quantifying sediment organic matter sources using carbon isotopes and C/N ratios: An example from Xiaowan Reservoir, Lancang River basin, China - Mingwei Guo; Shilu Wang; Kevin M. Yeager; Xiangfeng Han; Yuchun Wang; Shehong Li; Yufei Bao; Weiqi Lu; Zhenjie Zhao; Kun Liu; Jiaxi Wu (Applied Geochemistry, 2026)

Spatiotemporal Trade‐Offs and Synergies Among Environmental Footprints of Grain Crop Production in China - Fubin Sun; Wenfeng Liu; Han Su; Mesfin M. Mekonnen; Zenghui Xu; Wei Wang; Minhui Qiang; Xiangxiang Ji; Pute Wu; La Zhuo (Global Change Biology, 2026)
Human agricultural activities have exacerbated multiple types of natural resource depletion and environmental impacts through complex interactions with land, water, carbon, and nutrient cycles, which can be measured as corresponding environmental footprints (EFs). However, the spatiotemporal trade‐offs and synergies among multiple EFs in agricultural systems remain under‐quantified, hindering effective mitigation strategies. Here, we propose an assessment framework of spatiotemporal trade‐offs and synergies among multiple EFs of crop production, with a case study on blue water, green water, land, carbon, nitrogen, and phosphorus footprints for wheat, maize, rice, and soybean production across 31 Chinese provinces over 2000–2018. In total, 3630 pairwise EFs were analyzed. Results show that, although the EFs of unit mass crop production generally declined across provinces, national total EFs increased, with land, carbon, and phosphorus footprints rising by 16%, 17%, and 23%, respectively, during the study period. Synergistic interactions among EFs prevailed, comprising 50% positive and 32% negative synergies. The spatial distribution of trade‐offs and synergies varies by crop and region. Land use intensity is the main factor limiting the positive EF synergies.

Response of liquefiable sloping site to mainshock-aftershock ground motions - Junyan Han; Jiaxue Wang; Liyun Li; M. Hesham El Naggar; Chengshun Xu; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2026)

Clumped isotopes tracing methane cycle and budget: a review - Xinchu Wang; Cong-Qiang Liu; Jiaxu Han; Jiarui Liu; Timothy Csernica; Naizhong Zhang; Hu Ding; Jonathan Gropp; Jennifer McIntosh; Si-Liang Li; Sheng Xu; Rob M. Ellam (Earth-Science Reviews, 2026)

Waiting for the rains : An attempt to evaluate the efficiency of the large Roman cistern at Barbariga Stancija (Casematte, Istria, Croatia) - Fabian Welc; Agata Han; Krzysztof Markowicz; Davor Bulić; Robert Matijašić; Candace M. Rice; Ana Konestra; Andrew McLean (Journal of Quaternary Science, 2026)
Access to freshwater has always been a critical factor in sustaining human settlements, especially in regions with limited water resources. In the Mediterranean region, where dry summers and karst landscapes limit water availability, ancient societies developed advanced methods for collecting and storing rainwater. Among these, cisterns played an important role in securing drinking water supplies. Despite their historical importance, the efficiency of these installations remains less studied than that of monumental aqueducts. This study focuses on a large Roman cistern at Barbariga Stancija in south‐western Istria, Croatia, where rainwater harvesting was essential for sustaining local settlements and supporting intensive agricultural production. By integrating archaeological evidence, contemporary climatological analysis and paleoclimatic reconstructions, we have developed a quantitative model that simulates the performance of the cistern under varying rainfall conditions. The analysis uses high‐resolution meteorological data and Weibull distribution‐based simulations to estimate annual water storage capacity and variations in supply reliability. The study also assesses the maximum number of people the cistern could have supported, based on a reconstructed daily per capita water consumption rate. Our results suggest that under average rainfall conditions, the cistern could have reliably supported approximately 25–28 people throughout the year. However, seasonal variations in rainfall led to significant fluctuations in water availability, potentially leading to shortages during the dry summer months. Comparative analyses with other Roman cisterns in the Adriatic region provide a broader context for understanding the functionality and limitations of such storage systems within ancient water management strategies. This research not only enhances our understanding of local Roman hydraulic infrastructure but also contributes to broader discussions on sustainable water management in arid and semi‐arid climates. It highlights the need for interdisciplinary approaches that integrate archaeology, climatology and hydrological modelling to comprehensively assess ancient water supply mechanisms and their implications for modern water conservation strategies.

Plastisphere fungi from Yunnan, China: hydrolytic enzyme screening and taxonomic insights - Xue-Mei Chen; Jaturong Kumla; Pratthana Kodchasee; Wenhua Lu; Li-Su Han; Dongqin Dai; Abdallah M. Elgorban; Meiyan Han; Nakarin Suwannarach; Saowaluck Tibpromma (New Zealand Journal of Botany, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Mitigating the black-soil problem in the reflectance-to-fluorescence (R2F) relationship: A soil-adjusted reflectance-based approach for downscaling SIF - Peiqi Yang; Zhigang Liu; Dalei Han; Runfei Zhang; Bastian Siegmann; Jing Liu; Huarong Zhao; Uwe Rascher; Jing M. Chen; Christiaan van der Tol (Remote Sensing of Environment, 2025)

DDT exposure induces microglial activation and disease-associated microglial signatures: Relevance to mechanisms of Alzheimer’s disease - Isha Mhatre-Winters; Aseel Eid; Nicole Blum; Yoonhee Han; Ferass M. Sammoura; Long-Jun Wu; Jason R. Richardson (NeuroToxicology, 2025)

Smart prediction and optimization of air quality index with artificial intelligence - Muhammad Mubeen; Shuwei He; M. Safiur Rahman; Lijing Wang; Xin Zhang; Bashir Ahmed; Zhiwei He; Yinghui Han (Journal of Environmental Sciences, 2025)

Development of a marine probiotic bacterium producing nanobody and/or dsRNA against white spot syndrome virus (WSSV) - Mary Nia M. Santos; Fernand Fagutao; See-Yeun Ting; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Hofmeister-regulated fabrication of piezoelectric β-PVDF membrane: The specific ion effect on the membrane formation, piezoelectric property, and anti-fouling performance - R.D. Hope T. Cayron; Hannah Faye M. Austria; Tsung-Han Huang; Gabriel V. Carballo; Smrutiranjan Nayak; Alvin R. Caparanga; Wei-Song Hung; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2025)

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

Assessing humic acid as natural surfactant in sustainable electrokinetic remediation of low-permeability soil contaminated with petroleum hydrocarbons - J. Han; Y. J. Nam; H.-M. Ro; M. Kim (International Journal of Environmental Science and Technology, 2025)

Perspectives and Challenges in High-Resolution Whole-Atmosphere Modeling - Claudia Christine Stephan; Han-Li Liu; Huixin Liu; Xian Lu; Astrid Maute; Nicholas M. Pedatella; Valery A. Yudin (Surveys in Geophysics, 2025)

Correction: The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Development of a High-throughput Morphological Assay for Evaluating Mesenchymal Stromal Cell-derived Extracellular Vesicle Modulation of Brain Pericyte Secretory Phenotype - Courtney E. Campagna; Andrew M. Larey; Kanupriya R. Daga; Morgan Roos; Sneha Ghosh; Neil Grimsey; Jin Han; Ross A. Marklein (Stem Cell Reviews and Reports, 2025)
Mesenchymal stromal cell-derived extracellular vesicles (MSC-EVs) are a promising therapeutic tool for treating many neurodegenerative diseases. Neuroinflammation plays a major role in many of these conditions through an orchestration of interdependent processes that lead to the breakdown of the blood-brain barrier (BBB), infiltration of immune cells and neuronal death. MSC-EVs have shown preliminary evidence of modulating neuroinflammation, but their mechanisms of action are still unknown. Therefore, we explored the potential of MSC-EVs in modulating brain pericytes, a cell type that plays a critical role in BBB maintenance but has not been investigated as a therapeutic target for MSC-EVs. Brain pericytes are multifaceted cells that can modulate neuroinflammation through their involvement in BBB homeostasis, as well as the innate and adaptive immune response. Pericyte morphology has been shown to change in response to inflammatory stimuli in vivo, hence, we used this behavior to develop a quantitative morphological profiling approach to assess the immunomodulatory function of MSC-EVs in a high-throughput, low-cost manner. Using this assay, we were able to demonstrate that MSC-EVs manufactured under various conditions (2D, 3D, and in response to cytokine priming) could induce distinct pericyte morphological responses indicative of changes in secretion of chemokines and cytokines relevant to neuroinflammation.

Landslide mapping from post-event single-temporal polarimetric SAR image by a deep learning method exploiting a morphological model - Rubing Liang; Keren Dai; Juan M. Lopez-Sanchez; Yakun Han; Xianlin Shi; Qiang Xu (Remote Sensing of Environment, 2025)

Synergistic photocatalytic reduction of CO2 enabled by MIL-101(Cr)-TiO2-polyimide nanocomposite membranes - Lipei Ren; Shuaifei Zhao; Milad Laghaei; Han Wang; Jiaqi Zhang; Weimin Gao; Joselito M. Razal; Weilin Xu; Lingxue Kong (Journal of Environmental Chemical Engineering, 2025)

Provenance analysis of late Pleistocene sediment from IODP site U1477 reveals climate and river basin dynamics in the Zambezi river catchment - Youhong Gao; Hucai Zhang; Xiaonan Zhang; Lizeng Duan; Huayong Li; Ian R. Hall; Sidney R. Hemming; Leah J. LeVay; Junsheng Nie; Xibin Han; S. Barker; M.A. Berke; et al. (Gondwana Research, 2025)

Efficient adsorption of phosphate on magnetic Fe3O4@MOF@LDH superstructures: Kinetics, thermodynamics, and mechanisms - Zhang Liu; Wei Han; C. Marquina; Joseph K.C. Kwan; M. Ricardo Ibarra; King Lun Yeung (Environmental Research, 2025)

Ru-atom clusters embedded in Ti3C2Tx lattice for enhanced ammonium ion storage - Xiaofeng Zhang; Muhammad Sufyan Javed; Salamat Ali; Wei Xu; Peiao Lu; Awais Ahmad; Ammar M. Tighezza; Weihua Han; Kui-Qing Peng (Chemical Engineering Journal, 2025)

Whole Genome Sequencing Reveals How Plasticity and Genetic Differentiation Underlie Sympatric Morphs of Arctic Charr - Khrystyna Kurta; Mariano Olivera Fedi; Kendall Baker; Tom Barker; Leah Catchpole; Claudio Ciofi; Arianna Cocco; Joanna Collins; Genevieve Diedericks; Maria Angela Diroma; Alex Durrant; Kjetil Hindar; et al. (Molecular Ecology, 2025)
Salmonids have a remarkable ability to form sympatric morphs after postglacial colonisation of freshwater lakes. These morphs often differ in morphology, feeding and spawning behaviour. Here, we explored the genetic basis of morph differentiation in Arctic charr ( n = 283) by first establishing a high‐quality reference genome and then using this in whole genome sequencing of distinct morphs present in two Norwegian and two Icelandic lakes. The four lakes represent the spectrum of genetic differentiation between morphs from one lake with no genetic differentiation between morphs, implying phenotypic plasticity, to two lakes with locus‐specific genetic differentiation, implying incomplete reproductive isolation, and one lake with strong genome‐wide divergence consistent with complete reproductive isolation. As many as 12 putative inversions ranging from 0.45 to 3.25 Mbp in size segregated among the four morphs present in one lake, Thingvallavatn, and these contributed significantly to the genetic differentiation among morphs. None of the putative inversions were found in any of the other lakes, but there were cases of partial haplotype sharing in similar morph contrasts in other lakes. Our findings are consistent with a highly polygenic basis of morph differentiation with population‐specific selection on alleles linked to the development of similar morph phenotypes. The results support a model where morph differentiation is first established through phenotypic plasticity, leading to niche expansion and separation. This may be followed by gradual development of reproductive isolation, locus‐specific differentiation and eventually complete reproductive isolation and genome‐wide divergence.

Adaptive Evolution for Freshwater Adaptation in Coilia nasus by Directional Selection on Osmoregulation Genes - Shuang Han; Jie Wang; Taixing Lin; Jingping Zhang; Adelino V. M. Canario; Qigen Liu; Liangbiao Chen (Molecular Ecology, 2025)
The molecular mechanisms underlying the adaptation to freshwater habitats in fish of marine origin remain unclear. Grenadier anchovies, such as Coilia nasus , originate from marine environments and include both anadromous and freshwater‐resident conspecifics, making them ideal for studying adaptive evolution from marine to freshwater habitats. We conducted a comparative population genomic and transcriptome analysis of two distinct C. nasus lineages, one anadromous and the other freshwater‐resident, collected from mainstream and estuarine regions of the Yangtze River, China. By genome‐wide genotyping of the anadromous and the freshwater‐resident populations, we observed significant divergence in osmoregulation, energy metabolism, and immune response pathways associated with ecological adaptation and energy expenditure for migration. Some ion transport genes such as CAMK1 , ATP1α3 , KCNJ1 and SLC30A2 were identified that may contribute to freshwater adaptation. Notably, numerous mineralocorticoid signalling genes (e.g., NR3C2 , SGK1 , ATP1α3 , KCNJ1 ) exhibit dynamic change between the anadromous and freshwater populations, suggesting an important role for the hormone cortisol in regulating salinity acclimation in euryhaline fish. Among these genes, the ion channel ATP1α3 experienced adaptive amino acid substitutions (Val317Ile and Thr329Ser), which appear to be evolutionary hotspots across migratory species based on ortholog comparisons. These variants may facilitate sodium/potassium transport and highlight salinity tolerance as a key driver of divergence in anadromous fish transitioning to freshwater. These results enhance our understanding of the genetic basis underlying freshwater adaptation for an anadromous fish across osmotic boundaries.

P29-12 Four-Week Repeated Inhalation Toxicity Study of SiO2-ZnO Mixed Nanoparticles in Sprague-Dawley Rats - Y.-J. Heo; M.-J. Yang; H.-Y. Han; H.J. Jin; G.J. Oh; G.-H. Bae; M.-K. Song (Toxicology Letters, 2025)

Enhanced mapping of essential urban land use categories in China (EULUC-China 2.0): integrating multimodal deep learning with multisource geospatial data - Ziming Li; Bin Chen; Yufei Huang; Han Wang; Yadian Wang; Yiming Yuan; Xuecao Li; Jing M. Chen; Bing Xu; Peng Gong (Science Bulletin, 2025)

Hot hand thinking in children - Andreas Wilke; Gracie DeLaBruere; Steven Pedersen; Bang-Geul Han; Hannah Spilman; Yadhira Garcia; H. Clark Barrett; Peter M. Todd; Annie E. Wertz (Evolution and Human Behavior, 2025)

Phylogenetic distance drives rare cooperation in a competition-dominated cadmium stress environment - Fang Ma; Yi Jiang; Yanan Han; Yonghui Xing; Song Liu; Shuxin Tan; Qiaoyun Huang; Rasha M. El-Meihy; Wenli Chen (Environmental Research, 2025)

Soil functions are shaped by aridity through soil properties and the microbial community structure - Anna Doménech-Pascual; Luciana Chavez Rodriguez; Xingguo Han; Joan Pere Casas-Ruiz; Joan Ferriol-Ciurana; Jonathan Donhauser; Karen Jordaan; Steven D. Allison; Aline Frossard; Anders Priemé; Jean-Baptiste Ramond; Anna M. Romaní (Applied Soil Ecology, 2025)

Seismic response of sloping sites subject to near-fault pulse-like ground motions - Junyan Han; Jiaxue Wang; Liyun Li; Xiaoqiang Wang; M. Hesham El Naggar; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Modeling lamotrigine-induced reprotoxicity in porcine endometrial organoids: Integrated multi-platform profiling - Mariam M. Abady; Islam M. Saadeldin; Ayeong Han; Seonggyu Bang; Heejae Kang; Dong Wook Seok; Ha-Jeong Kwon; Jongki Cho; Ji-Seon Jeong (Reproductive Toxicology, 2025)

Association of urinary phthalate metabolite concentrations with inflammatory biomarker levels among pregnant women - Han Han; Sarah Grill; Xilin Shen; Paige L. Williams; Tamarra James-Todd; Jennifer B. Ford; Kathryn M. Rexrode; Antonia M. Calafat; Jorge E. Chavarro; Russ Hauser; Lidia Mínguez-Alarcón (Environmental Research, 2025)

A scaling approach for binary and grey computed tomography imaging of soil: A study in a coastal reclamation area - Xiaoqin Sun; Ana M. Tarquis; Dongli She; Xiao Han; Hongde Wang; Shengqiang Tang; Lei Gao; Pei Xin (CATENA, 2025)

Recent advances in layered double hydroxides for pharmaceutical wastewater treatment: A critical review - Yexiang Chen; Haihua Xu; M. Shahnawaz Khan; Shiqi Han; Sidi Zhu (Critical Reviews in Environmental Science and Technology, 2025)

The Natural History Study and Biomarker Collection of the Clinical Research Consortium for the Study of Cerebellar Ataxia (CRC-SCA) - Yicheng Lin; Nadia Amokrane; Sandie Worley; Lauren R. Moore; Andrew Rosen; Laura P. Crespo; Kelsey Trace; Tetsuo Ashizawa; Andrew Billnitzer; Susan Perlman; Aaron Fisher; Khalaf Bushara; et al. (The Cerebellum, 2025)

Past and future changes in potato production vulnerabilities in Maine, U.S - Eunjin Han; Amor V. M. Ines; David H. Fleisher (Climatic Change, 2025)
Maine's favorable climate for potato growth has been threatened by the changing climate as an unprecedented drought in 2020 resulted in a significant reduction in yield. This study investigated climate-induced vulnerabilities by conducting trend analysis for weather indices affecting potato growth, including daily minimum (T min ) and maximum temperature (T max ), length of dry spells, heatwave duration, several temperature thresholds critical to tuber quality, and tuber initiation. A crop simulation model was used to translate the climate data into more practical information for growers' decision-making and climate change adaptation associated with irrigation water requirement. This study confirmed the occurrence of increasing trends in the historical temperature record, particularly nighttime temperatures and heatwave duration, especially in Aroostook County, Maine's potato heartland. The increasing temperature was associated with higher probability of exceeding optimal temperature ranges, in excess of 20 °C, for potato tuber growth. To maintain current yields, growers will need to use more water for irrigation. Increasing temperatures make potatoes less water-efficient, offsetting the benefits of CO 2 fertilization. Future climate change scenarios revealed that potatoes will experience more heat-stressed days (T max > 32 °C) and stretches of sub-optimal temperatures by mid-century. Possible planting dates will shift 2–9 days earlier compared to historical averages. The irrigation water requirements will increase by up to 19% in the mid-century to meet potential potato production in the future. These results indicate that developing long-term strategies for managing agricultural water resources and improving water use efficiency are crucial to mitigating future vulnerabilities in Maine's potato industry. Highlights • Due to the warming climate, irrigation water requirements have, and will continue, to increase by the Mid-century. • Water use efficiency has decreased due to increasing temperature and ET. • The benefits of elevated CO 2 for WUE have declined because temperature increases exceed the optimal growth range. • Despite the humid climate in Maine, irrigation is critical to maintaining sustainable potato production.

Pharmacotherapeutic role of astringin against chromium induced nephrotoxicity via modulating TLR4/MyD88, HMGB1/RAGE and NF-κB pathway: A biochemical and pharmacokinetic approach - Han Hu; Muhammad Faisal Hayat; Syeda Sania Zahara; Ali Akbar; Khalid J. Alzahrani; Khalaf F. Alsharif; Fuad M. Alzahrani; Ahmed Al-Emam (Journal of Trace Elements in Medicine and Biology, 2025)

Ultrasound-assisted covalent cross-linking of egg white protein with ferulic acid: Structure, foaming, and application in chiffon cake - Bowen Xiao; Shihui Hua; Siyao Han; Huajiang Zhang; Wentao Zhang; Ning Xia; Fuming Yang; Rui Chuang; Mohamed Ghamry; Ahmed M. Rayan (Food Research International, 2025)

Exopolysaccharides from Rhizobium tropici mitigate Al phytotoxicity in Triticum aestivum - Huimin Zhang; Xinyun Xie; Steve L. Larson; John H. Ballard; Kauri A. Runge; Yan Meng; Subrata Chandra Roy; Saiful M. Islam; Fengxiang X. Han (Plant and Soil, 2025)

Synthesis of Population Trends Reveals Seascape‐Wide Reorganisation of Biodiversity From Microalgae to Birds - Anika Happe; Kasper J. Meijer; Jan‐Claas Dajka; Oscar Franken; Holger Haslob; Laura L. Govers; Michael Kleyer; Annebelle C. M. Kok; Lucie Kuczynski; Kertu Lõhmus; Sancia E. T. van der Meij; Han Olff; et al. (Global Change Biology, 2025)
Many monitoring programs aim to understand regional biodiversity patterns in relation to global and regional conservation targets, using either community‐wide biodiversity metrics to describe the community status or trends of pre‐selected “key” species as biodiversity change indicators. However, the former often lacks information on which species are changing, and the latter is heavily skewed towards specific taxa, potentially overlooking changes in other, functionally important taxa. We gathered an extensive set of monitoring data with over 3000 population trends (ranging from 5 to 91 years in duration) for a wide range of taxa across the Wadden Sea. We combined a systematic and quantitative categorization of population trends (weighted vote count) with a meta‐analysis on different taxonomic levels. This allowed the first cross‐taxa synopsis of species declines and increases and determined their directionalities throughout time. Our meta‐analysis showed an overall decrease in population size for fish, zooplankton, and plant species, while birds showed an overall increase. However, these increases mask recent negative trends within specific bird groups since the late 1990s. In contrast, fish populations exhibited declines over the entire monitoring period. Species with declining populations (losers) were phylogenetically related, whereas species with increasing populations (winners) represented various organismal groups. Directionality and onsets of change in population trends were temporally synchronized throughout several groups, such as bivalves, fish, and birds, and may provide warning signals for future local extinctions in these taxa. Our analysis moves beyond typical indicator species by including the entire species inventory of the system. Basal trophic levels of aquatic ecosystems, such as zooplankton and phytoplankton, are often missing from policy assessments but are among the most important organism groups for ecosystem functioning. Here, we show that without additional monitoring effort, a systematic analysis of population trends adds to our understanding of trophic and compositional restructuring of ecosystems.

Contrasting responses of flowering phenology in C 3 and C 4 plants shape grassland community structure under global change - Lu Bai; Guodong Han; Lin Jiang; Thomas W. Crowther; Constantin M. Zohner; Kailiang Yu; Zhuwen Xu; Zhongwu Wang; Qian Wu; Yi Zhu; Jinglei Tang; Haiyan Ren (Ecology, 2025)
Climate change is known to affect plant phenology. Yet, the sensitivity of flowering phenology in dryland regions to climate change, and the potential implications for community composition, remain largely unexplored. Here, we used an 18‐year field experiment to investigate the effects of climate warming and nitrogen addition on flowering phenology of four C 3 plant species and two C 4 plant species, and the cascading effects on the relative abundance of C 3 and C 4 plants in a desert steppe. Across the past 10 years of the experiment (2013–2022), we found that warming had a greater effect on phenological shifts in C 3 than in C 4 plants. Warming significantly advanced the flowering time of C 3 plants by 4.3 ± 0.1 days and of C 4 plants by 2.8 ± 0.1 days, respectively. Warming also reduced the duration of flowering by 1.8 ± 0.1 days for C 3 plants but had no effect on C 4 plants, and decreased the dominance of C 3 plants compared to C 4 plants. Nitrogen addition extended the duration of flowering of C 4 plants by 3.4 ± 0.2 days and increased their relative dominance, while decreasing the dominance of C 3 plants. Structural equation models revealed that these phenological responses were largely driven by soil temperature and soil water availability. Our results demonstrate that the different phenological responses of C 3 and C 4 plants contribute to shifts in dominance between these plant types in temperate dryland ecosystems under global changes.

The Cerebellar Neuropsychiatric Rating Scale in the Spinocerebellar Ataxias - Anna L. Burt; Maureen P. Daly; Janet C. Sherman; Jeremy D. Schmahmann; Susan L. Perlman; Liana S. Rosenthal; Sheng-Han Kuo; Tetsuo Ashizawa; Theresa Zesiewicz; Cameron Dietiker; Puneet Opal; Antoine Duquette; et al. (The Cerebellum, 2025)

Retraction notice to “Biodiesel synthesis from Prunus bokhariensis non-edible seed oil by using green silver oxide nanocatalyst” [Chemosphere 291, Part 2, March 2022, 132780] - Sumreen Dawood; Mushtaq Ahmad; Muhammad Zafar; Saira Asif; Jiří Jaromír Klemeš; Awais Bokhari; Muhammad Mubashir; Ning Han; Mohamed M. Ibrahim; Zeinhom M. El-Bahy; Kuan Shiong Khoo (Chemosphere, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Coprostanol records from two distinct prehistoric profiles in the middle and lower reaches of the Yellow River, China, provide evidence of anthropogenic fires - Zhihai Tan; Qi Zhang; Yongming M Han; Longjiang Mao; Shuxin Zheng; Meng Wang; Huanrong Zuo; Hanmiao Qin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Organic solvents tuned polymer derived-sulfonated microporous carbon structures enable resource regeneration and recovery in flow electrode capacitive deionization - T.M. Subrahmanya; Liang-Yan Gua; Hannah Faye M. Austria; Tsung-Han Huang; Shalligito Habetamu Abebe; Wei-Song Hung; Chih-Feng Wang; Chien-Chieh Hu; Kueir-Rarn Lee; Juin-Yih Lai (Desalination, 2025)

Mobile air monitoring to identify volatile organic compound distributions and potential hazard during the remediation of the East Palestine, Ohio train derailment - Mariana Saitas; Toriq Mustapha; Eva Vitucci; Oladayo Oladeji; Han-Hsuan D. Tsai; Carolyn Cannon; Ivan Rusyn; Albert A. Presto; Weihsueh A. Chiu; Natalie M. Johnson (Environmental Monitoring and Assessment, 2025)
On February 3, 2023, a train carrying hazardous chemicals derailed in East Palestine, Ohio. Initial mobile air monitoring in mid-February 2023 revealed unique spatiotemporal patterns for a range of volatile organic compounds (VOCs). To determine long-term impacts on air quality, two follow up mobile air monitoring campaigns were carried out in March and April 2023 on public roadways using a proton transfer reaction time-of-flight mass spectrometer. This study aimed to characterize VOC distributions, identify hotspots, and characterize potential hazards. Concentrations of targeted VOCs benzene, toluene, and xylenes were lower overall in East Palestine in April compared to March. Overall, more compounds ( n = 48) were identified using non-targeted analysis (NTA) in East Palestine in March compared with April ( n = 30). Several of these VOCs were uniquely identified during March sampling, and among the commonly detected compounds, higher average concentrations were observed in East Palestine compared background levels. Spatial analysis revealed similar patterns of hotspots for benzene and additional VOCs identified from NTA, including C 3 H 4 O, C 4 H 8 O, and C 6 H 12 O. Using the EPA Hazard Comparison Dashboard, 49% and 40% of the identified VOCs were classified as “very high” or “high” hazards for eye and skin irritation, respectively. Notably, eye and skin irritation were among the common symptoms reported by the residents near the disaster site. Additionally, 29%, 18%, and 14% of the identified VOCs were classified as “very high” or “high” hazards for genotoxicity/mutagenicity, acute inhalation toxicity, and acute dermal toxicity, respectively. Collectively, these findings provide exposure data supportive of the reported health concerns and demonstrate the application of mobile monitoring coupled with NTA as a novel approach for rapid identification and mapping of potentially hazardous chemicals following an environmental disaster.

Multiple measures to mitigate methane emissions from organic rice fields: a review and future challenges - Nuri Baek; Se-In Lee; Husna Israt Pia; Seo-Woo Park; Eun-Seo Shin; Miwa M. Yashima; Han-Yong Kim; Hyun-Jin Park; Woo-Jung Choi (Journal of Soils and Sediments, 2025)

Effect of extracellular vesicles derived from oviductal and uterine fluid on the development of porcine preimplantation embryos - Ayeong Han; Ahmad Yar Qamar; Seonggyu Bang; Heyyoung Kim; Heejae Kang; Jun-Hyeong Kim; Kimyung Choi; Sung Ho Yun; Seung Il Kim; Islam M. Saadeldin; Sanghoon Lee; Jongki Cho (Theriogenology, 2025)

Co-adsorption of methylene blue/Pb(II) from aqueous solutions using sulfonated mesoporous diatomite - Ali M. Abou-Elanwar; So Young Lee; Jeongkyun Yu; Jieun Kim; Chihyun Hwang; Hyungmin Park; Young-tai Noh; Ming Xie; Jiuyang Lin; Seong-Ju Park; Dong Han Seo; Youngjin Kim (Journal of Water Process Engineering, 2025)

Characteristics of elevated PM2.5 events driven by enhanced organic compound concentrations in a South Korean residential city - Hye-Ji Lee; Hyo-Won Lee; Sung-Won Park; Ji-Won Jeon; Pyung-Rae Kim; Kyung-Hwan Kwak; Young-Ji Han; Thomas M. Holsen; Seung-Ha Lee; Hyun-Gu Jung; Seung-Hwan Cha; Jung-Min Park; et al. (Atmospheric Environment, 2025)

An innovative method for the preservation and exhibition of four plastination specimens from a single minke whale (Balaenoptera acutorostrata) - Wen-Bin Jiang; Xue Song; M. Adeel Alam Shah; Jian Han; Xue-Wei Ma; Hong-Jin Sui (Frontiers in Marine Science, 2025)
Plastination represents the most advanced technique for preserving biological specimens, widely adopted in education, scientific research, and popular science. This study employed the technique of plastination to explore an innovative method for preserving and exhibiting minke whales, addressing challenges to optimize the use of rare marine mammal specimens and the multi-layered understanding of cetacean anatomy. A 6.5-meter-long adult female minke whale cadaver, weighing 3,368 kg, was dissected, plastinated with polymers, and assembled with internal support frames. Subsequently, skin, muscle, bone, and viscera specimens were prepared separately. The four specimens of the minke whale can be displayed together or individually, and their internal and external structures have been mostly well preserved, with superb surface textures and fine details. This marks the first application of plastination technique to create four distinct presentations from a single minke whale cadaver globally, which significantly conserves biological materials by maximizing the use of a single rare animal body. The innovative plastination technique not only broadens our understanding of cetacean biology but also establishes a sustainable model for preserving rare marine specimens, offering insights into the relationship between structures and functions, as well as environmental adaptations. This study will provide valuable tools for education, research, and popular science education.

Elevated vascular endothelial growth factor a is associated with disruption of default network connectivity in older adults - Arunima Kapoor; Jung Yun Jang; Allison C. Engstrom; Trevor Lohman; Shubir Dutt; John Paul M. Alitin; Isabel J. Sible; Anisa Marshall; Fatemah Shenasa; Aimee Gaubert; Amy Nguyen; David Robert Bradford; et al. (Brain Imaging and Behavior, 2025)
Vascular Endothelial Growth Factor A (VEGF-A) is an angiogenic signaling protein involved in the maintenance of the cerebral vasculature. No prior study has explored whether plasma VEGF-A levels may be associated with brain functional connectivity changes, such as disruption of the default mode network (DMN), which often precedes the development of cognitive changes in aging. Seventy-six independently living older adults (mean age = 70.3 years; SD = 7.5; 31.6% male) free of dementia or clinical stroke underwent venipuncture and brain MRI. Plasma was assayed for VEGF-A. Using resting state functional MRI, region of interest (ROI) to ROI connectivity and graph theory analysis were conducted to determine average connectivity and global efficiency between each of the following ROIs comprising the DMN: medial prefrontal cortex, lateral parietal cortex and precuneus cortex. Multiple linear regression analysis revealed a significant negative association between VEGF-A levels and DMN connectivity (B = − 0.14, 95% CI (-0.26, − 0.01), p =.038), accounting for age, sex, education, and vascular risk factors. Graph theory analysis similarly revealed that VEGF-A levels are associated with global efficiency of the entire network (B = − 0.18, p =.004). These findings suggest that VEGF-A may be elevated early in the progression of neurocognitive disorders. Whether higher levels of VEGF-A contribute to the pathogenesis of neurocognitive disorders or play a protective role in preserving cognitive function warrants further investigation. Clinical Trial Number: N/A; None.

A novel cross-priming amplification technique combined with lateral flow strips for rapid and visual detection of zoonotic Toxoplasma gondii - Yao Liang; Yuan-Hui He; Shu-Feng Yang; Shi-Chen Xie; Yi-Han Lv; Wei Cong; Hany M. Elsheikha; Xing-Quan Zhu (Veterinary Parasitology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Neoarchean orogenic belt evolution in the northeast North China Craton: Implications for the reconstruction of early Earth’s microplates - Guozheng Sun; Shuwen Liu; Sanzhong Li; Timothy M. Kusky; Fangyang Hu; Han Bao; Lei Gao; Yalu Hu; Shengyao Yu; Liming Dai; Lintao Wang; Xi Wang (Precambrian Research, 2025)

Zircon U-Pb ages, trace elements, and Hf isotopes establish a genetic link between volcanic ash beds and porphyritic intrusions during early Silurian in the South China Block - Tianrui Wang; Bo Ran; Shugen Liu; M. Santosh; Zhiwu Li; Yuyue Han; Yuehao Ye (Lithos, 2025)

Scalable fabrication of a tough and recyclable spore-bearing biocomposite thermoplastic polyurethane - Han Sol Kim; Evan M. White; Grant Crane; Kush Patel; Myung Hyun Noh; Md Arifur Rahman; Adam M. Feist; Jason J. Locklin; Jonathan K. Pokorski (Chemical Engineering Journal, 2025)

Eco-friendly lamellar structured graphene oxide-Lysine nanocomposite membranes with varying d-spacing for enhanced pervaporation desalination - Shalligito Habetamu Abebe; Hannah Faye M. Austria; T.M. Subrahmanya; Huai-Che Chang; Tsung-Han Huang; Gabriel V. Carballo; Wei-Song Hung; Chien-Chieh Hu; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2025)

Tree height–diameter allometry of Populus euphratica across riparian Tugay forests along a gradient of groundwater table depths - Dong He; Lu Han; Ümüt Halik; Tayierjiang Aishan; Frank M. Thomas (Trees, 2025)

Genome-wide identification of cis-regulatory elements and transcription factors associated with promoted callus formation in Brachypodium distachyon - Xin Zhang; Yan Dai; Qi Chen; Xiaobing Kou; Eid M. Mehareb; Ghulam Raza; Wei Wang; Ruqin Zhou; Robert Hasterok; Jinlei Han; Kai Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Ultimate bearing capacity of sand under lateral movement of buried pipelines - Zilan Zhong; Lingyue Xu; Chuntang Han; Junyan Han; M. Hesham El Naggar; Jinqiang Li; Xin Zhao; Huiquan Miao (Soil Dynamics and Earthquake Engineering, 2025)

Trends and classification of aerosol observed from MODIS sensor over Northern Europe and the Arctic - Kyung M. Han; Chang H. Jung; Chul H. Song; Ja H. Koo; Young J. Yoon; Bang Y. Lee; Hyun S. Kim; S. Seo (Atmospheric Pollution Research, 2025)

Correction: Relationship between south Asian summer monsoon intensity and north Indian ocean tropical cyclone activity - Ruoqi Wang; Shuzong Han; Donghui Sun; M. V. Subrahmanyam (Climate Dynamics, 2025)

Deep shared proxy construction hashing for cross-modal remote sensing image fast target retrieval - Lirong Han; Mercedes E. Paoletti; Sergio Moreno-Álvarez; Juan M. Haut; Antonio Plaza (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

The fungal strain promotes rapid agarwood resin production with medicinally accepted agarotetrol level - Tian-Ye Du; Saowaluck Tibpromma; Kevin D. Hyde; Yue-Hu Wang; Putarak Chomnunti; Ekachai Chukeatirote; Wen-Hua Lu; Ausana Mapook; Dong-Qin Dai; Douglas S.A. Wijesundara; Abdallah M. Elgorban; Nakarin Suwannarach; et al. (Food Bioscience, 2024)

Optimizing tomato waste hydrolysate for enhanced fucoxanthin biosynthesis in mixotrophic cultivation of Isochrysis galbana - Xi-Wen Fan; Han Sun; Derek M. Ayittey; Zhi-gang Zhou; Carol Sze Ki Lin; Tao Tang; Zheng Sun (Bioresource Technology, 2024)

Correction to: Harnessing green tide Ulva biomass for carbon dioxide sequestration - Jihae Park; Hojun Lee; De Saeger; Stephen Depuydt; Jana Asselman; Colin Janssen; Philippe M. Heynderickx; Di Wu; Frederik Ronsse; Filip M. G. Tack; Masanori Hiraoka; Lalit K. Pandey; et al. (Reviews in Environmental Science and Bio/Technology, 2024)

Harnessing green tide Ulva biomass for carbon dioxide sequestration - Jihae Park; Hojun Lee; Jonas De Saeger; Stephen Depuydt; Jana Asselman; Colin Janssen; Philippe M. Heynderickx; Di Wu; Frederik Ronsse; Filip M. G. Tack; Masanori Hiraoka; Lalit K. Pandey; et al. (Reviews in Environmental Science and Bio/Technology, 2024)

RETRACTED: Enhancing battery pack safety against cone impact using machine learning techniques and Gaussian noise - Qian Zhang; Shaoyong Han; Azher M. Abed; Ali Basem; Mohamed R. El-Sharkawy; Bashir Salah; Ibrahim Mahariq (Process Safety and Environmental Protection, 2024)

FireBox and CharBoss: An alternative to open burning of woody biomass - Paul O. Oyier; Han-Sup Han; Dipita Ghosh; Nathaniel Anderson; Deborah S. Page-Dumroese; Daniel W. McCollum; Joanne M. Tirocke; Derek N. Pierson (Biomass and Bioenergy, 2024)

Relationship between south Asian summer monsoon intensity and north Indian ocean tropical cyclone activity - Ruoqi Wang; Shuzong Han; Donghui Sun; M. V. Subrahmanyam (Climate Dynamics, 2024)

ACVR1/ALK2-p21 signaling axis modulates proliferation of the venous endothelium in the retinal vasculature - Boryeong Pak; Minjung Kim; Orjin Han; Heon-Woo Lee; Alexandre Dubrac; Woosoung Choi; Jee Myung Yang; Kevin Boyé; Heewon Cho; Kathryn M. Citrin; Injune Kim; Anne Eichmann; et al. (Angiogenesis, 2024)

Weight stigma as a stressor: A preliminary multi-wave, longitudinal study testing the biobehavioral pathways of the cyclic obesity/weight-based stigma (COBWEBS) model - Kristen M. Lee; Christy Wang; Han Du; Jeffrey Hunger; A. Janet Tomiyama (Appetite, 2024)

Comparison of drug-induced liver injury risk between propylthiouracil and methimazole: A quantitative systems toxicology approach - Qingfeng He; Min Li; Peiying Ji; Aole Zheng; Li Yao; Xiao Zhu; Jae-Gook Shin; Volker M. Lauschke; Bing Han; Xiaoqiang Xiang (Toxicology and Applied Pharmacology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Estimating ambient air pollutant concentrations outside and inside homes in the Subpopulations and Intermediate outcomes in COPD air pollution (SPIROMICS air) cohort - Kipruto Kirwa; Amanda J. Gassett; Coralynn Sack; Laura M. Paulin; Cheryl S. Pirozzi; R. Graham Barr; Prescott G. Woodruff; MeiLan Han; May-Lin Wilgus; Igor Barjaktarevic; Stephen Peters; Nadia N. Hansel; et al. (Environmental Research, 2024)

Green wood bio-adhesives from cellulose-derived bamboo powder hydrochars - Yong-Xing Chen; Han-Song Zhu; Fan Gao; Huan-Ran Xiong; Huan Yang; Zhi-Xiang Xu; Pei-Gao Duan; Li-Jun Zheng; Sameh M. Osman; Rafael Luque (Chemical Engineering Journal, 2024)

Self-condensation for enhancing the hydrophilicity of covalent organic polymers and photocatalytic hydrogen generation with unprecedented apparent quantum yield up to 500 nm - Islam M.A. Mekhemer; Ahmed M. Elewa; Mohamed M. Elsenety; Maha Mohamed Samy; Mohamed Gamal Mohamed; Ahmed Fouad Musa; Tse-Fu Huang; Tzu-Chien Wei; Shiao-Wei Kuo; Bo-Han Chen; Shang-Da Yang; Ho-Hsiu Chou (Chemical Engineering Journal, 2024)

Harnessing the power of tidal flat diatoms to combat climate change - Jihae Park; Hojun Lee; Jana Asselman; Colin Janssen; Stephen Depuydt; Jonas De Saeger; Thomas Friedl; Koen Sabbe; Wim Vyverman; Catharina J. M. Philippart; Jaime Pitarch; Philippe M. Heynderickx; et al. (Critical Reviews in Environmental Science and Technology, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Invasive plant species support each other's growth in low‐nutrient conditions but compete when nutrients are abundant - Ayub M. O. Oduor; Han Yu; Yanjie Liu (Ecology, 2024)
Globally, numerous ecosystems have been co‐invaded by multiple exotic plant species that can have competitive or facilitative interactions with each other and with native plants. Invaded ecosystems often exhibit spatial heterogeneity in soil moisture and nutrient levels, with some habitats having more nutrient‐rich and moist soils than others. The stress‐gradient hypothesis predicts that plants are likely to engage in facilitative interactions when growing in stressful environments, such as nutrient‐deficient or water‐deficient soils. In contrast, when resources are abundant, competitive interactions between plants should prevail. The invasional meltdown hypothesis proposes that facilitative interactions between invasive species can enhance their establishment and amplify their ecological impact. Considering both hypotheses can offer insights into the complex interactions among invasive and native plants across environmental gradients. However, experimental tests of the effects of soil moisture and nutrient co‐limitation on interactions between invasive and native plants at both interspecific and intraspecific levels in light of these hypotheses are lacking. We performed a greenhouse pot experiment in which we cultivated individual focal plants from five congeneric pairs of invasive and native species. Each focal plant was subjected to one of three levels of plant–plant interactions: (1) intraspecific, in which the focal plant was grown with another individual of the same species; (2) interspecific, involving a native and an invasive plant; and (3) interspecific, involving two native or invasive individuals. These plant–plant interaction treatments were fully crossed with two levels of water availability (drought vs. well‐watered) and two levels of nutrient supply (low vs. high). Consistent with the stress‐gradient and invasional meltdown hypotheses, our findings show that under low‐nutrient conditions, the biomass production of invasive focal plants was facilitated by invasive interspecific neighbors. However, under high‐nutrient conditions, the biomass production of invasive focal plants was suppressed by invasive interspecific neighbors. When competing with native interspecific neighbors, high‐nutrient conditions similarly enhanced the biomass production of both invasive and native focal plants. Invasive and native focal plants were neither competitively suppressed nor facilitated by conspecific neighbors. Taken together, these results suggest that co‐occurring invasive exotic plant species may facilitate each other in low‐nutrient habitats but compete in high‐nutrient habitats.

Cytotoxicity and cell membrane interactions of choline-based ionic liquids: Comparing amino acids, acetate, and geranate anions - Mohamad El Mohamad; Qi Han; Brendan Dyett; Haitao Yu; Sara Edgecomb; Mercedes C. Pride; Claylee M. Chism; Angela Roberts; Deauntaye Jones; Eden E.L. Tanner; Calum J. Drummond; Tamar L. Greaves; et al. (Chemosphere, 2024)

Evolutionary ecology of masting: mechanisms, models, and climate change - Michal Bogdziewicz; Dave Kelly; Davide Ascoli; Thomas Caignard; Francesco Chianucci; Elizabeth E. Crone; Emilie Fleurot; Jessie J. Foest; Georg Gratzer; Tomika Hagiwara; Qingmin Han; Valentin Journé; et al. (Trends in Ecology & Evolution, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Melatonin and resveratrol alleviate molecular and metabolic toxicity induced by Bisphenol A in endometrial organoids - Mariam M. Abady; Islam M. Saadeldin; Ayeong Han; Seonggyu Bang; Heejae Kang; Dong Wook Seok; Ha-Jeong Kwon; Jongki Cho; Ji-Seon Jeong (Reproductive Toxicology, 2024)

Effects of neonicotinoid residues on non-target soil animals: A case study of meta-analysis - Yuxuan Cao; Wenting Zhao; Jinrui Zhang; Daniel M. Figueiredo; Mingyu Zhao; Siyang Ren; Hongyu Mu; Yiyi Li; Huan Lu; Haoyuan Shi; Xin Li; Jindong Li; et al. (Journal of Hazardous Materials, 2024)

β-adrenergic stimulation after rewarming does not mitigate hypothermia-induced contractile dysfunction in rat cardiomyocytes - Torstein Schanche; Young Soo Han; Cole W. Jensen; Grace M. Arteaga; Torkjel Tveita; Gary C. Sieck (Cryobiology, 2024)

High performance lamellar structured graphene oxide nanocomposite membranes via Fe3O4-coordinated phytic acid control of interlayer spacing for organic solvent nanofiltration (OSN) - Shalligito Habetamu Abebe; T.M. Subrahmanya; Hannah Faye M. Austria; Smrutiranjan Nayak; Tsung-Han Huang; Owen Setiawan; Wei-Song Hung; Chien-Chieh Hu; Kueir-Rarn Lee; Juin-Yih Lai (Chemical Engineering Journal, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Effects of Mediterranean diets and nutrigenomics on cardiovascular health - Saad Bakrim; Sara Aboulaghras; Tarik Aanniz; Taoufiq Benali; Nasreddine El Omari; Mohamed El-Shazly; Learn-Han Lee; Syed Khalid Mustafa; Nargis Sahib; Maksim Rebezov; Mohammad Ali Shariati; Jose M. Lorenzo; et al. (Critical Reviews in Food Science and Nutrition, 2024)

A near-complete cucumber reference genome assembly and Cucumber-DB, a multi-omics database - Jiantao Guan; Han Miao; Zhonghua Zhang; Shaoyun Dong; Qi Zhou; Xiaoping Liu; Diane M. Beckles; Xingfang Gu; Sanwen Huang; Shengping Zhang (Molecular Plant, 2024)

Seismic fragility analysis of buried pipelines under Kahramanmaraş ground motions - Xiaoqiang Wang; Junyan Han; Anqi Kang; M. Hesham El Naggar; Huiquan Miao; Chengshun Xu (Engineering Geology, 2024)

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Sustainable regulation of calcium magnesium phosphate and rapeseed cake on soil-tea system in Mount Lushan, China - C. Han; Y. Ding; Z. J. Tang; Y. Q. Lai; M. Liu (Environmental Geochemistry and Health, 2024)

Human atherosclerotic plaque transcriptomics reveals endothelial beta-2 spectrin as a potential regulator a leaky plaque microvasculature phenotype - Timo Rademakers; Marco Manca; Han Jin; Tanguy Orban; Ljubica Matic Perisic; Hubertus J. M. Frissen; Frank Rühle; Petra Hautvast; Jos van Rijssel; Kim van Kuijk; Barend M. E. Mees; Carine J. Peutz-Kootstra; et al. (Angiogenesis, 2024)
The presence of atherosclerotic plaque vessels is a critical factor in plaque destabilization. This may be attributable to the leaky phenotype of these microvessels, although direct proof for this notion is lacking. In this study, we investigated molecular and cellular patterns of stable and hemorrhaged human plaque to identify novel drivers of intraplaque vessel dysfunction. From transcriptome data of a human atherosclerotic lesion cohort, we reconstructed a co-expression network, identifying a gene module strongly and selectively correlated with both plaque microvascular density and inflammation. Spectrin Beta Non-Erythrocytic 1 ( sptbn1 ) was identified as one of the central hubs of this module (along with zeb1 and dock1 ) and was selected for further study based on its predominant endothelial expression. Silencing of sptbn1 enhanced leukocyte transmigration and vascular permeability in vitro, characterized by an increased number of focal adhesions and reduced junctional VE-cadherin. In vivo, sptbn1 knockdown in zebrafish impaired the development of the caudal vein plexus. Mechanistically, increased substrate stiffness was associated with sptbn1 downregulation in endothelial cells in vitro and in human vessels. Plaque SPTBN1 mRNA and protein expression were found to correlate with an enhanced presence of intraplaque hemorrhage and future cardiovascular disease (CVD) events during follow-up. In conclusion, we identify SPTBN1 as a central hub gene in a gene program correlating with plaque vascularisation. SPTBN1 was regulated by substrate stiffness in vitro while silencing blocked vascular development in vivo, and compromised barrier function in vitro. Together, SPTBN1 is identified as a new potential regulator of the leaky phenotype of atherosclerotic plaque microvessels.

IC100, a humanized therapeutic monoclonal anti-ASC antibody alleviates oxygen-induced retinopathy in mice - Huijun Yuan; Shaoyi Chen; Matthew R. Duncan; Juan Pablo de Rivero Vaccari; Robert W. Keane; W. Dalton Dietrich; Tsung-Han Chou; Merline Benny; Augusto F. Schmidt; Karen Young; Kevin K. Park; Vittorio Porciatti; et al. (Angiogenesis, 2024)
Background Retinopathy of prematurity (ROP), which often presents with bronchopulmonary dysplasia (BPD), is among the most common morbidities affecting extremely premature infants and is a leading cause of severe vision impairment in children worldwide. Activations of the inflammasome cascade and microglia have been implicated in playing a role in the development of both ROP and BPD. Apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) is pivotal in inflammasome assembly. Utilizing mouse models of both oxygen-induced retinopathy (OIR) and BPD, this study was designed to test the hypothesis that hyperoxia induces ASC speck formation, which leads to microglial activation and retinopathy, and that inhibition of ASC speck formation by a humanized monoclonal antibody, IC100, directed against ASC, will ameliorate microglial activation and abnormal retinal vascular formation. Methods We first tested ASC speck formation in the retina of ASC-citrine reporter mice expressing ASC fusion protein with a C-terminal citrine (fluorescent GFP isoform) using a BPD model that causes both lung and eye injury by exposing newborn mice to room air (RA) or 85% O 2 from postnatal day (P) 1 to P14. The retinas were dissected on P14 and retinal flat mounts were used to detect vascular endothelium with AF-594-conjugated isolectin B4 (IB4) and citrine-tagged ASC specks. To assess the effects of IC100 on an OIR model, newborn ASC citrine reporter mice and wildtype mice (C57BL/6 J) were exposed to RA from P1 to P6, then 75% O 2 from P7 to P11, and then to RA from P12 to P18. At P12 mice were randomized to the following groups: RA with placebo PBS (RA-PBS), O 2 with PBS (O 2 -PBS), O 2 + IC100 intravitreal injection (O 2 -IC100-IVT), and O 2 + IC100 intraperitoneal injection (O 2 -IC100-IP). Retinal vascularization was evaluated by flat mount staining with IB4. Microglial activation was detected by immunofluorescence staining for allograft inflammatory factor 1 (AIF-1) and CD206. Retinal structure was analyzed on H&E-stained sections, and function was analyzed by pattern electroretinography (PERG). RNA-sequencing (RNA-seq) of the retinas was performed to determine the transcriptional effects of IC100 treatment in OIR. Results ASC specks were significantly increased in the retinas by hyperoxia exposure and colocalized with the abnormal vasculature in both BPD and OIR models, and this was associated with increased microglial activation. Treatment with IC100-IVT or IC100-IP significantly reduced vaso-obliteration and intravitreal neovascularization. IC100-IVT treatment also reduced retinal microglial activation, restored retinal structure, and improved retinal function. RNA-seq showed that IC100 treatment corrected the induction of genes associated with angiogenesis, leukocyte migration, and VEGF signaling caused by O 2 . IC100 also corrected the suppression of genes associated with cell junction assembly, neuron projection, and neuron recognition caused by O 2 . Conclusion These data demonstrate the crucial role of ASC in the pathogenesis of OIR and the efficacy of a humanized therapeutic anti-ASC antibody in treating OIR mice. Thus, this anti-ASC antibody may potentially be considered in diseases associated with oxygen stresses and retinopathy, such as ROP.

Navigating the complexity of p53-DNA binding: implications for cancer therapy - Kelly M. Thayer; Sean Stetson; Fernando Caballero; Christopher Chiu; In Sub Mark Han (Biophysical Reviews, 2024)
The tumor suppressor protein p53, a transcription factor playing a key role in cancer prevention, interacts with DNA as its primary means of determining cell fate in the event of DNA damage. When it becomes mutated, it opens damaged cells to the possibility of reproducing unchecked, which can lead to formation of cancerous tumors. Despite its critical role, therapies at the molecular level to restore p53 native function remain elusive, due to its complex nature. Nevertheless, considerable information has been amassed, and new means of investigating the problem have become available. Objectives We consider structural, biophysical, and bioinformatic insights and their implications for the role of direct and indirect readout and how they contribute to binding site recognition, particularly those of low consensus. We then pivot to consider advances in computational approaches to drug discovery. Materials and methods We have conducted a review of recent literature pertinent to the p53 protein. Results Considerable literature corroborates the idea that p53 is a complex allosteric protein that discriminates its binding sites not only via consensus sequence through direct H-bond contacts, but also a complex combination of factors involving the flexibility of the binding site. New computational methods have emerged capable of capturing such information, which can then be utilized as input to machine learning algorithms towards the goal of more intelligent and efficient de novo allosteric drug design. Conclusions Recent improvements in machine learning coupled with graph theory and sector analysis hold promise for advances to more intelligently design allosteric effectors that may be able to restore native p53-DNA binding activity to mutant proteins. Clinical relevance The ideas brought to light by this review constitute a significant advance that can be applied to ongoing biophysical studies of drugs for p53, paving the way for the continued development of new methodologies for allosteric drugs. Our discoveries hold promise to provide molecular therapeutics which restore p53 native activity, thereby offering new insights for cancer therapies. Graphical Abstract

Molecular phylogeny and morphology reveal two new species of Conocybe (Bolbitiaceae, Agaricales) from southwest China - Wenhua Lu; Nakarin Suwannarach; Saisamorn Lumyong; Abdallah M. Elgorban; Dong-Qin Dai; Arun K. Dutta; Li-Hong Han; Saowaluck Tibpromma; Samantha C. Karunarathna (New Zealand Journal of Botany, 2024)

Vector-valued fragility analysis of subway station structures subjected to the Kahramanmaras earthquake - Zhike Guo; Junyan Han; M. Hesham El Naggar; Yansong Bi; Chengshun Xu; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2024)

Reducing air pollution does not necessarily reduce related adults' mortality burden: Variations in 177 countries with different economic levels - Xiuling Zhao; Tong Wu; Weiqi Zhou; Lijian Han; Andreas M. Neophytou (Science of The Total Environment, 2024)

Utilization of carbon dioxide using electrochemical reduction: A review - Mansoor Al-Shamari; Ahmed Khodary; Dong Suk Han; Iqbal M. Mujtaba; N. Rahmanian (Gas Science and Engineering, 2024)

Nanocrystal-based thermoelectric SnTe-NaSbSe2 alloys with strengthened band convergence and reduced thermal conductivity - Bingfei Nan; Cheng Chang; Zhihao Li; Nilotpal Kapuria; Xu Han; Mengyao Li; Hongchao Wang; Kevin M. Ryan; Jordi Arbiol; Andreu Cabot (Chemical Engineering Journal, 2024)

Oral health effect of an oral rinse containing cetylpyridinium chloride: a randomized clinical trial - Md. Habibur Rahman; Jayson M. Antonio; Yun-Seon Lee; Ailyn Fadriquela; Soo-Min Kim; Sun-Young Han; Yeonkyung Lee; Jaeeun You; Cheol-Su Kim; Kyu-Jae Lee (Molecular & Cellular Toxicology, 2024)

Plant diversity decreases greenhouse gas emissions by increasing soil and plant carbon storage in terrestrial ecosystems - Pengfei Dang; Miaomiao Zhang; Xinli Chen; Michel Loreau; J. Emmett Duffy; Xin'e Li; Shuyue Wen; Xiaoqing Han; Lechen Liao; Tiantian Huang; Chenxi Wan; Xiaoliang Qin; et al. (Ecology Letters, 2024)
The decline in global plant diversity has raised concerns about its implications for carbon fixation and global greenhouse gas emissions (GGE), including carbon dioxide (CO 2 ), nitrous oxide (N 2 O) and methane (CH 4 ). Therefore, we conducted a comprehensive meta‐analysis of 2103 paired observations, examining GGE, soil organic carbon (SOC) and plant carbon in plant mixtures and monocultures. Our findings indicate that plant mixtures decrease soil N 2 O emissions by 21.4% compared to monocultures. No significant differences occurred between mixtures and monocultures for soil CO 2 emissions, CH 4 emissions or CH 4 uptake. Plant mixtures exhibit higher SOC and plant carbon storage than monocultures. After 10 years of vegetation development, a 40% reduction in species richness decreases SOC content and plant carbon storage by 12.3% and 58.7% respectively. These findings offer insights into the intricate connections between plant diversity, soil and plant carbon storage and GGE—a critical but previously unexamined aspect of biodiversity–ecosystem functioning.

Edible pentacyclic triterpenes: A review of their sources, bioactivities, bioavailability, self-assembly behavior, and emerging applications as functional delivery vehicles - Shiqi Liu; Han Liu; Lulu Zhang; Chao Ma; A. M. Abd El-Aty (Critical Reviews in Food Science and Nutrition, 2024)

Oxygen supersaturation adds resistance to a cnidarian: Symbiodiniaceae holobiont under moderate warming in experimental settings - Silvia Arossa; Shannon G. Klein; Elisa Garuglieri; Alexandra Steckbauer; Anieka J. Parry; Jacqueline V. Alva Garcia; Taiba Alamoudi; Xinyuan Yang; Shiou-Han Hung; Octavio R. Salazar; Ramona Marasco; Marco Fusi; et al. (Frontiers in Marine Science, 2024)
Ocean warming reduces O 2 solubility and increases organismal O 2 demand, endangering marine life. Coastal ecosystems, however, experience O 2 supersaturation during peak daytime temperatures due to metabolic cycles. Recent discoveries show that this environmental supersaturation can reduce the vulnerability of tropical species to warming by satisfying their oxygen requirements. To test whether this also occurs within the cnidarian holobiont, we elevated internal O 2 in Cassiopea andromeda at nighttime (i.e. holobiont respiration prevails on Symbiodniaceae O 2 production) relying on bell pulsation for ventilation, then experimentally subjected them to thermal stress (+1°C day -1 ). Though ecologically unrealistic, this approach verified our hypothesis and eliminated confounding factors. Holobionts were exposed to either constant levels of 100% air saturation (100AS) or nighttime supersaturation (NSS; where 100% air saturation transitioned to O 2 supersaturation at nighttime). At sublethal temperatures, supersaturation mitigated reductions in holobiont size of ~ 10.37% (-33.418% ± 0.345 under 100AS vs -23.039% ± 0.687 under NSS). Supersaturation alleviated chlorophyll- a loss by 42.73% until 34°C, when counteraction of this process could not be sustained due to excessive thermal stress. Supersaturation also enriched potentially beneficial bacterial taxa of the microbiome and selected a more consistent bacterial community. Although modest, the detected effects show that a O 2 surplus increased the resistance of the holobionts to thermal stress.

A field trial for remediation of multi-metal contaminated soils using the combination of fly ash stabilization and Zanthoxylum bungeanum- Lolium perenne intercropping system - Han Zhang; Xiaoyong Lv; Zhaowen Yang; Qian Li; Ping Wang; Shuqiang Zhang; Yaqiong Xu; Xuejia Wang; Esmat F. Ali; Peter S. Hooda; Sang Soo Lee; Ronghua Li; et al. (Journal of Environmental Management, 2024)

Early Triassic high-K granitoids and enclaves of the Daheba pluton, West Qinling (China): Implications for relative contributions of crust and mantle - Feng-Hui Zou; M. Santosh; Chang-Qian Ma; Cai-Lai Wu; Jian-Ping Zheng; Fa-Bin Pan; Han-Ming Gu; Li-Huan Deng (Journal of Asian Earth Sciences, 2024)

Sustainability information, taste perception and willingness to pay: The case of bird-friendly coffee - Klaus G. Grunert; Han-Seok Seo; Di Fang; Victoria J. Hogan; Rodolfo M. Nayga Jr. (Food Quality and Preference, 2024)

Needle and bud scale development in Picea abies - Carol L. Wenzel; Anny Y. Xia; Rebecca Saunders; Han Han Ly; Anson Mo; David M. Holloway (Trees, 2024)

Soleus H-reflex amplitude modulation during walking remains physiological during transspinal stimulation in humans - Abdullah M. Sayed Ahmad; Meghan Raphael; Jessy Feng Han; Yoseph Ahmed; Mohamed Moustafa; Shammah K. Solomon; Andreas Skiadopoulos; Maria Knikou (Experimental Brain Research, 2024)

Corrigendum to “Variations of oxidative potential of PM2.5 in a medium-sized residential city in South Korea measured using three different chemical assays” [920 (2024) 171053] - Pyung-Rae Kim; Sung-Won Park; Young-Ji Han; Myong-Hwa Lee; Thomas M. Holsen; Cheol-Heon Jeong; Greg Evans (Science of The Total Environment, 2024)

Exploring key factors affecting the ultimate compression capacity of Unbonded Steel-mesh-reinforced Rubber Bearings - Han Li; M. Shahria Alam (Engineering Structures, 2024)

Engineering pore limiting diameter of metal–organic frameworks for benchmark separation of mono- and di-branched hexane isomers - Jingyi Zhou; Xiao Han; Tian Ke; Jasper M. van Baten; Zongbi Bao; Zhiguo Zhang; Rajamani Krishna; Qilong Ren; Qiwei Yang (Chemical Engineering Journal, 2024)

Piezocatalytic property of PVDF/Graphene self-assembling piezoelectric membrane for environmental remediation - Tsung-Han Huang; Franz Kenneth C. Espino; Xin-Yuan Tian; Januar Widakdo; Hannah Faye M. Austria; Owen Setiawan; Wei-Song Hung; Kristopher Ray S. Pamintuan; Rhoda B. Leron; Ching-Yuan Chang; Alvin R. Caparanga; Kueir-Rarn Lee; et al. (Chemical Engineering Journal, 2024)

Efficiency of aqueous oleosome extraction from capsicum seeds compared to classical oil extraction - Mingzhao Han; Stefan ten Voorde; Xin Wen; Yuanying Ni; Remko M. Boom; Constantinos V. Nikiforidis (Bioresource Technology, 2024)

Effects of tillage regime on soil aggregate-associated carbon, enzyme activity, and microbial community structure in a semiarid agroecosystem - Chenglong Han; Weidi Zhou; Yanjie Gu; Junqiang Wang; Yanfang Zhou; Yunyin Xue; Zhiguo Shi; Kadambot H. M. Siddique (Plant and Soil, 2024)

Assessing the Performance of a Dynamical Downscaling Simulation Driven by a Bias-Corrected CMIP6 Dataset for Asian Climate - Zhongfeng Xu; Ying Han; Meng-Zhuo Zhang; Chi-Yung Tam; Zong-Liang Yang; Ahmed M. El Kenawy; Congbin Fu (Advances in Atmospheric Sciences, 2024)

Comammox and unknown ammonia oxidizers contribute to nitrite accumulation in an integrated A-B stage process that incorporates side-stream EBPR (S2EBPR) - Yuan Yan; Jangho Lee; IL Han; Zijian Wang; Guangyu Li; Kester McCullough; Stephanie Klaus; Da Kang; Dongqi Wang; Anand Patel; Jim McQuarrie; Beverley M. Stinson; et al. (Water Research, 2024)

Variations of oxidative potential of PM2.5 in a medium-sized residential city in South Korea measured using three different chemical assays - Pyung-Rae Kim; Sung-Won Park; Young-Ji Han; Myong-Hwa Lee; Thomas M. Holsen; Cheol-Heon Jeong; Greg Evans (Science of The Total Environment, 2024)

Microbial contribution estimated by clumped isotopologues (13CH3D and 12CH2D2) characteristics in a CO2 enhanced coal bed methane reservoir - Xinchu Wang; Biying Chen; Guannan Dong; Naizhong Zhang; Weiyi Liu; Jiaxu Han; Cong-Qiang Liu; Si-Liang Li; John M. Eiler; Sheng Xu (Science of The Total Environment, 2024)

Spontaneous rupture of the right aortic sinus resulting in a sterile aorto-atrial fistula in a pet rabbit (Oryctolagus cuniculus) - L. Cheung; B.A. Scansen; R. Baden; C.Q. Sloan; M. Garcia; S. Han; M.J. Sadar (Journal of Veterinary Cardiology, 2024)

Evaluating the future total water storage change and hydrological drought under climate change over lake basins, East Africa - Ayalkibet M. Seka; Huadong Guo; Jiahua Zhang; Jiaqi Han; Eyale Bayable; Gebiaw T. Ayele; Habtamu T. Workneh; Olfa T. Bayouli; Fabien Muhirwa; Kidane W. Reda (Journal of Cleaner Production, 2024)

Does more information mean better choices? A study on calorie display and consumer behavior in restaurants - Dae Hee Chung; Doo Bong Han; Rodolfo M. Nayga Jr.; Sang Hyeon Lee (Food Quality and Preference, 2024)

A novel Zr-P-modified nanomagnetic herbal biochar immobilized Cd and Pb in water and soil and enhanced the relative abundance of metal-resistant bacteria: Biogeochemical and spectroscopic investigations to identify the governing factors and potential mechanisms - Yueru Fang; Ping Wang; Lan Zhang; Han Zhang; Ran Xiao; Yuan Luo; Kuok Ho Daniel Tang; Ronghua Li; Hamada Abdelrahman; Zengqiang Zhang; Jörg Rinklebe; Sang Soo Lee; et al. (Chemical Engineering Journal, 2024)

A quantitative analysis of latitudinal variation of ionospheric total electron content and comparison with IRI-2020 over China - Yuyan Yang; Libo Liu; Xiukuan Zhao; Tingwei Han; M. Arslan Tariq; Yiding Chen; Hui Zhang; Huijun Le; Ruilong Zhang; Wenbo Li; Wenjie Sun; Guozhu Li (Advances in Space Research, 2024)

Geochemical behavior of C, N, and S in sediments of Hangzhou Bay, Southeastern China: implications for the study of paleoclimate and sea-level changes - Qin Gao; Alexander M. Piotrowski; Zilong Li; Pei Sun Loh; Cuicui Han; Zixuan Wang; Shihang Yang; Zengqing Guo; Dongqin Huang; Yanting Chen (Frontiers in Marine Science, 2024)
The correlation between the amount of organic carbon (OC) and sulfur (S) in sediments has been widely used as a paleosalinity indicator to distinguish between marine and freshwater environments. However, whether the ratio of total OC to total S (TOC/TS) can be used to identify unsteady or dynamic marine environments across sedimentary strata is still contended. An HZW1907 sediment core of 80 m in length was successfully collected in the middle of Hangzhou Bay (HZB), serving as one of the few boreholes that are crucial for the study of geologic and geo-environment changes in the coastal regions of eastern China since the Last Glacial Maximum (LGM). Total OC (TOC), stable carbon isotope, and TS of 82 subsamples from the HZW1907 core were analyzed to reconstruct the history of the shallow water biological pump and sulfur preservation record in the bay since the Late Pleistocene. Our results indicate that the samples had low concentrations of TOC (0.21%) and total nitrogen (TN) (0.02%), high mass ratio of TOC/TN (10.8), low δ 13 C (−24.9‰), low TS content (0.06%), and a high ratio of TOC/TS (9.1) from 33.6 ka BP to 12.3 ka BP, implying that freshwater organic matter (OM), algae, and C3 plant fragments were the main sources of OM in a relatively cold environment. The abundances of TOC, TN, and TS increased to 0.56%, 0.07%, and 0.4%, respectively, while δ 13 C (−23.9‰) increased and TOC/TS (2.7) decreased in the Holocene sediments, suggesting that seawater began to influence the composition of the sediments of HZB. Climate warming, which is likely to have impacted the results, was experienced from 12.3 ka BP. An OC isotope mixing model indicated that since the Mid-late Holocene, more than 70% of riverine OM accounted for the total OM. The TOC/TS ratio was identified as an effective indicator of seawater intrusion, with C/S ratios of 1–6 being considered to indicate a “sea–land transitional zone” sedimentary environment, a C/S >6 indicating freshwater, and a C/S<1 indicating normal marine facies. These findings provide crucial evidence for using TOC/TS to distinguish freshwater from marine environments and enhance our understanding of past climate changes. Therefore, these geochemical indicators can be used in conjunction with other sedimentary records to obtain accurate results about sedimentary evolution.

Side-Stream Enhanced Biological Phosphorus Removal (S2EBPR) enables effective phosphorus removal in a pilot-scale A-B stage shortcut nitrogen removal system for mainstream municipal wastewater treatment - Dongqi Wang; Il Han; Kester McCullough; Stephanie Klaus; Jangho Lee; Varun Srinivasan; Guangyu Li; Zijian Leo Wang; Charles B. Bott; Jim McQuarrie; Beverley M. Stinson; Christine deBarbadillo; et al. (Water Research, 2024)

RETRACTED: Spatial congruency or discrepancy? Exploring the spatiotemporal dynamics of built-up expansion patterns and flood risk - Mahmoud Mabrouk; Haoying Han; Karim I. Abdrabo; Mahran Gamal N. Mahran; Salma Antar A. AbouKorin; Sarah Nasrallah; Guoqiang Shen; Chao Fan; Ahmed Yousry; Hisham M. Hafez (Science of The Total Environment, 2024)

Reaction pathways and Sb(III) minerals formation during the reduction of Sb(V) by Rhodoferax ferrireducens strain YZ-1 - Yidan Zhang; Maxim I. Boyanov; Edward J. O’Loughlin; Kenneth M. Kemner; Robert A. Sanford; Han-Suk Kim; Soo-Chan Park; Man Jae Kwon (Journal of Hazardous Materials, 2024)

Seasonal dynamics of gut microbiome: A study of multi-kingdom microbiota of earthworm gut in an urban park - Jiahua Hao; Liping Wang; Nonillon M. Aspe; Anne Charis Han; Mengya Chen; Meiyan Li; Sisi Zhang; Donghui Wu (Applied Soil Ecology, 2024)

How does Green education result in resource extraction and consumption sustainability? - Zunlan Xiao; Mary Josephine M. Duritan; Dongmei Han; Yi Zong (Resources Policy, 2024)

Failure analysis and flow dynamic modeling using a new slow-flow functionality: the 2022 Jiaokou (China) tailings dam breach - Chenxu Su; Martin Mergili; Nahyan M. Rana; Shuai Zhang; Cong Dai; Bijiao Wang; Yingyue Han (Landslides, 2024)

Genomic data reveal shift in geographic source of an illegally traded songbird - Meng Yue Wu; Han Wei Chong; Yen Yi Tan; Bryan T. M. Lim; Anna M.S. Wong; Rachel Rui Ying Oh; Jessica G.H. Lee; Elize Y.X. Ng; Frank E. Rheindt (Conservation Genetics, 2024)

Early-Life Social Determinants of SCA6 Age at Onset, Severity, and Progression - Tiffany X. Chen; Hannah L. Casey; Chi-Ying R. Lin; Theresa A. Boyle; Jeremy D. Schmahmann; Gilbert J. L’Italien; Sheng-Han Kuo; Christopher M. Gomez (The Cerebellum, 2024)
SCA6 patients with the same size CAG repeat allele can vary significantly in age at onset (AAO) and clinical progression. The specific external factors affecting SCA6 have yet to be investigated. We assessed the effect of early life events on AAO, severity, and progression in SCA6 patients using a social determinant of health approach. We performed a survey of biological and social factors in SCA6 patients enrolled in the SCA6 Network at the University of Chicago. AAO of ataxia symptoms and patient-reported outcome measure (PROM) of ataxia were used as primary outcome measures. Least absolute shrinkage and selection operation (LASSO) regressions were used to identify which early life factors are predictive of SCA6 AAO, severity, and progression. Multiple linear regression models were then used to assess the degree to which these determinants influence SCA6 health outcomes. A total of 105 participants with genetically confirmed SCA6 completed the assessments. SCA6 participants with maternal difficulty during pregnancy, active participation in school sports, and/or longer CAG repeats were determined to have earlier AAO. We found a 13.44-year earlier AAO for those with maternal difficulty in pregnancy than those without ( p = 0.008) and a 12.31-year earlier AAO for those active in school sports than those who were not ( p < 0.001). Higher education attainment was associated with decreased SCA6 severity and slower progression. Early life biological and social factors can have a strong influence on the SCA6 disease course, indicating that non-genetic factors can contribute significantly to SCA6 health outcomes.

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

RETRACTED: Mitigation of the mobilization and accumulation of toxic metal(loid)s in ryegrass using sodium sulfide - Han Zhang; You Li; Ronghua Li; Weilong Wu; Hamada Abdelrahman; Jianxu Wang; Samir G. Al-Solaimani; Vasileios Antoniadis; Jörg Rinklebe; Sang Soo Lee; Sabry M. Shaheen; Zengqiang Zhang (Science of The Total Environment, 2024)

Fluorescence lifetime imaging microscopy as a tool to characterize spice powder variations for quality and authenticity purposes: A ginger case study - Qing Han; Sara W. Erasmus; Arjen Bader; Christos Fryganas; Christopher T. Elliott; Saskia M. van Ruth (Food Research International, 2024)

Multi-constellation GNSS interferometric reflectometry for tidal analysis: mitigations for K1 and K2 biases due to GPS geometrical errors - Dongju Peng; Yunung Nina Lin; Jui-Chi Lee; Hsuan-Han Su; Emma M. Hill (Journal of Geodesy, 2024)
It has been observed that when using sea levels derived from GPS (Global Positioning System) signal-to-noise ratio (SNR) data to perform tidal analysis, the luni-solar semidiurnal (K2) and the luni-solar diurnal (K1) constituents are biased due to geometrical errors in the reflection data, which result from their periods coinciding with the GPS orbital period and revisit period. In this work, we use 18 months of GNSS SNR data from multiple frequencies and multiple constellations at three sites to further investigate the biases and how to mitigate them. We first estimate sea levels using SNR data from the GPS, GLONASS, and Galileo signals, both individually and by combination. Secondly, we conduct tidal harmonic analysis using these sea-level estimates. By comparing the eight major tidal constituents estimated from SNR data with those estimated from the co-located tide-gauge records, we find that the biases in the K1 and K2 amplitudes from GPS S1C, S2X and S5X SNR data can reach 5 cm, and they can be mitigated by supplementing GLONASS- and Galileo-based sea-level estimates. With a proper combination of sea-level estimates from GPS, GLONASS, and Galileo, SNR-based tidal constituents can reach agreement at the millimeter level with those from tide gauges.

A bibliometric analysis of the toxicity research of carbon nanomaterials - M. Han; Y. Lei; F. X. Yang; H. F. Sun (International Journal of Environmental Science and Technology, 2024)

Comparison of PM2.5 components and secondary formation during the heavily polluted period of two megacities in China - Z. Ran; X. Wang; X. Yin; Y. Liu; M. Han; Y. Cheng; J. Han; T. Jin (International Journal of Environmental Science and Technology, 2024)

Spatio-temporal multi-level attention crop mapping method using time-series SAR imagery - Zhu Han; Ce Zhang; Lianru Gao; Zhiqiang Zeng; Bing Zhang; Peter M. Atkinson (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Antimicrobial, antioxidant, α-amylase and α-glucosidase inhibitory activities of a chemically characterized essential oil from Lavandula angustifolia Mill.,: in vitro and in silico investigations - Mohamed Jeddi; Naoufal El Hachlafi; Mohamed El Fadili; Nesrine Benkhaira; Samiah Hamad Al-Mijalli; Fahd Kandsi; Emad M. Abdallah; Zineb Benziane Ouaritini; Abdelhakim Bouyahya; Learn-Han Lee; Gokhan Zengin; Hanae Naceiri Mrabti; et al. (Biochemical Systematics and Ecology, 2023)

Biochar-derived dissolved organic matter (BDOM) and its influence on soil microbial community composition, function, and activity: A review - Muhammad Azeem; Tian-Ran Sun; Parimala Gnana Soundari Arockiam Jeyasundar; Rui-Xia Han; Hui Li; Hamada Abdelrahman; Sabry M. Shaheen; Yong-Guan Zhu; Gang Li (Critical Reviews in Environmental Science and Technology, 2023)

Graphene-based biomimetic array film for simultaneous fog water harvesting and wind power generation - Tsung Han Huang; Mu-Jie Shih; Yi-Yun Chen; Hannah Faye M. Austria; Owen Setiawan; Chunrui Wu; Xiaolong Lu; Lin Zhang; Wei-Song Hung (Chemical Engineering Journal, 2023)

Exploring perovskite oxide for advancing salt-resistant photothermal membranes and reliable thermoelectric generators - Naila Arshad; Muhammad Sultan Irshad; Muneerah Alomar; Jinming Guo; M. Sohail Asghar; Naveed Mushtaq; M.A.K. Yousaf; Uzma Ghazanfar; Matiullah Shah; Xianbao Wang; Yabin Hao; Lien Thi Do; et al. (Chemical Engineering Journal, 2023)

Interaction of exopolysaccharide with clay minerals and their effects on U(VI) adsorption - Huimin Zhang; Steve Larson; John Ballard; Jing Nie; Qiqi Zhang; Joseph A. Kazery; Shaloam Dasari; Nihar Pradhan; Qilin Dai; Olanrewaju M. Olafuyi; Xianchun Zhu; Youhua Ma; et al. (Journal of Soils and Sediments, 2023)

Effects of extracellular vesicles derived from steroids-primed oviductal epithelial cells on porcine in vitro embryonic development - Seonggyu Bang; Ahmad Yar Qamar; Xun Fang; Heyyoung Kim; Ayeong Han; Heejae Kang; Dabin Cha; Joohyun Shim; Jun-Hyeong Kim; Kimyung Choi; Sung Ho Yun; Hayoung Lee; et al. (Theriogenology, 2023)

Performance of parallel double pipelines under non-uniform seismic excitation - Junyan Han; Xiaoqiang Wang; Huiquan Miao; Benwei Hou; M. Hesham El Naggar; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2023)

High-resolution conodont unitary association zonations (UAZs) across the Induan-Olenekian boundary (Lower Triassic): A global correlation - Zhengyi Lyu; Charles M. Henderson; Zhong-Qiang Chen; Jinnan Tong; Laishi Zhao; Chen Han; Shunling Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

CHD7 variants associated with hearing loss and enlargement of the vestibular aqueduct - Isabelle Roux; Cristina Fenollar-Ferrer; Hyun Jae Lee; Parna Chattaraj; Ivan A. Lopez; Kyungreem Han; Keiji Honda; Carmen C. Brewer; John A. Butman; Robert J. Morell; Donna M. Martin; Andrew J. Griffith (Human Genetics, 2023)
Enlargement of the endolymphatic sac, duct, and vestibular aqueduct (EVA) is the most common inner ear malformation identified in patients with sensorineural hearing loss. EVA is associated with pathogenic variants in SLC26A4. However, in European–Caucasian populations, about 50% of patients with EVA carry no pathogenic alleles of SLC26A4 . We tested for the presence of variants in CHD7 , a gene known to be associated with CHARGE syndrome, Kallmann syndrome, and hypogonadotropic hypogonadism, in a cohort of 34 families with EVA subjects without pathogenic alleles of SLC26A4 . In two families, NM_017780.4: c.3553A > G [p.(Met1185Val)] and c.5390G > C [p.(Gly1797Ala)] were detected as monoallelic CHD7 variants in patients with EVA. At least one subject from each family had additional signs or potential signs of CHARGE syndrome but did not meet diagnostic criteria for CHARGE. In silico modeling of these two missense substitutions predicted detrimental effects upon CHD7 protein structure. Consistent with a role of CHD7 in this tissue, Chd7 transcript and protein were detected in all epithelial cells of the endolymphatic duct and sac of the developing mouse inner ear. These results suggest that some CHD7 variants can cause nonsyndromic hearing loss and EVA. CHD7 should be included in DNA sequence analyses to detect pathogenic variants in EVA patients. Chd7 expression and mutant phenotype data in mice suggest that CHD7 contributes to the formation or function of the endolymphatic sac and duct.

Functional traits explain waterbirds' host status, subtype richness, and community‐level infection risk for avian influenza - Shenglai Yin; Ning Li; Wenjie Xu; Daniel J. Becker; Willem F. de Boer; Chi Xu; Taej Mundkur; Nicholas M. Fountain‐Jones; Chunlin Li; Guan‐zhu Han; Qiang Wu; Diann J. Prosser; et al. (Ecology Letters, 2023)
Species functional traits can influence pathogen transmission processes, and consequently affect species' host status, pathogen diversity, and community‐level infection risk. We here investigated, for 143 European waterbird species, effects of functional traits on host status and pathogen diversity (subtype richness) for avian influenza virus at species level. We then explored the association between functional diversity and HPAI H5Nx occurrence at the community level for 2016/17 and 2021/22 epidemics in Europe. We found that both host status and subtype richness were shaped by several traits, such as diet guild and dispersal ability, and that the community‐weighted means of these traits were also correlated with community‐level risk of H5Nx occurrence. Moreover, functional divergence was negatively associated with H5Nx occurrence, indicating that functional diversity can reduce infection risk. Our findings highlight the value of integrating trait‐based ecology into the framework of diversity–disease relationship, and provide new insights for HPAI prediction and prevention.

P19-07: 13-week repeated-dose oral toxicity study in rats treated with a mixture of Cirsium japonicum and Brassica oleracea extracts - W.-J. Im; M.-H. Yang; H. Park; J.-S. Han; J.-W. Cho; M.H. Yoo; Y.-B. Kim (Toxicology Letters, 2023)

Southern China can produce more high-quality rice with less N by green manuring - Songjuan Gao; Guopeng Zhou; Danna Chang; Hao Liang; Jun Nie; Yulin Liao; Yanhong Lu; Changxu Xu; Jia Liu; Ji Wu; Shang Han; Hui Wang; et al. (Resources, Conservation and Recycling, 2023)

Physical and numerical modeling of seismic soil-structure interaction of prefabricated subway station structure - Jinnan Chen; Chengshun Xu; Xiuli Du; Runbo Han; Hesham M. El Naggar (Engineering Structures, 2023)

Multifunctional composite membranes for interfacial solar steam and electricity generation - Yiting Wu; Jianqiushi Ma; Shuo Zang; Weiming Zhou; Zequn Wang; Minsu Han; Sameh M. Osman; Chong Wang; Yusuke Yamauchi; Jungmok You; Meng An; Liwei Wang; et al. (Chemical Engineering Journal, 2023)

Boosting the energy storage performance of aqueous NH4+ symmetric supercapacitor based on the nanostructured molybdenum disulfide nanosheets - Muhammad Sufyan Javed; Xiaofeng Zhang; Salamat Ali; Syed Shoaib Ahmad Shah; Awais Ahmad; Iftikhar Hussain; Shahid Hussain; Shaukat Khan; Mohamed Ouladsmane; Sayed M. Tag ElDin; Waqas Ul Arifeen; Weihua Han (Chemical Engineering Journal, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Colon-cancer liver metastasis is effectively targeted by recombinant methioninase (rMETase) in an orthotopic mouse model - Kentaro Miyake; Qinghong Han; Takashi Murakami; Tasuku Kiyuna; Kei Kawaguchi; Kentaro Igarashi; Thinzar M. Lwin; Masuyo Miyake; Jun Yamamoto; Michael Bouvet; Itaru Endo; Robert M. Hoffman (Tissue and Cell, 2023)

Interpreting the variation in particle size of ground spice by high-resolution visual and spectral imaging: A ginger case study - Qing Han; Joseph Peller; Sara W. Erasmus; Christopher T. Elliott; Saskia M. van Ruth (Food Research International, 2023)

Cadmium uptake and membrane transport in roots of hyperaccumulator Amaranthus hypochondriacus L. - Mengxuan Han; Habib Ullah; Huan Yang; Guo Yu; Shaohong You; Jie Liu; Baoliang Chen; Asfandyar Shahab; Vasileios Antoniadis; Sabry M. Shaheen; Jörg Rinklebe (Environmental Pollution, 2023)

The quest to develop automated systems for monitoring animal behavior - Janice M. Siegford; Juan P. Steibel; Junjie Han; Madonna Benjamin; Tami Brown-Brandl; Joao R.R. Dórea; Daniel Morris; Tomas Norton; Eric Psota; Guilherme J.M. Rosa (Applied Animal Behaviour Science, 2023)

Recent advances on humic acid removal from wastewater using adsorption process - Tamara Alomar; Hazim Qiblawey; Fares Almomani; Riyadh I. Al-Raoush; Dong Suk Han; Nasir M. Ahmad (Journal of Water Process Engineering, 2023)

Numerical analysis of buried pipelines response to bidirectional non-uniform seismic excitation - Zhike Guo; Junyan Han; M. Hesham El Naggar; Benwei Hou; Zilan Zhong; Xiuli Du (Computers and Geotechnics, 2023)

Reduction in productivity of soybean plants infested with Neohyadatothrips variabilis (Thysanoptera: Thripidae) with and without soybean vein necrosis virus - Doris M. Lagos-Kutz; Michelle L. Pawlowski; Jaeyeong Han; Steven J. Clough; Glen L. Hartman (Phytoparasitica, 2023)
Soybean thrips, Neohyadatothrips variabilis (Beach), a vector of Soybean Vein Necrosis Virus (SVNV), has been recognized as a widespread pest of soybean [ Glycine max (L.) Merr.] in USA and Canada. Several experiments investigated the effect on soybean when infested with soybean thrips with and without SVNV. Experiment 1 compared soybean infested at V1 and V5 growth stages (GS) with soybean thrips without SVNV and noninfested plants. For plants infested at GS V1, plant height, number of seeds, and seed weights were reduced by 50, 80, and 75%, respectively. When plants were infested at GSs V1 and V5, the counts of soybean thrips peaked at 1,803 and 4,214 per plant 4 weeks after infestation (WAI), respectively. Experiment 2 used SVNV-infected soybean thrips and compared soybean infested versus control at GS V1 and V5. For plants infested at GS V1, plant height was reduced 77.8%, and plants died before setting pods. For plants infested at GS V5, height, number of seeds, and seed weights were reduced 56, 78, and 92%, respectively. When plants were infested at GSs V1 and V5, the counts of soybean thrips peaked at 282 and 883 per plant 2 WAI, respectively. Experiment 3, five soybean genotypes were infested with SVNV-infected thrips at GS V1. Number and weight of seeds per plant were higher and with lower visual disease ratings (progressive chlorosis, necrosis and rugosity) for the more resistant genotypes Merschman Kennedy and plant introduction (PI) 171451 than for the more susceptible genotypes: soybean breeding line LD12-12734a ( Rag1/2 ), cv Williamsfield Illini 3509N, and PI 417136.

Lead change of a HIF-2α antagonist guided by multiparameter optimization and utilization of an Olp→π*Ar interaction - Paul M. Wehn; Song Yang; Jonas A. Grina; James P. Rizzi; Stephen T. Schlachter; Bin Wang; Rui Xu; Hanbiao Yang; Xinlin Du; Guangzhou Han; Keshi Wang; Robert M. Czerwinski; et al. (Medicinal Chemistry Research, 2023)

SARS-CoV-2 3CL-protease inhibitors derived from ML300: investigation of P1 and replacements of the 1,2,3-benzotriazole - Alice Hooper; Jonathan D. Macdonald; Brenna Reilly; Joshua Maw; Aidan P. Wirrick; Sang Hoon Han; A. Abigail Lindsey; Emma G. Rico; Todd Romigh; Christopher M. Goins; Nancy S. Wang; Shaun R. Stauffer (Medicinal Chemistry Research, 2023)

Effect of functionalized nanodiamonds and surfactants mediation on the nanofiltration performance of polyamide thin-film nanocomposite membranes - T.M. Subrahmanya; Jing-Yang Lin; Januar Widakdo; Hannah Faye M. Austria; Owen-Setiawan; Yu-Hsuan Chiao; Tsung-Han Huang; Wei-Song Hung; Hideto Matsuyama; Kueir-Rarn Lee; Juin-Yih Lai (Desalination, 2023)

Soil grit influences the effects of earthworms (Lumbricus terrestris) on seed damage - Shu Han Gan; Michael J. McTavish; Robert S. Bourchier; Sandy M. Smith (Applied Soil Ecology, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Transfer learning in a biomaterial fibrosis model identifies in vivo senescence heterogeneity and contributions to vascularization and matrix production across species and diverse pathologies - Christopher Cherry; James I. Andorko; Kavita Krishnan; Joscelyn C. Mejías; Helen Hieu Nguyen; Katlin B. Stivers; Elise F. Gray-Gaillard; Anna Ruta; Jin Han; Naomi Hamada; Masakazu Hamada; Ines Sturmlechner; et al. (GeroScience, 2023)

Evaluating ecotoxicological assays for comprehensive risk assessment of toxic metals present in industrial wastewaters in the Republic of Korea - Jihae Park; Kisik Shin; Hojun Lee; Soyeon Choi; Geonhee Kim; Stephen Depuydt; Jonas De Saeger; Philippe M. Heynderickx; Di Wu; Jana Asselman; Colin Janssen; Taejun Han (Science of The Total Environment, 2023)

H2 impact on combustion kinetics, soot formation, and NOx emission of hydrocarbon fuel flames - M. Zuhaib Akram; Fanhua Ma; Muhammad Aziz; Yangbo Deng; Han Wu (Fuel, 2023)

Multi-sectoral analysis of smarter urban nitrogen metabolism: A case study of Suzhou, China - M Bruce Beck; Chen Chen; Rodrigo Villarroel Walker; Zongguo Wen; Jiangxue Han (Ecological Modelling, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Hydrology and water quality shape macroinvertebrate patterns and facilitate non-native species dispersals in an inter-basin water transfer system - Xiao Qu; Julian D. Olden; Wentong Xia; Han Liu; Zhicai Xie; Robert M. Hughes; Yushun Chen (Journal of Environmental Management, 2023)

The relationship between the use of electronic nicotine delivery systems (ENDS) and effects on pulmonary immune responses—a literature review - Seok Gyu Han; Fenna CM. Sillé; Jana N. Mihalic; Ana M. Rule (Environmental Research, 2023)

Polystyrene nanoplastics affect transcriptomic and epigenomic signatures of human fibroblasts and derived induced pluripotent stem cells: Implications for human health - Miodrag Stojkovic; Francisco Manuel Ortuño Guzmán; Dongjun Han; Petra Stojkovic; Joaquin Dopazo; Konstantina M. Stankovic (Environmental Pollution, 2023)

Evaluation of biogenic emissions from three different vegetation distributions in South Korea - Jinhyeok Yu; Kyung M. Han; Chul H. Song; Kyunghwa Lee; Sojin Lee; Younha Kim; Jung-Hun Woo; Saewung Kim; Armin Wisthaler (Atmospheric Environment, 2023)

Towards multiomic analysis of oral mucosal pathologies - Jakob Einhaus; Xiaoyuan Han; Dorien Feyaerts; John Sunwoo; Brice Gaudilliere; Somayeh H. Ahmad; Nima Aghaeepour; Karl Bruckman; David Ojcius; Christian M. Schürch; Dyani K. Gaudilliere (Seminars in Immunopathology, 2023)
Oral mucosal pathologies comprise an array of diseases with worldwide prevalence and medical relevance. Affecting a confined space with crucial physiological and social functions, oral pathologies can be mutilating and drastically reduce quality of life. Despite their relevance, treatment for these diseases is often far from curative and remains vastly understudied. While multiple factors are involved in the pathogenesis of oral mucosal pathologies, the host’s immune system plays a major role in the development, maintenance, and resolution of these diseases. Consequently, a precise understanding of immunological mechanisms implicated in oral mucosal pathologies is critical (1) to identify accurate, mechanistic biomarkers of clinical outcomes; (2) to develop targeted immunotherapeutic strategies; and (3) to individualize prevention and treatment approaches. Here, we review key elements of the immune system’s role in oral mucosal pathologies that hold promise to overcome limitations in current diagnostic and therapeutic approaches. We emphasize recent and ongoing multiomic and single-cell approaches that enable an integrative view of these pathophysiological processes and thereby provide unifying and clinically relevant biological signatures.

Optical bulk-boundary dichotomy in a quantum spin Hall insulator - Junfeng Han; Pengcheng Mao; Hailong Chen; Jia-Xin Yin; Maoyuan Wang; Dongyun Chen; Yongkai Li; Jingchuan Zheng; Xu Zhang; Dashuai Ma; Qiong Ma; Zhi-Ming Yu; et al. (Science Bulletin, 2023)

Influence of catalase encapsulation on Cobalt@Nanoporous carbon with multiwall shell for supercapacitor and polyurethane synthesis using carbon dioxide - Rahul Patil; Nitish Kumar; Sudip Bhattacharjee; Hsi-Yen Wu; Po-Chun Han; Babasaheb M. Matsagar; Kevin C.W. Wu; Rahul R. Salunkhe; Asim Bhaumik; Saikat Dutta (Chemical Engineering Journal, 2023)

Within-species plant phylogeny drives ectomycorrhizal fungal community composition in tree roots along a timberline - Teng Yang; Luyao Song; Han-Yang Lin; Ke Dong; Xiao Fu; Gui-Feng Gao; Jonathan M. Adams; Haiyan Chu (Soil Biology and Biochemistry, 2023)

Impacts of land uses on spatio-temporal variations of seasonal water quality in a regulated river basin, Huai River, China - Lingqing Wang; Xiaoxiao Han; Yongyong Zhang; Qian Zhang; Xiaoming Wan; Tao Liang; Hocheol Song; Nanthi Bolan; Sabry M. Shaheen; John R. White; Jörg Rinklebe (Science of The Total Environment, 2023)

Higher blood selenium level is associated with lower risk of hyperhomocysteinemia in the elderly - Ting Wang; Liqin Su; Xi Chen; Sisi Wang; Xu Han; Yibin Cheng; Shaobin Lin; Liang Ding; Jingyi Liu; Chen Chen; Frederick W. Unverzagt; Ann M. Hake; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Halogen (F, Cl, Br, and I) concentrations of the upper continental crust through time as recorded in ancient glacial diamictite composites - Peng-Yuan Han; Roberta L. Rudnick; Tao He; Michael A.W. Marks; Shui-Jiong Wang; Richard M. Gaschnig; Zhao-Chu Hu (Geochimica et Cosmochimica Acta, 2023)

Lactic acid bacteria promoted soil quality and enhanced phytoextraction of Cd and Zn by mustard: A trial for bioengineering of toxic metal contaminated mining soils - Shuqiang Zhang; Yiman Li; Ping Wang; Han Zhang; Esmat F. Ali; Ronghua Li; Sabry M. Shaheen; Zengqiang Zhang (Environmental Research, 2023)

Rapid preparation of nickel fluoride motif via solution-free plasma route for high-energy aqueous hybrid supercapacitor - Nilesh R. Chodankar; Indrajit V. Bagal; Swati J. Patil; Seung-Kyu Hwang; Pragati A. Shinde; Amar M. Patil; Smita V. Karekar; Amal Al Ghaferi; Wenli Zhang; Sang-Wan Ryu; Yun Suk Huh; Young Kyu Han (Chemical Engineering Journal, 2023)

Correction to: Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2023)

Gastrointestinal consequences of lipopolysaccharide-induced lung inflammation - Rachel M. McQuade; Methma Bandara; Shanti Diwakarla; Lauren Sahakian; Myat Noe Han; Maryam Al Thaalibi; Madeleine R. Di Natale; Marsha Tan; Kiera H. Harwood; Elena K. Schneider-Futschik; Andrew Jarnicki (Inflammation Research, 2023)
Background Respiratory inflammation is the body’s response to lung infection, trauma or hypersensitivity and is often accompanied by comorbidities, including gastrointestinal (GI) symptoms. Why respiratory inflammation is accompanied by GI dysfunction remains unclear. Here, we investigate the effect of lipopolysaccharide (LPS)-induced lung inflammation on intestinal barrier integrity, tight-junctions, enteric neurons and inflammatory marker expression. Methods Female C57bl/6 mice (6–8 weeks) were intratracheally administered LPS (5 µg) or sterile saline, and assessed after either 24 or 72 h. Total and differential cell counts in bronchoalveolar lavage fluid (BALF) were used to evaluate lung inflammation. Intestinal barrier integrity was assessed via cross sectional immunohistochemistry of tight junction markers claudin-1, claudin-4 and EpCAM. Changes in the enteric nervous system (ENS) and inflammation in the intestine were quantified immunohistochemically using neuronal markers Hu + and nNOS, glial markers GFAP and S100β and pan leukocyte marker CD45. Results Intratracheal LPS significantly increased the number of neutrophils in BALF at 24 and 72 h. These changes were associated with an increase in CD45 + cells in the ileal mucosa at 24 and 72 h, increased goblet cell expression at 24 h, and increased expression of EpCAM at 72 h. LPS had no effect on the expression of GFAP, S100β, nor the number of Hu + neurons or proportion of nNOS neurons in the myenteric plexus. Conclusions Intratracheal LPS administration induces inflammation in the ileum that is associated with enhanced expression of EpCAM, decreased claudin-4 expression and increased goblet cell density, these changes may contribute to systemic inflammation that is known to accompany many inflammatory diseases of the lung.

Elastoplastic Modelling of Porous Limestones with Porosity Dependency - B. Han; Q. M. Gong; X. L. Du; Y. Gao; W. Q. Shen; S. Lin (Rock Mechanics and Rock Engineering, 2022)

The developmental journey of therapies targeting purine receptors: from basic science to clinical trials - Seunga Han; Haruna Suzuki-Kerr; Srdjan M. Vlajkovic; Peter R. Thorne (Purinergic Signalling, 2022)
Since the discovery of ATP as an extracellular signalling molecule in 1972, purinergic signalling, mediated by extracellular purines and pyrimidines has been identified in virtually all mammalian tissues and is implicated in regulating fundamental cellular processes. In recent years, there has been an increasing focus on the pathophysiology and potential therapeutic interventions based on purinergic signalling. A vast range of compounds targeting purine receptors are in clinical development, and many more are in preclinical studies, which highlights the fast growth in this research field. As a tribute to Professor Geoffrey Burnstock’s legacy in purinergic signalling, we present here a brief review of compounds targeting purine receptors that are in different stages of clinical trials. The review highlights the 50-year journey from basic research on purinergic receptors to clinical applications of therapies targeting purine receptors.

Correlation notice on the electrochemical dealloying and antibacterial properties of gold–silver alloy nanoparticles - Javad B. M. Parambath; Islam M. Ahmady; Seema Panicker; Aebin Sin; Changseok Han; Ahmed A. Mohamed (BioMetals, 2022)

Probing the nature of soil organic matter - Zhe (Han) Weng; Johannes Lehmann; Lukas Van Zwieten; Stephen Joseph; Braulio S. Archanjo; Bruce Cowie; Lars Thomsen; Mark J. Tobin; Jitraporn Vongsvivut; Annaleise Klein; Casey L. Doolette; Helen Hou; et al. (Critical Reviews in Environmental Science and Technology, 2022)

Fossilized diatoms as indirect indicators of the origin of carbon stored in intertidal flats - El-Hacen M. El-Hacen; Ties Mens; Tjeerd J. Bouma; Theunis Piersma; Suzanne A.G. Leroy; Han Olff; Francesca Sangiorgi (Frontiers in Marine Science, 2022)
Coastal systems store enormous carbon quantities in their sediment, which originates from various autochthonous and allochthonous sources. Carbon fluxes in coastal ecosystems have a strong effect on the recipient food-webs and carbon emission offsets. Yet, the relative importance of autochthonous vs. allochthonous C inputs to coastal carbon budget is still challenging to identify. Here, we combine diatoms preserved in the sediment with geochemical analyses to identify the sources of carbon stored in Africa’s largest intertidal seagrass beds at Banc d’Arguin, Mauritania. The area lies between an active ocean upwelling and the ‘Sahara-dust hotspot’ systems. The extensive seagrass beds of the area are thus expected to receive C from these neighboring systems in addition to producing C in-situ . Three sediment cores (50 cm) were collected at three intertidal sites with different hydrodynamic regimes, and analyzed for diatom composition, total organic carbon (TOC), total nitrogen (TN), total phosphorus (TP), and carbon isotopic signatures (δ 13 C). Diatom taxa are grouped into three guilds: (1) benthic (epiphyte, epipelon, and epipsammon), (2) planktonic, and (3) freshwater. Benthic diatoms are considered to be autochthonous, while typical oceanic and freshwater diatoms are considered to be allochthonous. Benthic diatoms are the most diverse and abundant group, while allochthonous freshwater (i.e., dust imported) and typical upwelling (i.e., tidal imported) taxa ranked last in both abundance and species’ richness. Structure equation modelling shows that variation in the stored carbon is best explained by the total abundance of diatoms and guild composition. We conclude that the C stored in the intertidal seagrass beds of Banc d’Arguin is predominantly autochthonous. Our method provides an effective way to identify historical carbon sources in coastal systems.

Antimicrobial activity of quaternary ammonium salts: structure-activity relationship - Mallikarjuna N. Nadagouda; Pooja Vijayasarathy; Aebin Sin; Heeyeon Nam; Sanaullah Khan; Javad B. M. Parambath; Ahmed A. Mohamed; Changseok Han (Medicinal Chemistry Research, 2022)

Patient Perspectives on the Risk-Based NLST Outcomes Tool for Lung Cancer Screening - Megan C. Roberts; Elizabeth L. Seaman; William M. P. Klein; Rebecca A. Ferrer; Paul K.J. Han; Hormuzd A. Katki; Stephanie R. Land; Robert A. Liotta; Joel A. Nations; P. Gabriel Peterson (Journal of Cancer Education, 2022)

Sustained-release ketamine-loaded lipid-particulate system: in vivo assessment in mice - Weizhi Xu; Faheem Maqbool; Vinod Kumar; James R. Falconer; Cedric S. Cui; Trent M. Woodruff; Karin Borges; Andrew K. Whittaker; Maree T. Smith; Felicity Y. Han (Drug Delivery and Translational Research, 2022)

The proposed Anthropocene Epoch/Series is underpinned by an extensive array of mid‐20 th century stratigraphic event signals - Martin J. Head; Jan A. Zalasiewicz; Colin N. Waters; Simon D. Turner; Mark Williams; Anthony D. Barnosky; Will Steffen; Michael Wagreich; Peter K. Haff; Jaia Syvitski; Reinhold Leinfelder; Francine M. G. Mccarthy; et al. (Journal of Quaternary Science, 2022)
The extensive array of mid‐20 th century stratigraphic event signals associated with the ‘Great Acceleration’ enables precise and unambiguous recognition of the Anthropocene as an epoch/series within the Geological Time Scale. A mid‐20 th century inception is consistent with Earth System science analysis in which the Anthropocene term and concept arose, and would reflect the reality that our planet has sharply exited the range of natural variability characterizing the Holocene Epoch/Series, which the Anthropocene would therefore terminate. An alternative, recently proposed ‘geological event’ approach to the Anthropocene is primarily an interdisciplinary concept, encompassing historical and socio‐cultural processes and their global environmental impacts over a diachronous timeframe that extends back at least many millennia. Resembling more closely a geological episode than an event , it would decouple the Anthropocene from its chronostratigraphic delineation and association with an abrupt planetary perturbation; but separately defined and differently named it might be usefully complementary. We recommend a clear separation of epochs , events and episodes . An epoch is a formal subdivision of the Geological Time Scale, and its correlation may be assisted by one or more events ; an event is usually, and particularly in the Quaternary, a brief incident or perturbation with a sedimentary expression; and an episode is a longer, internally complex time interval that may include several events and even extend across several epochs.

Fine mapping and candidate gene analysis of gummy stem blight resistance in cucumber stem - Jianan Han; Shaoyun Dong; Yanxia Shi; Han Miao; Xiaoping Liu; Diane M. Beckles; Xingfang Gu; Shengping Zhang (Theoretical and Applied Genetics, 2022)

The S-Factor, a New Measure of Disease Severity in Spinocerebellar Ataxia: Findings and Implications - Louisa P. Selvadurai; Susan L. Perlman; George R. Wilmot; Sub H. Subramony; Christopher M. Gomez; Tetsuo Ashizawa; Henry L. Paulson; Chiadi U. Onyike; Liana S. Rosenthal; Haris I. Sair; Sheng-Han Kuo; Eva-Maria Ratai; et al. (The Cerebellum, 2022)

The qLTG1.1 candidate gene CsGAI regulates low temperature seed germination in cucumber - Caixia Li; Shaoyun Dong; Diane M. Beckles; Han Miao; Jiaqiang Sun; Xiaoping Liu; Weiping Wang; Shengping Zhang; Xingfang Gu (Theoretical and Applied Genetics, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Longitalea arenae gen. nov., sp. nov. and Longitalea luteola sp. nov., two new members of the family Chitinophagaceae isolated from desert soil - Shuai Li; Lei Dong; Jia-Rui Han; Guo-Yuan Shi; Chun-Yan Lu; Lu Xu; Wen-Hui Lian; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Wen-Jun Li (Archives of Microbiology, 2022)

Growth of non‐English‐language literature on biodiversity conservation - Shawan Chowdhury; Kristofer Gonzalez; M. Çisel Kemahlı Aytekin; Seung‐Yun Baek; Michał Bełcik; Sandro Bertolino; Sjoerd Duijns; Yuqing Han; Kerstin Jantke; Ryosuke Katayose; Mu‐Ming Lin; Elham Nourani; et al. (Conservation Biology, 2022)
English is widely recognized as the language of science, and English‐language publications (ELPs) are rapidly increasing. It is often assumed that the number of non‐ELPs is decreasing. This assumption contributes to the underuse of non‐ELPs in conservation science, practice, and policy, especially at the international level. However, the number of conservation articles published in different languages is poorly documented. Using local and international search systems, we searched for scientific articles on biodiversity conservation published from 1980 to 2018 in English and 15 non‐English languages. We compared the growth rate in publications across languages. In 12 of the 15 non‐English languages, published conservation articles significantly increased every year over the past 39 years, at a rate similar to English‐language articles. The other three languages showed contrasting results, depending on the search system. Since the 1990s, conservation science articles in most languages increased exponentially. The variation in the number of non‐English‐language articles identified among the search systems differed markedly (e.g., for simplified Chinese, 11,148 articles returned with local search system and 803 with Scopus). Google Scholar and local literature search systems returned the most articles for 11 and 4 non‐English languages, respectively. However, the proportion of peer‐reviewed conservation articles published in non‐English languages was highest in Scopus, followed by Web of Science and local search systems, and lowest in Google Scholar. About 20% of the sampled non‐English‐language articles provided no title or abstract in English; thus, in theory, they were undiscoverable with English keywords. Possible reasons for this include language barriers and the need to disseminate research in countries where English is not widely spoken. Given the known biases in statistical methods and study characteristics between English‐ and non‐English‐language studies, non‐English‐language articles will continue to play an important role in improving the understanding of biodiversity and its conservation.

Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2022)

Alterations in Functional and Structural Connectivity of Basal Ganglia Network in Patients with Obesity - Zongxin Tan; Yang Hu; Gang Ji; Guanya Li; Yueyan Ding; Wenchao Zhang; Jia Wang; Zhenzhen Jia; Lei Zhang; Hao Li; Karen M. von Deneen; Yu Han; et al. (Brain Topography, 2022)

A New Berberine Preparation Protects Pancreatic Islet Cells from Apoptosis Mediated by Inhibition of Phospholipase A2/p38 MAPK Pathway - X. J. Bi; Y. Q. Lv; X. H. Yang; Y. Ge; H. Han; J. S. Feng; M. Zhang; L. Chen; M. Z. Xu; F. Y. Guan (Bulletin of Experimental Biology and Medicine, 2022)

Structural variability in the bulk soil, rhizosphere, and root endophyte fungal communities of Themeda japonica plants under different grades of karst rocky desertification - Ming Tang; Jie Liu; Wenpeng Hou; Reed M. Stubbendieck; Han Xiong; Jie Jin; Jiyi Gong; Chen Cheng; Xiaoxin Tang; Yinglong Liu; Zhaofeng Li; Jianfeng Wang; et al. (Plant and Soil, 2022)

Truncation of the N-terminus of cardiac troponin I initiates adaptive remodeling of the myocardial proteosome via phosphorylation of mechano-sensitive signaling pathways - Chad M. Warren; Monika Halas; Paul H. Goldspink; Han-Zhong Feng; Anthony W. Herren; Beata M. Wolska; Pieter P. de Tombe; Jian-Ping Jin; R. John Solaro (Molecular and Cellular Biochemistry, 2022)

FDA Approaches in Monitoring Drug Quality, Forces Impacting the Drug Quality, and Recent Alternative Strategies to Assess Quality in the US Drug Supply - Philip J. Almeter; James T. Isaacs; Aaron N. Hunter; Bradley S. Henderson; Thomas Platt; Billie J. Mitchell; David Do; Alyssa B. Brainard; Joshua E. Brown; Rachael M. Stone; Bao-Han Nguyen; Matthew F. Warren; et al. (Journal of Pharmaceutical Innovation, 2022)

Insight into soil nitrogen and phosphorus availability and agricultural sustainability by plant growth-promoting rhizobacteria - Qingwei Zeng; Xiaolei Ding; Jiangchuan Wang; Xuejiao Han; Hafiz M. N. Iqbal; Muhammad Bilal (Environmental Science and Pollution Research, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Productivity of Leymus chinensis grassland is co-limited by water and nitrogen and resilient to climate change - Yujie Shi; Yunna Ao; Baixin Sun; Johannes M. H. Knops; Jinwei Zhang; Zhihan Guo; Xianming De; Jiayu Han; Yuheng Yang; Xiaoyu Jiang; Chunsheng Mu; Junfeng Wang (Plant and Soil, 2022)

A hypotonic gel-forming eye drop provides enhanced intraocular delivery of a kinase inhibitor with melanin-binding properties for sustained protection of retinal ganglion cells - Yoo Chun Kim; Henry T. Hsueh; Matthew D. Shin; Cynthia A. Berlinicke; Hyounkoo Han; Nicole M. Anders; Avelina Hemingway; Kirby T. Leo; Renee Ti Chou; HyeYoung Kwon; Matthew B. Appell; Usha Rai; et al. (Drug Delivery and Translational Research, 2022)

Synthesis and anticancer activity of novel hydrazone linkage-based aryl sulfonate derivatives as apoptosis inducers - Sevil Şenkardeş; M. İhsan Han; Merve Gürboğa; Özlem Bingöl Özakpinar; Ş. Güniz Küçükgüzel (Medicinal Chemistry Research, 2022)

Integrated pest management of Tuta absoluta: practical implementations across different world regions - Nicolas Desneux; Peng Han; Ramzi Mansour; Judit Arnó; Thierry Brévault; Mateus R. Campos; Anais Chailleux; Raul N. C. Guedes; Javad Karimi; Kouassi Arthur J. Konan; Anne-violette Lavoir; María G. Luna; et al. (Journal of Pest Science, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

The second wave of earthworm invasions in North America: biology, environmental impacts, management and control of invasive jumping worms - Chih-Han Chang; Marie L. C. Bartz; George Brown; Mac A. Callaham; Erin K. Cameron; Andrea Dávalos; Annise Dobson; Josef H. Görres; Bradley M. Herrick; Hiroshi Ikeda; Samuel W. James; Marie R. Johnston; et al. (Biological Invasions, 2021)

Molecular characterization of Toll-like receptor type-3 in mallard duck and its response to Newcastle disease virus infection - Wael K. Elfeil; Reham R. Abouelmaatti; Shaimaa Talat; Mohamed Fawzy; Mohamed Rady; Mohamed Diab; Saad Alkahtani; Hesham Sultan; Changjiang Sun; Liancheng Lei; Wenyu Han; Mahmoud Sedeik; et al. (Environmental Science and Pollution Research, 2021)

Fast grain-boundary ionic conduction in multiphase aggregates as revealed by electrical conductivity measurements - Kui Han; Xinzhuan Guo; Junfeng Zhang; Xuben Wang; Simon M. Clark (Contributions to Mineralogy and Petrology, 2021)

Eutrophication and Hypoxia in Tropical Negombo Lagoon, Sri Lanka - Hsueh-Han Hsieh; Ming-Hsiu Chuang; Yung-Yen Shih; W. Sanjaya Weerakkody; Wei-Jen Huang; Chin-Chang Hung; François L. L. Muller; R. R. M. K. P. Ranatunga; D. S. Wijethunga (Frontiers in Marine Science, 2021)
Hypoxic events are becoming frequent in some estuaries and coastal waters due to over-enrichment of anthropogenic nutrients, organic matter, and/or due to restricted water circulation. The coastal lagoons and estuaries of Sri Lanka are facing high population pressure and lacking sufficient infrastructure. Coastal lagoons may receive high anthropogenic inputs of natural or untreated nitrogen and phosphorus wastes, and consequently result in hypoxic conditions while sluggish circulation occurred. In this study, we examined the spatiotemporal variability of eutrophication and hypoxia in the Negombo Lagoon, one of the most productive and sensitive coastal ecosystems in Sri Lanka. Based on seasonal measurements of dissolved oxygen, nutrients, chlorophyll- a (Chl- a ), particulate and dissolved organic carbon (POC and DOC), we concluded that eutrophication and hypoxia occurred in both the dry and wet seasons. The main contributing factors were high seawater temperature and poor water circulation in the dry season and high nutrient loading combined with elevated POC and DOC inputs in the wet season.

Uranium Adsorption on Three Nanohydroxyapatites Under Various Biogeochemical Conditions - Precious Cooper; Jing Nie; Steven L. Larson; John H. Ballard; Heather M. Knotek-Smith; Ahmet Celik; Shaloam Dasari; Xianchun Zhu; Fengxiang X. Han (Water, Air, & Soil Pollution, 2021)

Synthesis of a novel ZnFe2O4/porous biochar magnetic composite for Th(IV) adsorption in aqueous solutions - W. D. Wang; Y. X. Cui; L. K. Zhang; Y. M. Li; P. Sun; J. H. Han (International Journal of Environmental Science and Technology, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

Use of Moringa oleifera seeds powder as bio-coagulants for the surface water treatment - H. T. Nhut; N. T. Q. Hung; B. Q. Lap; L. T. N. Han; T. Q. Tri; N. H. K. Bang; N. T. Hiep; N. M. Ky (International Journal of Environmental Science and Technology, 2021)

The resilience of reproductive interference - Scott M. Villa; Diane D. Han; Malichai E. Jordan; Nicole M. Gerardo (Evolutionary Ecology, 2021)

The Internal Microenvironment of the Symbiotic Jellyfish Cassiopea sp. From the Red Sea - Silvia Arossa; Alan Barozzi; Matteo Callegari; Shannon G. Klein; Anieka J. Parry; Shiou-Han Hung; Alexandra Steckbauer; Manuel Aranda; Daniele Daffonchio; Carlos M. Duarte (Frontiers in Marine Science, 2021)
The characterization of the internal microenvironment of symbiotic marine invertebrates is essential for a better understanding of the symbiosis dynamics. Microalgal symbionts (of the family: Symbiodiniaceae) influence diel fluctuations of in host O 2 and pH conditions through their metabolic activities (i.e., photosynthesis and respiration). These variations may play an important role in driving oxygen budgets and energy demands of the holobiont and its responses to climate change. In situ measurements using microsensors were used to resolve the O 2 and pH diel fluctuations in the oral arms of non-calcifying cnidarian model species Cassiopea sp. (the “upside-down jellyfish”), which has an obligatory association with Symbiodiniaceae. Before sunrise, the internal O 2 and pH levels were substantially lower than those in ambient seawater conditions (minimum average levels: 61.92 ± 5.06 1SE μmol O 2 L –1 and 7.93 ± 0.02 1SE pH units, respectively), indicating that conditions within Cassiopea’s oral arms were acidified and hypoxic relative to the surrounding seawater. Measurements performed during the afternoon revealed hyperoxia (maximum average levels: 546.22 ± 16.45 1SE μmol O 2 L –1 ) and internal pH similar to ambient levels (8.61 ± 0.02 1SE pH units). The calculated gross photosynthetic rates of Cassiopea sp. were 0.04 ± 0.013 1SE nmol cm –2 s –1 in individuals collected at night and 0.08 ± 0.02 1SE nmol cm –2 s –1 in individuals collected during the afternoon.

Microbially Induced Carbonate Precipitation Techniques for the Remediation of Heavy Metal and Trace Element–Polluted Soils and Water - Xue Chen; Dan Zhang; Steven L. Larson; John H. Ballard; Heather M. Knotek-Smith; Jing Nie; Nan Hu; Dexin Ding; Fengxiang X. Han (Water, Air, & Soil Pollution, 2021)

Genetic diversity and population genetic structure in native Ethiopian donkeys (Equus asinus) inferred from equine microsatellite markers - E. Kefena; S. Rosenbom; A. Beja-Pereira; M. Yusuf Kurtu; J. L. Han; T. Dessie (Tropical Animal Health and Production, 2021)

Strain Evolution and Instability of an Anticyclonic Eddy From a Laboratory Experiment - Guoqing Han; Changming Dong; Jingsong Yang; Joel Sommeria; Alexandre Stegner; Rui M. A. Caldeira (Frontiers in Marine Science, 2021)
Using the 13 m diameter LEGI-Coriolis rotating platform, the evolution processes of a generated anticyclonic eddy throughout its lifecycle are analyzed. Experimental results have shown that the eddy lasted for approximately 3 T 0 , where T 0 is the rotating period of 90 s. After T = 0.3 T 0 , the eddy enters its mature phase, whereby following this event, eddy intensity slowly decreases from its maximum rotation speed. By T = 2.6 T 0 , the eddy enters a stage of rapid weakening. In its decay period, two underlying mechanisms for this decay have been identified as inertial instability and eddy–eddy interactions.

Potential Micro-Plastics Dispersal and Accumulation in the North Sea, With Application to the MSC Zoe Incident - Johan van der Molen; Sonja M. van Leeuwen; Laura L. Govers; Tjisse van der Heide; Han Olff (Frontiers in Marine Science, 2021)
The fate and effects of microplastics in the marine environment are an increasingly important area of research, policy and legislation. To manage and reduce microplastics in the seas and oceans, and to help understand causes and effects, we need improved understanding of transport patterns, transit times and accumulation areas. In this paper, we use a particle tracking model to investigate the differences in dispersal and accumulation of microplastics with different properties (floating and sinking) in the North Sea. In these simulations, particles were released with a uniform horizontal distribution, and also from rivers at rates proportional to the river runoff. The results showed that floating particles can accumulate temporarily on salinity fronts and in gyres, and are deposited predominantly on west-facing beaches. Sinking particles moved more slowly and less far, accumulated in deeper areas associated with fine sediments, and were deposited more on west- and north-facing beaches. The model was also applied to the MSC Zoe incident of 1 January 2019, in which 342 containers were lost north of the Dutch Wadden islands in the southern North Sea, tracking two types of microplastics with similar properties (∼5mm floating HDPE pellets and ∼0.6mm sinking PS grains) to identify release locations and potential accumulation areas. We used field observations collected by a citizen science initiative ( waddenplastic.nl ) to constrain the model results. For these simulations, particles were released along the ship’s trajectory and at locations on the trajectory where debris was found. The simulations of the MSC Zoe incident showed that over 90% of floating (∼5mm) HDPE pellets beached within 3–7 weeks, and predominantly on the more eastern Dutch Wadden Islands in agreement with the field observations, and that most of the sinking (∼0.6mm) PS grains were still at sea after 6 weeks, and a large proportion may have been deposited on German shores. The work is relevant to Descriptor 10 (Marine Litter) of the EU Marine Strategy Framework Directive.

Genetic characterization of popcorn hybrids based on SNP genotyping and development of rapid ARMS based primers - Jae-Keun Choi; Jong-Yeol Park; Si-Hwan Ryu; Min Namgung; Moon-Jong Kim; Jeong-Heon Han; M. M. M. Sharma; Seon-Kang Choi; Ik-Young Choi; Rahul Vasudeo Ramekar; Kyong-Cheul Park (Journal of Crop Science and Biotechnology, 2021)

Late Blight Resistance Profiles of Elite Potato Germplasm in the United States - Kristen M. Brown-Donovan; Gregory A. Porter; Ek Han Tan (American Journal of Potato Research, 2021)

Pseudomonas koreensis promotes tomato growth and shows potential to induce stress tolerance via auxin and polyphenol‐related pathways - Q. Guo; Y. Sun; M. Shi; X. Han; Y. Jing; Y. Li; H. Li; H. Lai (Plant and Soil, 2021)

Conservation Implications of Sabellaria spinulosa Reef Patches in a Dynamic Sandy-Bottom Environment - Karin J. van der Reijden; Leo Koop; Sebastiaan Mestdagh; Mirjam Snellen; Peter M. J. Herman; Han Olff; Laura L. Govers (Frontiers in Marine Science, 2021)
Biogenic reefs form biodiversity hotspots and are key components of marine ecosystems, making them priority habitats for nature conservation. However, the conservation status of biogenic reefs generally depends on their size and stability. Dynamic, patchy reefs may therefore be excluded from protection. Here, we studied epibenthos and epifauna density, richness, and community composition of patchy, dynamic Sabellaria spinulosa (ross worm) reefs in the North Sea. This study was conducted by comparing boxcore (endobenthos) and video transect (epifauna) data from two research campaigns in 2017 and 2019 to the Brown Bank area on the Dutch Continental Shelf, where S. spinulosa reefs were first discovered in 2017. The Brown Bank area is characterized by dynamic, migratory bedforms at multiple scales which potentially affect biogenic reef stability. We showed that S. spinulosa habitats had a patchy distribution and alternated with habitats comprised of plain sand. Average S. spinulosa habitat patch size was 5.57 ± 0.99 m and 3.94 ± 0.22 m in 2017 and 2019, respectively (mean ± SE), which especially in 2019 closely resembled the small-scale megaripple bedforms. Contrary to the endobenthos communities that were unaffected by S. spinulosa , epifauna density and species richness were at least two times higher in S. spinulosa habitats compared to sandy habitats, resulting in different community compositions between the two habitat types. We showed that S. spinulosa persisted in the area for almost 2 years. Although the stability of individual patches remained unclear, we demonstrated that even patchy biogenic reefs may promote density and local biodiversity of mobile, epibenthic species, very likely as a result of increased habitat heterogeneity provided by reef habitat patches. This indicates that patchy biogenic reefs that occur in dynamic environments may also have high ecological value and their conservation status should be (re)considered to ensure their protection.

ValSten: a new wild species derived allotetraploid for increasing genetic diversity of the peanut crop (Arachis hypogaea L.) - Dongying Gao; Ana C. G. Araujo; Eliza F. M. B. Nascimento; M. Carolina Chavarro; Han Xia; Scott A. Jackson; David J. Bertioli; Soraya C. M. Leal-Bertioli (Genetic Resources and Crop Evolution, 2021)
Introgression of desirable traits from wild relatives plays an important role in crop improvement, as wild species have important characters such as high resistance to pests and pathogens. However, use of wild peanut relatives is challenging because almost all wild species are diploid and sexually incompatible with cultivated peanut, which is tetraploid (AABB genome type; 2 n = 4x = 40). To overcome the ploidy barrier, we used 2 wild species to make a tetraploid with the same allotetraploid genome composition as cultivated peanut. Crosses were made between 2 diploid wild species, Arachis valida Krapov. and W.C. Greg. (BB genome; 2 n = 2x = 20) and Arachis stenosperma Krapov. and W.C. Greg. (AA genome; 2 n = 2x = 20). Cuttings from the diploid F 1 AB hybrid were treated with colchicine to induce chromosome doubling thus generating an induced allotetraploid. Chromosome counts confirmed polyploidy (AABB genome; 2 n = 4x = 40). We named the new allotetraploid ValSten. Plants had well-developed fertile pollen, produced abundant seed and were sexually compatible with cultivated peanut. ValSten exhibits the same high resistance to early and late leaf spot and rust as its diploid parents. Notably, we observed morphological variations, including flower width and branch angles in the earliest generation (S 0 ) of allotetraploids. A SNP array was used to genotype 47 S 0 allotetraploids. The great majority of markers showed the additive allelic state from both parents (AABB). However, some loci were AAAA or BBBB, indicating homeologous recombination. ValSten provides a new, vigorous, highly fertile, disease resistant germplasm for peanut research and improvement.

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

NABat: A top-down, bottom-up solution to collaborative continental-scale monitoring - Brian E. Reichert; Mylea Bayless; Tina L. Cheng; Jeremy T. H. Coleman; Charles M. Francis; Winifred F. Frick; Benjamin S. Gotthold; Kathryn M. Irvine; Cori Lausen; Han Li; Susan C. Loeb; Jonathan D. Reichard; et al. (Ambio, 2021)
Collaborative monitoring over broad scales and levels of ecological organization can inform conservation efforts necessary to address the contemporary biodiversity crisis. An important challenge to collaborative monitoring is motivating local engagement with enough buy-in from stakeholders while providing adequate top-down direction for scientific rigor, quality control, and coordination. Collaborative monitoring must reconcile this inherent tension between top-down control and bottom-up engagement. Highly mobile and cryptic taxa, such as bats, present a particularly acute challenge. Given their scale of movement, complex life histories, and rapidly expanding threats, understanding population trends of bats requires coordinated broad-scale collaborative monitoring. The North American Bat Monitoring Program (NABat) reconciles top-down, bottom-up tension with a hierarchical master sample survey design, integrated data analysis, dynamic data curation, regional monitoring hubs, and knowledge delivery through web-based infrastructure. NABat supports collaborative monitoring across spatial and organizational scales and the full annual lifecycle of bats.

Slingshot spiders build tensed, underdamped webs for ultrafast launches and speedy halts - Elio J. Challita; Symone L. M. Alexander; Sarah I. Han; Todd A. Blackledge; Jonathan A. Coddington; Sunghwan Jung; M. Saad Bhamla (Journal of Comparative Physiology A, 2021)

The Interface Motion and Hydrodynamic Shear of the Liquid Slosh in Syringes - Yuchen Zhang; Dingding Han; Zhongwang Dou; Jean-Christophe Veilleux; Galen H. Shi; David S. Collins; Pavlos P. Vlachos; Arezoo M. Ardekani (Pharmaceutical Research, 2021)

The reduction of lipid-sourced energy production caused by ATGL inhibition cannot be compensated by activation of HSL, autophagy, and utilization of other nutrients in fish - Si-Lan Han; Yan Liu; Samwel M. Limbu; Li-Qiao Chen; Mei-Ling Zhang; Zhen-Yu Du (Fish Physiology and Biochemistry, 2021)

Cycling in degradation of organic polymers and uptake of nutrients by a litter‐degrading fungus - Aurin M. Vos; Robert‐Jan Bleichrodt; Koen C. Herman; Robin A. Ohm; Karin Scholtmeijer; Heike Schmitt; Luis G. Lugones; Han A. B. Wösten (Environmental Microbiology, 2021)
Summary Wood and litter degrading fungi are the main decomposers of lignocellulose and thus play a key role in carbon cycling in nature. Here, we provide evidence for a novel lignocellulose degradation strategy employed by the litter degrading fungus Agaricus bisporus (known as the white button mushroom). Fusion of hyphae allows this fungus to synchronize the activity of its mycelium over large distances (50 cm). The synchronized activity has a 13‐h interval that increases to 20 h before becoming irregular and it is associated with a 3.5‐fold increase in respiration, while compost temperature increases up to 2°C. Transcriptomic analysis of this burst‐like phenomenon supports a cyclic degradation of lignin, deconstruction of (hemi‐) cellulose and microbial cell wall polymers, and uptake of degradation products during vegetative growth of A. bisporus . Cycling in expression of the ligninolytic system, of enzymes involved in saccharification, and of proteins involved in nutrient uptake is proposed to provide an efficient way for degradation of substrates such as litter.

Dissociable dopaminergic and pavlovian influences in goal-trackers and sign-trackers on a model of compulsive checking in OCD - D. M. Eagle; C. Schepisi; S. Chugh; S. Desai; S. Y. S. Han; T. Huang; J. J. Lee; C. Sobala; W. Ye; A. L. Milton; T. W. Robbins (Psychopharmacology, 2020)
Rationale Checking is a functional behaviour that provides information to guide behaviour. However, in obsessive-compulsive disorder (OCD), checking may escalate to dysfunctional levels. The processes underpinning the transition from functional to dysfunctional checking are unclear but may be associated with individual differences that support the development of maladaptive behaviour. We examined one such predisposition, sign-tracking to a pavlovian conditioned stimulus, which we previously found associated with dysfunctional checking. How sign-tracking interacts with another treatment with emerging translational validity for OCD-like checking, chronic administration of the dopamine D 2 receptor agonist quinpirole, is unknown. Objectives We tested how functional and dysfunctional checking in the rat observing response task (ORT) was affected by chronic quinpirole administration in non-autoshaped controls and autoshaped animals classified as sign-trackers or goal-trackers. Methods Sign-trackers or goal-trackers were trained on the ORT before the effects of chronic quinpirole administration on checking were assessed. Subsequently, the effects on checking of different behavioural challenges, including reward omission and the use of unpredictable reinforcement schedules, were tested. Results Prior autoshaping increased checking. Sign-trackers and goal-trackers responded differently to quinpirole sensitization, reward omission and reinforcement uncertainty. Sign-trackers showed greater elevations in dysfunctional checking, particularly during uncertainty. By contrast, goal-trackers predominantly increased functional checking responses, possibly in response to reduced discrimination accuracy in the absence of cues signalling which lever was currently active. Conclusions The results are discussed in terms of how pavlovian associations influence behaviour that becomes compulsive in OCD and how this may be dependent on striatal dopamine D 2 receptors.

Replication study and meta-analysis indicate a suggestive association of RUNX3 locus with primary biliary cholangitis - Rohil Jawed; Mingming Zhang; Chan Wang; Shu-Han Yang; Peng Jiang; Qiuyuan Wu; Li Li; Weichang Chen; M. Eric Gershwin; Ye Tian; Michael F. Seldin; Xiong Ma; et al. (Immunogenetics, 2020)

Regional drivers of diversification in the late Quaternary in a widely distributed generalist species, the common pheasant Phasianus colchicus - Simin Liu; Yang Liu; Edouard Jelen; Mansour Alibadian; Cheng‐Te Yao; Xintong Li; Nasrin Kayvanfar; Yutao Wang; Farhad S. M. Vahidi; Jian‐Lin Han; Gombobaatar Sundev; Zhengwang Zhang; et al. (Journal of Biogeography, 2020)
Aim Pleistocene climate and associated environmental changes have influenced phylogeographic patterns of many species. These not only depend on a species’ life history but also vary regionally. Consequently, populations of widespread species that occur in several biomes might display different evolutionary trajectories. We aimed to identify regional drivers of diversification in the common pheasant, a widely distributed ecological generalist. Location Asia. Taxon Common pheasant Phasianus colchicus . Methods Using a comprehensive geographical sampling of 204 individuals from the species’ entire range genotyped at seven nuclear and two mitochondrial loci, we reconstructed spatio‐temporal diversification and demographic history of the common pheasant. We applied Bayesian phylogenetic inference to describe phylogeographic structure, generated a species tree and inferred demographic history within and migration between lineages. Moreover, to establish a taxonomic framework, we conducted a species delimitation analysis. Results The common pheasant diversified during the Late Pleistocene into eight distinct lineages. It originated at the edge of the Qinghai–Tibetan plateau and spread to East and Central Asia. Only the widely distributed lowland lineage of East Asia displayed recent range expansion. Greater phylogeographic structure was identified elsewhere, with lineages showing no sign of recent demographic changes. One lineage in south‐central China is the result of long‐term isolation within a climatically stable but topographically complex region. In lineages from arid Central Asia and China, range expansions were impeded by repeated population fragmentation during dry glacial periods and by recent aridification. Main conclusions Spatio‐temporal phylogeographic frameworks of widespread taxa such as the common pheasant provide valuable opportunities to identify divergent drivers of regional diversification. Our results suggest that diversification and population histories in the eight distinct evolutionary lineages were shaped by regionally variable effects of past climate and associated environmental changes. The evolutionary history of the common pheasant is best reflected by its being split into three species.

Phosphodiesterase 2 inhibitor Hcyb1 reverses corticosterone-induced neurotoxicity and depression-like behavior - Meng-Jia Zhu; Jing Shi; Yong Chen; Guobing Huang; Xiong-Wei Zhu; Sam Zhang; Xian-Feng Huang; Guo-Qiang Song; Han-Ting Zhang; Heng-Ming Ke; James M. O’Donnell; Li-Qun Wang; et al. (Psychopharmacology, 2020)

Evolution Mechanisms of Carbonate Reservoirs Based on Dissolution Rates and Multifractal Analysis of Microscopic Morphology - Jiayi Ma; Shuyun Xie; Huayun Tang; Ming Ma; Emmanuel John M. Carranza; Jun Han; Zhiliang He; Cunli Jiao; Hai Zhang (Natural Resources Research, 2020)

DNA Polyplexes of a Phosphorylcholine-Based Zwitterionic Polymer for Gene Delivery - Kandarp M. Dave; Linjiang Han; Meredith A. Jackson; Lindsay Kadlecik; Craig L. Duvall; Devika S Manickam (Pharmaceutical Research, 2020)

Potential pathophysiological role of microRNA 193b-5p in human placentae from pregnancies complicated by preeclampsia and intrauterine growth restriction - Zain Awamleh; Victor K. M. Han (Molecular Biology Reports, 2020)

Anthropogenic Contaminants and Histopathological Findings in Stranded Cetaceans in the Southeastern United States, 2012–2018 - Annie Page-Karjian; Catherine F. Lo; Branson Ritchie; Craig A. Harms; David S. Rotstein; Sushan Han; Sayed M. Hassan; Andreas F. Lehner; John P. Buchweitz; Victoria G. Thayer; Jill M. Sullivan; Emily F. Christiansen; et al. (Frontiers in Marine Science, 2020)

Multiomic immune clockworks of pregnancy - Laura S. Peterson; Ina A. Stelzer; Amy S. Tsai; Mohammad S. Ghaemi; Xiaoyuan Han; Kazuo Ando; Virginia D. Winn; Nadine R. Martinez; Kevin Contrepois; Mira N. Moufarrej; Stephen Quake; David A. Relman; et al. (Seminars in Immunopathology, 2020)
Preterm birth is the leading cause of mortality in children under the age of five worldwide. Despite major efforts, we still lack the ability to accurately predict and effectively prevent preterm birth. While multiple factors contribute to preterm labor, dysregulations of immunological adaptations required for the maintenance of a healthy pregnancy is at its pathophysiological core. Consequently, a precise understanding of these chronologically paced immune adaptations and of the biological pacemakers that synchronize the pregnancy “immune clock” is a critical first step towards identifying deviations that are hallmarks of peterm birth. Here, we will review key elements of the fetal, placental, and maternal pacemakers that program the immune clock of pregnancy. We will then emphasize multiomic studies that enable a more integrated view of pregnancy-related immune adaptations. Such multiomic assessments can strengthen the biological plausibility of immunological findings and increase the power of biological signatures predictive of preterm birth

Synthesis, molecular docking and evaluation of novel sulfonyl hydrazones as anticancer agents and COX-2 inhibitors - Sevil Şenkardeş; M. İhsan Han; Necla Kulabaş; Mürüvvet Abbak; Özge Çevik; İlkay Küçükgüzel; Ş. Güniz Küçükgüzel (Molecular Diversity, 2020)

Genetic and antigenic characterization of influenza A/H5N1 viruses isolated from patients in Indonesia, 2008–2015 - Hana A. Pawestri; Arie A. Nugraha; Alvin X. Han; Eka Pratiwi; Edyth Parker; Mathilde Richard; Stefan van der Vliet; Ron A. M. Fouchier; David H. Muljono; Menno D. de Jong; Vivi Setiawaty; Dirk Eggink (Virus Genes, 2020)

Simultaneous fluorescence imaging of distinct nerve and blood vessel patterns in dual Thy1-YFP and Flt1-DsRed transgenic mice - Samuel M. Santosa; Kai Guo; Michael Yamakawa; Evguenia Ivakhnitskaia; Neeraj Chawla; Tara Nguyen; Kyu-Yeon Han; Masatsugu Ema; Mark I. Rosenblatt; Jin-Hong Chang; Dimitri T. Azar (Angiogenesis, 2020)

Integrating data mining and transmission theory in the ecology of infectious diseases - Barbara A. Han; Suzanne M. O’Regan; John Paul Schmidt; John M. Drake (Ecology Letters, 2020)
Our understanding of ecological processes is built on patterns inferred from data. Applying modern analytical tools such as machine learning to increasingly high dimensional data offers the potential to expand our perspectives on these processes, shedding new light on complex ecological phenomena such as pathogen transmission in wild populations. Here, we propose a novel approach that combines data mining with theoretical models of disease dynamics. Using rodents as an example, we incorporate statistical differences in the life history features of zoonotic reservoir hosts into pathogen transmission models, enabling us to bound the range of dynamical phenomena associated with hosts, based on their traits. We then test for associations between equilibrium prevalence, a key epidemiological metric and data on human outbreaks of rodent‐borne zoonoses, identifying matches between empirical evidence and theoretical predictions of transmission dynamics. We show how this framework can be generalized to other systems through a rubric of disease models and parameters that can be derived from empirical data. By linking life history components directly to their effects on disease dynamics, our mining‐modelling approach integrates machine learning and theoretical models to explore mechanisms in the macroecology of pathogen transmission and their consequences for spillover infection to humans.

Carbapenem-resistant Enterobacteriaceae in patients with bacteraemia at tertiary hospitals in South Africa, 2015 to 2018 - O. Perovic; H. Ismail; V. Quan; C. Bamford; T. Nana; V. Chibabhai; P. Bhola; P. Ramjathan; K. Swe Swe-Han; J. Wadula; A. Whitelaw; M. Smith; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

The gene repertoire of Pythium porphyrae (Oomycota) suggests an adapted plant pathogen tackling red algae - Yacine Badis; Jong Won Han; Tatyana A. Klochkova; Claire M. M. Gachon; Gwang Hoon Kim (Algae, 2020)

Ontogenetic niche shifts as a driver of seasonal migration - Wimke Fokkema; Henk P. van der Jeugd; Thomas K. Lameris; Adriaan M. Dokter; Barwolt S. Ebbinge; André M. de Roos; Bart A. Nolet; Theunis Piersma; Han Olff (Oecologia, 2020)
Ontogenetic niche shifts have helped to understand population dynamics. Here we show that ontogenetic niche shifts also offer an explanation, complementary to traditional concepts, as to why certain species show seasonal migration. We describe how demographic processes (survival, reproduction and migration) and associated ecological requirements of species may change with ontogenetic stage (juvenile, adult) and across the migratory range (breeding, non-breeding). We apply this concept to widely different species (dark-bellied brent geese ( Branta b. bernicla ), humpback whales ( Megaptera novaeangliae ) and migratory Pacific salmon ( Oncorhynchus gorbuscha ) to check the generality of this hypothesis. Consistent with the idea that ontogenetic niche shifts are an important driver of seasonal migration, we find that growth and survival of juvenile life stages profit most from ecological conditions that are specific to breeding areas. We suggest that matrix population modelling techniques are promising to detect the importance of the ontogenetic niche shifts in maintaining migratory strategies. As a proof of concept, we applied a first analysis to resident, partial migratory and fully migratory populations of barnacle geese ( Branta leucopsis ). We argue that recognition of the costs and benefits of migration, and how these vary with life stages, is important to understand and conserve migration under global environmental change.

Glycosaminoglycan remodeling during chondrogenic differentiation of human bone marrow−/synovial-derived mesenchymal stem/stromal cells under normoxia and hypoxia - João C. Silva; Xiaorui Han; Teresa P. Silva; Ke Xia; Paiyz E. Mikael; Joaquim M. S. Cabral; Frederico Castelo Ferreira; Robert J. Linhardt (Glycoconjugate Journal, 2020)

Random Forest and Bayesian Network Techniques for Probabilistic Prediction of Flyrock Induced by Blasting in Quarry Sites - Han Han; Danial Jahed Armaghani; Reza Tarinejad; Jian Zhou; M. M. Tahir (Natural Resources Research, 2020)

The transformation of the lithospheric mantle beneath South China Block (SCB): constraints from petrological and geochemical studies of Daoxian and Ningyuan basalts and their melt inclusions - Xianzhe Duan; Hongfu Zhang; M. Santosh; Hengci Tian; He Sun; Kaixuan Tan; Shili Han; Yilin Xiao; Zhenhui Hou; Yanqun Zhang; Le Jiang (International Geology Review, 2020)

Incidence and Clinical Features of TRPV4-Linked Axonal Neuropathies in a USA Cohort of Charcot–Marie–Tooth Disease Type 2 - Sheng Deng; Shawna M. E. Feely; Yong Shi; Hong Zhai; Luna Zhan; Teepu Siddique; Han-Xiang Deng; Michael E. Shy (NeuroMolecular Medicine, 2020)

Role of Adult Tissue-Derived Pluripotent Stem Cells in Bone Regeneration - Liudmila Leppik; K. Sielatycka; D. Henrich; Z. Han; H. Wang; M. J. Eischen-Loges; K. M. C. Oliveira; M. B. Bhavsar; M. Z. Ratajczak; J. H. Barker (Stem Cell Reviews and Reports, 2020)
Background Bone marrow-derived mononuclear cells (BM-MNC) consist of a heterogeneous mix of mesenchymal stem cells (MSC), hematopoietic progenitor cells (HPC), endothelial progenitor cells (EPC), monocytes, lymphocytes and pluripotent stem cells. Whereas the importance of MSC and EPC has been well documented in bone healing and regeneration studies, the role of pluripotent stem cells is still poorly understood. In the present study we evaluated if and how Very Small Embryonic Like cells (VSEL), isolated from rat BM-MNC, contribute to bone healing. Methods Large bone defects were made in the femurs of 38 Sprague Dawley female rats and treated with β-TCP scaffold granules seeded with male VSEL; BM-MNC, VSEL-depleted BM-MNC or scaffold alone, and bone healing was evaluated at 8 weeks post-surgery. Results Bone healing was significantly increased in defects treated with VSEL and BM-MNC, compared to defects treated with VSEL-depleted BM-MNC. Donor cells were detected in new bone tissue, in all the defects treated with cells, and in fibrous tissue only in defects treated with VSEL-depleted BM-MNC. The number of CD68+ cells was the highest in the VSEL-depleted group, whereas the number of TRAP positive cells was the lowest in this group. Conclusions Based on the results, we can conclude that VSEL play a role in BM-MNC induced bone formation. In our rat femur defect model, in defects treated with VSEL-depleted BM-MNC, osteoclastogenesis and bone formation were decreased, and foreign body reaction was increased.

Stem Cell Mechanosensation on Gelatin Methacryloyl (GelMA) Stiffness Gradient Hydrogels - Claire Kim; Jennifer L. Young; Andrew W. Holle; Kwanghee Jeong; Luke G. Major; Ji Hoon Jeong; Zachary M. Aman; Dong-Wook Han; Yongsung Hwang; Joachim P. Spatz; Yu Suk Choi (Annals of Biomedical Engineering, 2020)

Front Cover - Wei Wang; Jie Wang; Francis M. P. Choi; Ping Ding; Xiao‐xu Li; Guo‐dong Han; Meng‐wen Ding; Minquan Guo; Xiong‐wei Huang; Wei‐xiang Duan; Zhi‐yuan Cheng; Zhi‐yuan Chen; et al. (Global Ecology and Biogeography, 2020)

Global warming and artificial shorelines reshape seashore biogeography - Wei Wang; Jie Wang; Francis M. P. Choi; Ping Ding; Xiao‐xu Li; Guo‐dong Han; Meng‐wen Ding; Minquan Guo; Xiong‐wei Huang; Wei‐xiang Duan; Zhi‐yuan Cheng; Zhi‐yuan Chen; et al. (Global Ecology and Biogeography, 2020)
Aim Rapid anthropogenic warming coupled with changes in land use is altering the distributions of species, with consequences for ecosystem functioning and services. It is crucial to evaluate species range shifts based on understanding of the interaction of temperature with non‐climatic factors such as habitat availability and dispersal potential. Here, we aim to investigate roles of environmental temperature, habitat availability and population connectivity on the distributions of hard‐shore intertidal animals. We further examine potential roles of extensive artificial seawall construction in enabling poleward expansion of species in China, thus reshaping coastal biogeography. Location Chinese coast. Time period 2013–2017. Major taxa studied Intertidal invertebrates. Methods We took an integrative approach encompassing distributional ecology, thermal physiology, molecular genetics, heat budget modelling and larval dispersal to elucidate how interacting multiple drivers, including temperature, habitat availability and larval dispersal, determine distributions of hard‐shore invertebrates, focusing on what sets their range edges at a boundary between biogeographic provinces. Results Our results untangle the complex interactions of global climate change with the impacts of regional scale coastal development. Temperature, larval transport and habitat availability are the major proximate factors controlling the range limits of coastal marine species. The artificial shorelines provide suitable habitats for hard‐shore species on the Yangtze River Delta, and minimum temperature in winter is an important factor setting the new northern range limit of these hard‐shore species along the Chinese coast. Main conclusions In the face of global warming and global sprawl of marine hard infrastructure, species distributions, community structures and biogeographic patterns are experiencing dramatic changes. The combined influence of multiple human stressors including climate change and artificial shorelines can be evaluated by using a multidisciplinary framework, including ecological distribution, physiological sensitivity of species to these stressors, and the role of dispersal in maintaining population connectivity.

Climate‐dependent variation in cold tolerance of weedy rice and rice mediated by OsICE1 promoter methylation - Hongjie Xie; Yihao Han; Xinyue Li; Weimin Dai; Xiaoling Song; Kenneth M. Olsen; Sheng Qiang (Molecular Ecology, 2020)
The mechanisms by which weedy rice ( Oryza sativa f. spontanea ) has adapted to endure low‐temperature stress in northern latitudes remain unresolved. In this study, we assessed cold tolerance of 100 rice varieties and 100 co‐occurring weedy rice populations, which were sampled across a broad range of climates in China. A parallel pattern of latitude‐dependent variation in cold tolerance was detected in cultivated rice and weedy rice. At the molecular level, differential cold tolerance was strongly correlated with relative expression levels of CBF cold response pathway genes and with methylation levels in the promoter region of OsICE1 , a regulator of this pathway. Among all methylated cytosine sites of the OsICE1 promoter, levels of CHG and CHH methylation were found to be significantly correlated with cold tolerance among accessions. Furthermore, within many of the collection locales, weedy rice shared identical or near‐identical OsICE1 methylation patterns with co‐occurring cultivated rice. These findings provide new insights on the possible roles that methylation variation in the OsICE1 promoter may play in cold tolerance, and they suggest that weedy rice can rapidly acquire cold tolerance via methylation patterns that are shared with co‐occurring rice cultivars.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Current Opinions and Consensus for Studying Tremor in Animal Models - Sheng-Han Kuo; Elan D. Louis; Phyllis L. Faust; Adrian Handforth; Su-youne Chang; Billur Avlar; Eric J. Lang; Ming-Kai Pan; Lauren N. Miterko; Amanda M. Brown; Roy V. Sillitoe; Collin J. Anderson; et al. (The Cerebellum, 2019)

Ecosystem engineering creates a new path to resilience in plants with contrasting growth strategies - Laura M. Soissons; Marieke M. van Katwijk; Baoquan Li; Qiuying Han; Tom Ysebaert; Peter M. J. Herman; Tjeerd J. Bouma (Oecologia, 2019)

Water-Saving Traits Can Protect Wheat Grain Number Under Progressive Soil Drying at the Meiotic Stage: A Phenotyping Approach - Michele Faralli; Kevin S. Williams; Jiwan Han; Fiona M. K. Corke; John H. Doonan; Peter S. Kettlewell (Journal of Plant Growth Regulation, 2019)

Corrigendum: Night-Time Temperature Reprieves Enhance the Thermal Tolerance of a Symbiotic Cnidarian - Shannon G. Klein; Kylie A. Pitt; Cathy H. Lucas; Shiou-Han Hung; Sebastian Schmidt-Roach; Manuel Aranda; Carlos M. Duarte (Frontiers in Marine Science, 2019)

Characteristics of an Advective Marine Heatwave in the Middle Atlantic Bight in Early 2017 - Glen Gawarkiewicz; Ke Chen; Jacob Forsyth; Frank Bahr; Anna M. Mercer; Aubrey Ellertson; Paula Fratantoni; Harvey Seim; Sara Haines; Lu Han (Frontiers in Marine Science, 2019)

Impacts of Basin-Scale Climate Modes on Coastal Sea Level: a Review - Weiqing Han; Detlef Stammer; Philip Thompson; Tal Ezer; Hindu Palanisamy; Xuebin Zhang; Catia M. Domingues; Lei Zhang; Dongliang Yuan (Surveys in Geophysics, 2019)

Climate Model Uncertainty and Trend Detection in Regional Sea Level Projections: A Review - Mark Carson; Kewei Lyu; Kristin Richter; Mélanie Becker; Catia M. Domingues; Weiqing Han; Laure Zanna (Surveys in Geophysics, 2019)

Plant and microalgae consortium for an enhanced biodegradation of sulfamethazine - Jiu-Qiang Xiong; Byong-Hun Jeon; Sanjay P. Govindwar; Mayur B. Kurade; Swapnil M. Patil; Jung-Han Park; Ki-Hyun Kim (Environmental Science and Pollution Research, 2019)

COL4A1 mutations as a potential novel cause of autosomal dominant CAKUT in humans - Thomas M. Kitzler; Ronen Schneider; Stefan Kohl; Caroline M. Kolvenbach; Dervla M. Connaughton; Rufeng Dai; Nina Mann; Makiko Nakayama; Amar J. Majmundar; Chen-Han W. Wu; Jameela A. Kari; Sherif M. El Desoky; et al. (Human Genetics, 2019)

Asymmetry in above‐ and belowground productivity responses to N addition in a semi‐arid temperate steppe - Jing Wang; Yingzhi Gao; Yunhai Zhang; Junjie Yang; Melinda D. Smith; Alan K. Knapp; David M. Eissenstat; Xingguo Han (Global Change Biology, 2019)
Nitrogen (N) enrichment often increases aboveground net primary productivity (ANPP) of the ecosystem, but it is unclear if belowground net primary productivity (BNPP) track responses of ANPP. Moreover, the frequency of N inputs may affect primary productivity but is rarely studied. To assess the response patterns of above‐ and belowground productivity to rates of N addition under different addition frequencies, we manipulated the rate (0–50 g N m −2 year −1 ) and frequency (twice vs. monthly additions per year) of NH 4 NO 3 inputs for six consecutive years in a temperate grassland in northern China and measured ANPP and BNPP from 2012 to 2014. In the low range of N addition rates, BNPP showed the greatest negative response and ANPP showed the greatest positive responses with increases in N addition ( −2 year −1 ). As N addition increased beyond 10 g N m −2 year −1 , increases in ANPP dampened and decreases in BNPP ceased altogether. The response pattern of net primary productivity (combined above‐ and belowground; NPP) corresponded more closely to ANPP than to BNPP. The N effects on BNPP and BNPP/NPP ( f BNPP ) were not dependent on N addition frequency in the range of N additions typically associated with N deposition. BNPP was more sensitive to N addition frequency than ANPP, especially at low rates of N addition. Our findings provide new insights into how plants regulate carbon allocation to different organs with increasing N rates and changing addition frequencies. These root response patterns, if incorporated into Earth system models, may improve the predictive power of C dynamics in dryland ecosystems in the face of global atmospheric N deposition.

Increased Diagnostic Yield of Spastic Paraplegia with or Without Cerebellar Ataxia Through Whole-Genome Sequencing - Aryun Kim; Kishore R. Kumar; Ryan L. Davis; Amali C. Mallawaarachchi; Velimir Gayevskiy; Andre E. Minoche; Zachary Walls; Han-Joon Kim; Mihee Jang; Mark J. Cowley; Ji-Hyun Choi; Chaewon Shin; et al. (The Cerebellum, 2019)

Development of polymorphic microsatellite markers for tree peony Paeonia delavayi (Paeoniaceae) using ddRAD-seq data - Shao-Lin Tan; Peter M. Hollingsworth; Han-Tao Qin; Lin-Jiang Ye; Jia-Yun Zou; Lian-Ming Gao (Molecular Biology Reports, 2019)

Seagrass Sensitivity to Collapse Along a Hydrodynamic Gradient: Evidence from a Pristine Subtropical Intertidal Ecosystem - El-Hacen M. El-Hacen; Tjeerd J. Bouma; Laura L. Govers; Theunis Piersma; Han Olff (Ecosystems, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Night-Time Temperature Reprieves Enhance the Thermal Tolerance of a Symbiotic Cnidarian - Shannon G. Klein; Kylie A. Pitt; Cathy H. Lucas; Shiou-Han Hung; Sebastian Schmidt-Roach; Manuel Aranda; Carlos M. Duarte (Frontiers in Marine Science, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

A Sustained Ocean Observing System in the Indian Ocean for Climate Related Scientific Knowledge and Societal Needs - J. C. Hermes; Y. Masumoto; L. M. Beal; M. K. Roxy; J. Vialard; M. Andres; H. Annamalai; S. Behera; N. D’Adamo; T. Doi; M. Feng; W. Han; et al. (Frontiers in Marine Science, 2019)

Tremor in the Degenerative Cerebellum: Towards the Understanding of Brain Circuitry for Tremor - Ruo-Yah Lai; Darya Tomishon; Karla P. Figueroa; Stefan M. Pulst; Susan Perlman; George Wilmot; Christopher M. Gomez; Jeremy D. Schmahmann; Henry Paulson; Vikram G. Shakkottai; Sarah H. Ying; Theresa Zesiewicz; et al. (The Cerebellum, 2019)

Operating characteristics of stepwise covariate selection in pharmacometric modeling - Malidi Ahamadi; Anna Largajolli; Paul M. Diderichsen; Rik de Greef; Thomas Kerbusch; Han Witjes; Akshita Chawla; Casey B. Davis; Ferdous Gheyas (Journal of Pharmacokinetics and Pharmacodynamics, 2019)

Nocardioides speluncae sp. nov., a novel actinobacterium isolated from a karstic subterranean environment sample - Bao-Zhu Fang; Ming-Xian Han; Jian-Yu Jiao; Xiao-Tong Zhang; Yuan-Guo Xie; Wael N. Hozzein; Dalal Hussien M. Alkhalifah; Min Xiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Optogenetic stimulation of basal forebrain parvalbumin neurons modulates the cortical topography of auditory steady-state responses - Eunjin Hwang; Ritchie E. Brown; Bernat Kocsis; Tae Kim; James T. McKenna; James M. McNally; Hio-Been Han; Jee Hyun Choi (Brain Structure and Function, 2019)

A high production of flavonoids and anthraquinones via adventitious root culture of Oplopanax elatus and evaluating antioxidant activity - L. Han; X. C. Piao; J. Jiang; X. L. Jiang; C. R. Yin; M. L. Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Compositional and structural analysis of glycosaminoglycans in cell-derived extracellular matrices - João C. Silva; Marta S. Carvalho; Xiaorui Han; Ke Xia; Paiyz E. Mikael; Joaquim M. S. Cabral; Frederico Castelo Ferreira; Robert J. Linhardt (Glycoconjugate Journal, 2019)

High frequency and diversity of parechovirus A in a cohort of Malawian children - Lieke Brouwer; Eveliina Karelehto; Alvin X. Han; Xiomara V. Thomas; Andrea H. L. Bruning; Job C. J. Calis; Michaël Boele van Hensbroek; Brenda M. Westerhuis; Darsha Amarthalingam; Sylvie M. Koekkoek; Sjoerd P. H. Rebers; Kamija S. Phiri; et al. (Archives of Virology, 2019)

Expression and characterisation of a pH and salt tolerant, thermostable and xylose tolerant recombinant GH43 β-xylosidase from Thermobifida halotolerans YIM 90462T for promoting hemicellulose degradation - Yi-Rui Yin; Wen-Dong Xian; Ming-Xian Han; En-Min Zhou; Lan Liu; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Min Xiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Disrupted topological organization of the frontal-mesolimbic network in obese patients - Qianqian Meng; Yu Han; Gang Ji; Guanya Li; Yang Hu; Li Liu; Qingchao Jin; Karen M. von Deneen; Jizheng Zhao; Guangbin Cui; Huaning Wang; Dardo Tomasi; et al. (Brain Imaging and Behavior, 2018)

Optimization of culture medium components and culture period for production of adventitious roots of Echinacea pallida (Nutt.) Nutt - Y. Gao; C. H. Wu; X. C. Piao; L. Han; R. Gao; M. L. Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Fluorescent reporter transgenic mice for in vivo live imaging of angiogenesis and lymphangiogenesis - Susan J. Doh; Michael Yamakawa; Samuel M. Santosa; Mario Montana; Kai Guo; Joseph R. Sauer; Nicholas Curran; Kyu-Yeon Han; Charles Yu; Masatsugu Ema; Mark I. Rosenblatt; Jin-Hong Chang; et al. (Angiogenesis, 2018)

Millennial multi-proxy reconstruction of oasis dynamics in Jordan, by the Dead Sea - Sebastian Eggenberger; Erika Gobet; Jacqueline F. N. van Leeuwen; Christoph Schwörer; Willem O. van der Knaap; Han F. van Dobben; Hendrik Vogel; Willy Tinner; Claire M. C. Rambeau (Vegetation History and Archaeobotany, 2018)

Carbon Storage Declines in Old Boreal Forests Irrespective of Succession Pathway - Bilei Gao; Anthony R. Taylor; Eric B. Searle; Praveen Kumar; Zilong Ma; Alexandra M. Hume; Han Y. H. Chen (Ecosystems, 2018)

Fecal pollution: new trends and challenges in microbial source tracking using next‐generation sequencing - Tatsuya Unno; Christopher Staley; Clairessa M. Brown; Dukki Han; Michael J. Sadowsky; Hor‐Gil Hur (Environmental Microbiology, 2018)
Summary In this minireview, we expand upon traditional microbial source tracking (MST) methods by discussing two recently developed, next‐generation‐sequencing (NGS)‐based MST approaches to identify sources of fecal pollution in recreational waters. One method defines operational taxonomic units (OTUs) that are specific to a fecal source, e.g., humans and animals or shared among multiple fecal sources to determine the magnitude and likely source association of fecal pollution. The other method uses SourceTracker, a program using a Bayesian algorithm, to determine which OTUs have contributed to an environmental community based on the composition of microbial communities in multiple fecal sources. Contemporary NGS‐based MST tools offer a promising avenue to rapidly characterize fecal source contributions for water monitoring and remediation efforts at a broader and more efficient scale than previous molecular MST methods. However, both NGS methods require optimized sequence processing methodologies (e.g. quality filtering and clustering algorithms) and are influenced by primer selection for amplicon sequencing. Therefore, care must be taken when extrapolating data or combining datasets. Furthermore, traditional limitations of library‐dependent MST methods, including differential decay of source material in environmental waters and spatiotemporal variation in source communities, remain to be fully understood. Nevertheless, increasing use of these methods, as well as expanding fecal taxon libraries representative of source communities, will help improve the accuracy of these methods and provide promising tools for future MST investigations.

Inhibition of phosphodiesterase 2 by Bay 60-7550 decreases ethanol intake and preference in mice - Jing Shi; Huaxia Liu; Jianchun Pan; Jie Chen; Nianping Zhang; Kaiping Liu; Ning Fei; James M. O’Donnell; Han-Ting Zhang; Ying Xu (Psychopharmacology, 2018)

Forward modelling of global gravity fields with 3D density structures and an application to the high-resolution (~ 2 km) gravity fields of the Moon - M. Šprlák; S.-C. Han; W. E. Featherstone (Journal of Geodesy, 2018)

ERM model analysis for adaptation to hydrological model errors - M. Baymani-Nezhad; D. Han (Acta Geophysica, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

An Automatic Computer-Aided Diagnosis System for Breast Cancer in Digital Mammograms via Deep Belief Network - Mugahed A. Al-antari; Mohammed A. Al-masni; Sung-Un Park; JunHyeok Park; Mohamed K. Metwally; Yasser M. Kadah; Seung-Moo Han; Tae-Seong Kim (Journal of Medical and Biological Engineering, 2018)

Sequence divergence between spelt and common wheat - Miao Liu; Qiang Zhao; Feng Qi; Jiri Stiller; Shican Tang; Jiashun Miao; Jan Vrána; Kateřina Holušová; Dengcai Liu; Jaroslav Doležel; John M. Manners; Bin Han; et al. (Theoretical and Applied Genetics, 2018)

De novo mutations in MED13, a component of the Mediator complex, are associated with a novel neurodevelopmental disorder - Lot Snijders Blok; Susan M. Hiatt; Kevin M. Bowling; Jeremy W. Prokop; Krysta L. Engel; J. Nicholas Cochran; E. Martina Bebin; Emilia K. Bijlsma; Claudia A. L. Ruivenkamp; Paulien Terhal; Marleen E. H. Simon; Rosemarie Smith; et al. (Human Genetics, 2018)

Genome sequence and comparative analysis of Jiangella alba YIM 61503T isolated from a medicinal plant Maytenus austroyunnanensis - Jian-Yu Jiao; Nimaichand Salam; Lan Liu; Manik Prabhu Narsing Rao; Xiao-Tong Zhang; Bao-Zhu Fang; Ming-Xian Han; Zi-Tong Zhang; Jing Chen; Jiao Zhao; Yu Zhou; Dalal Hussien M. Alkhalifah; et al. (Antonie van Leeuwenhoek, 2018)

Rhizosphere‐associated Pseudomonas induce systemic resistance to herbivores at the cost of susceptibility to bacterial pathogens - Cara H. Haney; Christina L. Wiesmann; Lori R. Shapiro; Ryan A. Melnyk; Lucy R. O'Sullivan; Sophie Khorasani; Li Xiao; Jiatong Han; Jenifer Bush; Juli Carrillo; Naomi E. Pierce; Frederick M. Ausubel (Molecular Ecology, 2018)
Plant‐associated soil microbes are important mediators of plant defence responses to diverse above‐ground pathogen and insect challengers. For example, closely related strains of beneficial rhizosphere Pseudomonas spp. can induce systemic resistance ( ISR ), systemic susceptibility ( ISS ) or neither against the bacterial foliar pathogen Pseudomonas syringae pv. tomato DC 3000 ( Pto DC 3000). Using a model system composed of root‐associated Pseudomonas spp. strains, the foliar pathogen Pto DC 3000 and the herbivore Trichoplusia ni (cabbage looper), we found that rhizosphere‐associated Pseudomonas spp. that induce either ISS and ISR against Pto DC 3000 all increased resistance to herbivory by T. ni . We found that resistance to T. ni and resistance to Pto DC 3000 are quantitative metrics of the jasmonic acid ( JA )/salicylic acid ( SA ) trade‐off and distinct strains of rhizosphere‐associated Pseudomonas spp. have distinct effects on the JA / SA trade‐off. Using genetic analysis and transcriptional profiling, we provide evidence that treatment of Arabidopsis with Pseudomonas sp. CH 267, which induces ISS against bacterial pathogens, tips the JA / SA trade‐off towards JA ‐dependent defences against herbivores at the cost of a subset of SA ‐mediated defences against bacterial pathogens. In contrast, treatment of Arabidopsis with the ISR strain Pseudomonas sp. WCS 417 disrupts JA / SA antagonism and simultaneously primes plants for both JA ‐ and SA ‐mediated defences. Our findings show that ISS against the bacterial foliar pathogens triggered by Pseudomonas sp. CH 267 , which is a seemingly deleterious phenotype, may in fact be an adaptive consequence of increased resistance to herbivory. Our work shows that pleiotropic effects of microbiome modulation of plant defences are important to consider when using microbes to modify plant traits in agriculture.

Visco-elastic–Plastic Creep Constitutive Relation of Tunnels in Soft Schist - Y. Y. Zuo; L. Han; H. Hu; S. Y. Luo; Y. Zhang; X. M. Chen (Geotechnical and Geological Engineering, 2018)

Petrography and provenance of Upper Cretaceous – Palaeogene sandstones in the foreland basin system of Central Nepal - Bhupati Neupane; Yiwen Ju; Charlotte M. Allen; Prakash Das Ulak; Kui Han (International Geology Review, 2018)

iDNA at Sea: Recovery of Whale Shark (Rhincodon typus) Mitochondrial DNA Sequences from the Whale Shark Copepod (Pandarus rhincodonicus) Confirms Global Population Structure - Mark Meekan; Christopher M. Austin; Mun H. Tan; Nu-Wei V. Wei; Adam Miller; Simon J. Pierce; David Rowat; Guy Stevens; Tim K. Davies; Alessandro Ponzo; Han Ming Gan (Frontiers in Marine Science, 2017)

Congenic mice demonstrate the presence of QTLs conferring obesity and hypercholesterolemia on chromosome 1 in the TALLYHO mouse - Jacaline K. Parkman; James Denvir; Xia Mao; Kristy D. Dillon; Sofia Romero; Arnold M. Saxton; Jung Han Kim (Mammalian Genome, 2017)

Causes for the reversal of North Indian Ocean decadal sea level trend in recent two decades - U. Srinivasu; M. Ravichandran; Weiqing Han; S. Sivareddy; H. Rahman; Yuanlong Li; Shailesh Nayak (Climate Dynamics, 2017)

Fungal Denitrification Activity in Vertical Flow Constructed Wetlands as Impacted by Plant Species Richness, Carbon, Nitrogen and pH Amendments - W. L. Liu; C. B. Zhang; W. J. Han; M. Guan; S. Y. Liu; Y. Ge; J. Chang (Bulletin of Environmental Contamination and Toxicology, 2017)

Decline patterns and risk assessment of 10 multi-class pesticides in young sprout amaranth (Amaranthus mangostanus) under greenhouse growing conditions - In Kyung Kim; Sung-Woo Kim; A. M. Abd El-Aty; Md. Musfiqur Rahman; Md. Humayun Kabir; Han Sol Lee; Hyung Suk Chung; Ji Hoon Jeong; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Rapid recovery of nuclear and mitochondrial genes by genome skimming from Northern Hemisphere freshwater crayfish - Frederic Grandjean; Mun Hua Tan; Han Ming Gan; Yin Peng Lee; Tadashi Kawai; Robert J. Distefano; Martin Blaha; Angela J. Roles; Christopher M. Austin (Zoologica Scripta, 2017)
Molecular phylogenetics has benefited tremendously from the advent of next‐generation sequencing, enabling quick and cost‐effective recovery of whole mitogenomes via an approach referred to as ‘genome skimming’. Recently, genome skimming has been utilised to recover highly repetitive nuclear genes such as 18S and 28S ribosomal RNA genes that are useful for inferring deeper evolutionary relationships. To address some outstanding issues in the relationships among Northern Hemisphere freshwater crayfish (Astacoidea), we sequenced the partial genome of crayfish species from Asian, North American and European genera and report the successful recovery of whole mitogenome sequences in addition to three highly repetitive nuclear genes, namely histone H3, 18S and 28S ribosomal RNA . Consistent with some previous studies using short mt DNA and nuclear gene fragments, phylogenetic analyses based on the concatenation of recovered mitochondrial and/or nuclear sequences recovered the Asian cambarid lineage as basal to all astacids and North American cambarids, which conflicts with the current taxonomic classification based on morphological and reproduction‐related characters. Lastly, we show that complete H3, 18S and 28S ribosomal RNA genes can also be consistently recovered from a diverse range of animal taxa, demonstrating the potential wide utility of genome skimming for nuclear markers.

Signatures of polygenic adaptation associated with climate across the range of a threatened fish species with high genetic connectivity - Katherine A. Harrisson; Stephen J. Amish; Alexandra Pavlova; Shawn R. Narum; Marina Telonis‐Scott; Meaghan L. Rourke; Jarod Lyon; Zeb Tonkin; Dean M. Gilligan; Brett A. Ingram; Mark Lintermans; Han Ming Gan; et al. (Molecular Ecology, 2017)
Adaptive differences across species’ ranges can have important implications for population persistence and conservation management decisions. Despite advances in genomic technologies, detecting adaptive variation in natural populations remains challenging. Key challenges in gene–environment association studies involve distinguishing the effects of drift from those of selection and identifying subtle signatures of polygenic adaptation. We used paired‐end restriction site‐associated DNA sequencing data (6,605 biallelic single nucleotide polymorphisms; SNP s) to examine population structure and test for signatures of adaptation across the geographic range of an iconic Australian endemic freshwater fish species, the Murray cod Maccullochella peelii . Two univariate gene–association methods identified 61 genomic regions associated with climate variation. We also tested for subtle signatures of polygenic adaptation using a multivariate method (redundancy analysis; RDA ). The RDA analysis suggested that climate (temperature‐ and precipitation‐related variables) and geography had similar magnitudes of effect in shaping the distribution of SNP genotypes across the sampled range of Murray cod. Although there was poor agreement among the candidate SNP s identified by the univariate methods, the top 5% of SNP s contributing to significant RDA axes included 67% of the SNP s identified by univariate methods. We discuss the potential implications of our findings for the management of Murray cod and other species generally, particularly in relation to informing conservation actions such as translocations to improve evolutionary resilience of natural populations. Our results highlight the value of using a combination of different approaches, including polygenic methods, when testing for signatures of adaptation in landscape genomic studies.

Warming effects on permafrost ecosystem carbon fluxes associated with plant nutrients - Fei Li; Yunfeng Peng; Susan M. Natali; Kelong Chen; Tianfeng Han; Guibiao Yang; Jinzhi Ding; Dianye Zhang; Guanqin Wang; Jun Wang; Jianchun Yu; Futing Liu; et al. (Ecology, 2017)
Large uncertainties exist in carbon (C)‐climate feedback in permafrost regions, partly due to an insufficient understanding of warming effects on nutrient availabilities and their subsequent impacts on vegetation C sequestration. Although a warming climate may promote a substantial release of soil C to the atmosphere, a warming‐induced increase in soil nutrient availability may enhance plant productivity, thus offsetting C loss from microbial respiration. Here, we present evidence that the positive temperature effect on carbon dioxide ( CO 2 ) fluxes may be weakened by reduced plant nitrogen (N) and phosphorous (P) concentrations in a Tibetan permafrost ecosystem. Although experimental warming initially enhanced ecosystem CO 2 uptake, the increased rate disappeared after the period of peak plant growth during the early growing season, even though soil moisture was not a limiting factor in this swamp meadow ecosystem. We observed that warming did not significantly affect soil extractable N or P during the period of peak growth, but decreased both N and P concentrations in the leaves of dominant plant species, likely caused by accelerated plant senescence in the warmed plots. The attenuated warming effect on CO 2 assimilation during the late growing season was associated with lowered leaf N and P concentrations. These findings suggest that warming‐mediated nutrient changes may not always benefit ecosystem C uptake in permafrost regions, making our ability to predict the C balance in these warming‐sensitive ecosystems more challenging than previously thought.

Dissipation kinetics, pre-harvest residue limits, and hazard quotient assessments of pesticides flubendiamide and fluopicolide in Korean melon (Cucumis melo L. var. makuwa) grown under regulated conditions in plastic greenhouses - Md. Humayun Kabir; A. M. Abd El-Aty; Md. Musfiqur Rahman; Sung-Woo Kim; Han Sol Lee; Hyung Suk Chung; Jung Ah Do; Ji Hoon Jeong; Byung-Joon Chang; Moon Ik Chang; Ho-Chul Shin; Jae-Han Shim (Environmental Science and Pollution Research, 2017)

Widespread generalist clones are associated with range and niche expansion in allopolyploids of Pacific Northwest Hawthorns ( Crataegus L.) - J. M. Coughlan; S. Han; S. Stefanović; T. A. Dickinson (Molecular Ecology, 2017)
Range and niche expansion are commonly associated with transitions to asexuality, polyploidy and hybridity (allopolyploidy) in plants. The ability of asexual polyploids to colonize novel habitats may be due to widespread generalist clones, multiple ecologically specialized clones, or may be a neutral by‐product of multiple, independent origins of asexual polyploids throughout the range. We have quantified niche size and divergence for hawthorns of the Pacific Northwest using data from herbarium vouchers with known cytotypes. We find that all polyploid niches diverge from that of the diploid range, and allopolyploids have the broadest niches. Allotetraploids have the largest niche and the widest geographic distribution. We then assessed the genetic mechanism of range expansion by surveying the ecological and geographic distribution of genotypes within each cytotype from sites in which fine‐scale habitat assessments were completed. We find no isolation by either geographic or ecological distance in allopolyploids, suggesting high dispersal and colonization ability. In contrast, autotriploids and diploids show patterns of isolation by geographic distance. We also compared the geographic and ecological distributions of clonal genotypes with those of randomly drawn sites of the most widespread cytotype. We found that most clones are geographically widespread and occur in a variety of habitats. We interpret these findings to suggest that patterns of range and niche expansion in Pacific Northwest Hawthorns may stem from these widespread, ecologically generalist clones of hybrid origin.

Transgenic Mice Overexpressing the Divalent Metal Transporter 1 Exhibit Iron Accumulation and Enhanced Parkin Expression in the Brain - Cheng-Wu Zhang; Yee Kit Tai; Bing-Han Chai; Katherine C. M. Chew; Eng-Tat Ang; Fai Tsang; Bryce W. Q. Tan; Eugenia T. E. Hong; Abu Bakar Ali Asad; Kai-Hsiang Chuang; Kah-Leong Lim; Tuck Wah Soong (NeuroMolecular Medicine, 2017)

Identification of interspecific heterotic loci associated with agronomic traits in rice introgression lines carrying genomic fragments of Oryza glaberrima - Tondi Yacouba Nassirou; Wenchuang He; Caijin Chen; Adedze Y. M. Nevame; Athanase Nsabiyumva; Xilong Dong; Yilong Yin; Quanqin Rao; Wei Zhou; Han Shi; Wubin Zhao; Deming Jin (Euphytica, 2017)

Site Selection: a Case Study in the Identification of Optimal Cysteine Engineered Antibody Drug Conjugates - L. Nathan Tumey; Fengping Li; Brian Rago; Xiaogang Han; Frank Loganzo; Sylvia Musto; Edmund I. Graziani; Sujiet Puthenveetil; Jeffrey Casavant; Kimberly Marquette; Tracey Clark; Jack Bikker; et al. (The AAPS Journal, 2017)

Erratum to: Ocean atmosphere thermal decoupling in the eastern equatorial Indian ocean - Sudheer Joseph; M. Ravichandran; B. Praveen Kumar; Raju V. Jampana; Weiqing Han (Climate Dynamics, 2017)

Ocean atmosphere thermal decoupling in the eastern equatorial Indian ocean - Sudheer Joseph; M. Ravichandran; B. Praveen Kumar; Raju V. Jampana; Weiqing Han (Climate Dynamics, 2017)

Metabolites from the co-culture of nigranoic acid and Umbelopsis dimorpha SWUKD3.1410, an endophytic fungus from Kadsura angustifolia - L. Wang; D. Qin; K. Zhang; Q. Huang; S. Liu; M. J. Han; J. Y. Dong (Natural Product Research, 2017)

The Initial Symptom and Motor Progression in Spinocerebellar Ataxias - Lan Luo; Jie Wang; Raymond Y Lo; Karla P Figueroa; Stefan M Pulst; Pei-Hsin Kuo; Susan Perlman; George Wilmot; Christopher M Gomez; Jeremy D. Schmahmann; Henry Paulson; Vikram G Shakkottai; et al. (The Cerebellum, 2017)

Dissipation pattern and risk quotients assessment of amisulbrom in Korean melon cultivated in plastic house conditions - Md. Humayun Kabir; A. M. Abd El-Aty; Md. Musfiqur Rahman; Hyung Suk Chung; Han Sol Lee; Sun-Hyang Park; Fazil Hacımüftüoğlu; Byung-Joon Chang; Ho-Chul Shin; Jae-Han Shim (Environmental Monitoring and Assessment, 2017)

Magnetically recoverable TiO2-WO3 photocatalyst to oxidize bisphenol A from model wastewater under simulated solar light - S. Dominguez; M. Huebra; C. Han; P. Campo; M.N. Nadagouda; M.J. Rivero; I. Ortiz; D. D. Dionysiou (Environmental Science and Pollution Research, 2017)

N2O emissions from grain cropping systems: a meta-analysis of the impacts of fertilizer-based and ecologically-based nutrient management strategies - Zhen Han; M. Todd Walter; Laurie E. Drinkwater (Nutrient Cycling in Agroecosystems, 2017)

IGF-1 has sexually dimorphic, pleiotropic, and time-dependent effects on healthspan, pathology, and lifespan - Nicole M. Ashpole; Sreemathi Logan; Andriy Yabluchanskiy; Matthew C. Mitschelen; Han Yan; Julie A. Farley; Erik L. Hodges; Zoltan Ungvari; Anna Csiszar; Sixia Chen; Constantin Georgescu; Gene B. Hubbard; et al. (GeroScience, 2017)

Cryopreservation of Jerusalem artichoke cultivars using an improved droplet-vitrification method - Jin-Mei Zhang; Li Han; Xin-Xiong Lu; Gayle M. Volk; Xia Xin; Guang-Kun Yin; Juan-Juan He; Ling Wang; Xiao-Ling Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Biosynthesis of Veratrum californicum specialty chemicals in Camelina sativa seed - Megan M. Augustin; Ashutosh K. Shukla; Courtney M. Starks; Mark O’Neil-Johnson; Linna Han; Cynthia K. Holland; Toni M. Kutchan (Plant Biotechnology Reports, 2017)

Rhizobium hidalgonense sp. nov., a nodule endophytic bacterium of Phaseolus vulgaris in acid soil - Jun Yan; Hui Yan; Li Xue Liu; Wen Feng Chen; Xiao Xia Zhang; Myrthala M. Verástegui-Valdés; En Tao Wang; Xiao Zeng Han (Archives of Microbiology, 2017)

An overview on common aspects influencing the dissipation pattern of pesticides: a review - Waziha Farha; A. M. Abd El-Aty; Md. Musfiqur Rahman; Ho-Chul Shin; Jae-Han Shim (Environmental Monitoring and Assessment, 2016)

Persistent infiltration and pro-inflammatory differentiation of monocytes cause unresolved inflammation in brain arteriovenous malformation - Rui Zhang; Zhenying Han; Vincent Degos; Fanxia Shen; Eun-Jung Choi; Zhengda Sun; Shuai Kang; Michael Wong; Wan Zhu; Lei Zhan; Helen M. Arthur; S. Paul Oh; et al. (Angiogenesis, 2016)

Detrital zircon geochronology of Devonian quartzite from tectonic mélange in the Mianlue Suture Zone, Central China: provenance and tectonic implications - Xing-Zhong Ji; Li-Qiang Yang; M. Santosh; Nan Li; Chuang Zhang; Zhi-Chao Zhang; Ri Han; Zai-Chun Li; Chun-Jun Wu (International Geology Review, 2016)

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

A homozygous truncating mutation in PUS3 expands the role of tRNA modification in normal cognition - Ranad Shaheen; Lu Han; Eissa Faqeih; Nour Ewida; Eman Alobeid; Eric M. Phizicky; Fowzan S. Alkuraya (Human Genetics, 2016)

Autism spectrum disorder prevalence and associations with air concentrations of lead, mercury, and arsenic - Aisha S. Dickerson; Mohammad H. Rahbar; Amanda V. Bakian; Deborah A. Bilder; Rebecca A. Harrington; Sydney Pettygrove; Russell S. Kirby; Maureen S. Durkin; Inkyu Han; Lemuel A. Moyé; Deborah A. Pearson; Martha Slay Wingate; et al. (Environmental Monitoring and Assessment, 2016)

A combined liquid chromatography-triple-quadrupole mass spectrometry method for the residual detection of veterinary drugs in porcine muscle, milk, and eggs - Dan Zhang; Zee-Yong Park; Jin-A Park; Seong-Kwan Kim; Daun Jeong; Sang-Hyun Cho; Jae-Han Shim; Jin-Suk Kim; A. M. Abd El-Aty; Ho-Chul Shin (Environmental Monitoring and Assessment, 2016)

Characterisation of 12 microsatellite loci in the Vietnamese commercial clam Lutraria rhynchaena Jonas 1844 (Heterodonta: Bivalvia: Mactridae) through next-generation sequencing - Binh Thanh Thai; Mun Hua Tan; Yin Peng Lee; Han Ming Gan; Trang Thi Tran; Christopher M. Austin (Molecular Biology Reports, 2016)

Introgression of genes from bread wheat enhances the aluminium tolerance of durum wheat - Chang Han; Peng Zhang; Peter R. Ryan; Tina M. Rathjen; ZeHong Yan; Emmanuel Delhaize (Theoretical and Applied Genetics, 2016)

First comprehensive multi-tissue transcriptome of Cherax quadricarinatus (Decapoda: Parastacidae) reveals unexpected diversity of endogenous cellulase - Mun Hua Tan; Han Ming Gan; Huan You Gan; Yin Peng Lee; Larry J. Croft; Mark B. Schultz; Adam D. Miller; Christopher M. Austin (Organisms Diversity & Evolution, 2016)

Effects of light shading and climatic conditions on the metabolic behavior of flonicamid in red bell pepper - Da-I Jung; Waziha Farha; A. M. Abd El-Aty; Sung-Woo Kim; Md. Musfiqur Rahman; Jeong-Heui Choi; Md. Humayun Kabir; So Jeong Im; Young-Jun Lee; Lieu. T. B. Truong; Ho-Chul Shin; Geon-Jae Im; et al. (Environmental Monitoring and Assessment, 2016)

Stress-Induced Increases in Levels of Caspases in the Prefrontal Cortex in a Rat Model of PTSD - J. H. Zhang; M. Li; F. Han; Yu X. Shi (Neurophysiology, 2016)

Scaffolding during the cell cycle by A-kinase anchoring proteins - B. Han; W. J. Poppinga; M. Schmidt (Pflügers Archiv - European Journal of Physiology, 2015)

Analysis of DDT and its metabolites in soil and water samples obtained in the vicinity of a closed-down factory in Bangladesh using various extraction methods - M. N. U. Al Mahmud; Farzana Khalil; Md. Musfiqur Rahman; M. I. R. Mamun; Mohammad Shoeb; A. M. Abd El-Aty; Jong-Hyouk Park; Ho-Chul Shin; Nilufar Nahar; Jae-Han Shim (Environmental Monitoring and Assessment, 2015)

A hybrid modelling approach for assessing solar radiation - M. A. Shamim; M. Bray; R. Remesan; D. Han (Theoretical and Applied Climatology, 2015)

Tuna and swordfish catch in the U.S. northwest Atlantic longline fishery in relation to mesoscale eddies - Ango C. Hsu; Andre M. Boustany; Jason J. Roberts; Jui‐Han Chang; Patrick N. Halpin (Fisheries Oceanography, 2015)

Effect of a Rho Kinase Inhibitor on Cognitive Impairment Induced by Chronic Cerebral Hypoperfusion in Rats - Q. Zhang; J.-J. Zhang; Zh.-M. Han (Neurophysiology, 2015)

QTL mapping of adult-plant resistance to stripe rust in wheat line P9897 - X. L. Zhou; D. J. Han; X. M. Chen; J. M. Mu; W. B. Xue; Q. D. Zeng; Q. L. Wang; L. L. Huang; Z. S. Kang (Euphytica, 2015)

Structural and stratigraphic characteristics on distal parts of the outer fold and thrust belt of southern Niger Delta, Nigeria - E. K. Nyantakyi; Tao Li; WangShui Hu; J. K. Borkloe; Songze Li; M. Han Cheng (Arabian Journal of Geosciences, 2015)

The Fresnel–Fizeau effect and the atmospheric time delay in geodetic VLBI - S. M. Kopeikin; W.-B. Han (Journal of Geodesy, 2015)

Identification of QTL for adult plant resistance to stripe rust in Chinese wheat landrace Caoxuan 5 - X. L. Zhou; Y. Zhang; Q. D. Zeng; X. M. Chen; D. J. Han; L. L. Huang; Z. S. Kang (Euphytica, 2015)

The Domain II S4-S5 Linker in Nav1.9: A Missense Mutation Enhances Activation, Impairs Fast Inactivation, and Produces Human Painful Neuropathy - Chongyang Han; Yang Yang; Bianca T. A. de Greef; Janneke G. J. Hoeijmakers; Monique M. Gerrits; Camiel Verhamme; Jian Qu; Giuseppe Lauria; Ingemar S. J. Merkies; Catharina G. Faber; Sulayman D. Dib-Hajj; Stephen G. Waxman (NeuroMolecular Medicine, 2015)

Carbon stock and its responses to climate change in C entral A sia - Chaofan Li; Chi Zhang; Geping Luo; Xi Chen; Bagila Maisupova; Abdullo A. Madaminov; Qifei Han; Bekmamat M. Djenbaev (Global Change Biology, 2015)
Central Asia has a land area of 5.6 × 10 6 km 2 and contains 80–90% of the world's temperate deserts. Yet it is one of the least characterized areas in the estimation of the global carbon (C) stock/balance. This study assessed the sizes and spatiotemporal patterns of C pools in Central Asia using both inventory (based on 353 biomass and 284 soil samples) and process‐based modeling approaches. The results showed that the C stock in Central Asia was 31.34–34.16 Pg in the top 1‐m soil with another 10.42–11.43 Pg stored in deep soil (1–3 m) of the temperate deserts. They amounted to 18–24% of the global C stock in deserts and dry shrublands. The C stock was comparable to that of the neighboring regions in Eurasia or major drylands around the world (e.g. Australia). However, 90% of Central Asia C pool was stored in soil, and the fraction was much higher than in other regions. Compared to hot deserts of the world, the temperate deserts in Central Asia had relatively high soil organic carbon density. The C stock in Central Asia is under threat from dramatic climate change. During a decadal drought between 1998 and 2008, which was possibly related to protracted La Niña episodes, the dryland lost approximately 0.46 Pg C from 1979 to 2011. The largest C losses were found in northern Kazakhstan, where annual precipitation declined at a rate of 90 mm decade −1 . The regional C dynamics were mainly determined by changes in the vegetation C pool, and the SOC pool was stable due to the balance between reduced plant‐derived C influx and inhibited respiration.

Influence of Constant Temperature on Development and Reproduction of Encarsia guadeloupae Viggiani (Hymenoptera: Aphelinidae), a Parasitoid of the Spiraling Whitefly Aleurodicus dispersus Russell (Hemiptera: Aleyrodidae) - J Y Chen; L M Niu; L Li; D Y Han; Y G Fu (Neotropical Entomology, 2015)

Gastric cancer in three relatives of a patient with a biallelic IL12RB1 mutation - Ingrid P. Vogelaar; Rachel S. van der Post; Esther van de Vosse; J. Han J. M. van Krieken; Nicoline Hoogerbrugge; Marjolijn J. L. Ligtenberg; Encarna Gómez García (Familial Cancer, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Functionality and prevalence of trehalose‐based oligosaccharides as novel compatible solutes in ascospores of N eosartorya fischeri ( A spergillus fischeri ) and other fungi - Timon T. Wyatt; M. Richard van Leeuwen; Elena A. Golovina; Folkert A. Hoekstra; Eric J. Kuenstner; Edward A. Palumbo; Nicole L. Snyder; Cobus Visagie; Alex Verkennis; John E. Hallsworth; Han A.B. Wösten; Jan Dijksterhuis (Environmental Microbiology, 2015)
Summary Ascospores of N eosartorya , B yssochlamys and T alaromyces can be regarded as the most stress‐resistant eukaryotic cells. They can survive exposure at temperatures as high as 85° C for 100 min or more. N eosartorya fischeri ascospores are more viscous and more resistant to the combined stress of heat and desiccation than the ascospores of T alaromyces macrosporus which contain predominantly trehalose. These ascospores contain trehalose‐based oligosaccharides ( TOS ) that are novel compatible solutes, which are accumulated to high levels. These compounds are also found in other members of the genus N eosartorya and in some other genera within the order Eurotiales that also include B yssochlamys and T alaromyces . The presence of oligosaccharides was observed in species that had a relatively high growth temperature. TOS glasses have a higher glass transition temperature ( T g ) than trehalose, and they form a stable glass with crystallizing molecules, such as mannitol. Our data indicate that TOS are important for prolonged stabilization of cells against stress. The possible unique role of these solutes in protection against dry heat conditions is discussed.

Characterization of the microbial community in different types of Daqu samples as revealed by 16S rRNA and 26S rRNA gene clone libraries - Xiao-Wei Zheng; Zheng Yan; M. J. Robert Nout; Teun Boekhout; Bei-Zhong Han; Marcel H. Zwietering; Eddy J. Smid (World Journal of Microbiology and Biotechnology, 2015)

Polarization of excitation light influences molecule counting in single-molecule localization microscopy - Ye Chen; Han Lin; Mandy J. Ludford-Menting; Andrew H. Clayton; Min Gu; Sarah M. Russell (Histochemistry and Cell Biology, 2015)

Evaluating the causal basis of ecological success within the scleractinia: an integral projection model approach - Peter J. Edmunds; Scott C. Burgess; Hollie M. Putnam; Marissa L. Baskett; Lorenzo Bramanti; Nick S. Fabina; Xueying Han; Michael P. Lesser; Joshua S. Madin; Christopher B. Wall; Denise M. Yost; Ruth D. Gates (Marine Biology, 2014)

Health Literacy and Pap Testing in Insured Women - K. M. Mazor; A. E. Williams; D. W. Roblin; B. Gaglio; S. L. Cutrona; M. E. Costanza; P. K. J. Han; J. L. Wagner; H. Fouayzi; T. S. Field (Journal of Cancer Education, 2014)

Characterization and molecular mapping of stripe rust resistance gene Yr61 in winter wheat cultivar Pindong 34 - X. L. Zhou; D. J. Han; X. M. Chen; H. L. Gou; S. J. Guo; L. Rong; Q. L. Wang; L. L. Huang; Z. S. Kang (Theoretical and Applied Genetics, 2014)

Ecotoxicity of triphenyltin on the marine copepod Tigriopus japonicus at various biological organisations: from molecular to population-level effects - Andy Xianliang Yi; Jeonghoon Han; Jae-Seong Lee; Kenneth M. Y. Leung (Ecotoxicology, 2014)

Trajectory of overall health from self-report and factors contributing to health declines among cancer survivors - Jessica L. Petrick; Randi E. Foraker; Anna M. Kucharska-Newton; Bryce B. Reeve; Elizabeth A. Platz; Sally C. Stearns; Xuesong Han; B. Gwen Windham; Debra E. Irwin (Cancer Causes & Control, 2014)

Limited diagnostic value of microsatellite instability associated pathology features in colorectal cancer - Paul G. van Putten; Margot G. F. van Lier; Mariska Hage; Katharina Biermann; Reinier H. van Rijssel; Pieter J. Westenend; Hans Morreau; Ewout W. Steyerberg; Winand N. M. Dinjens; Ernst J. Kuipers; Monique E. van Leerdam; J. Han van Krieken (Familial Cancer, 2014)

Effects of watershed land use on sources and nutritional value of particulate organic matter in temperate headwater streams - Yue Han Lu; Elizabeth A. Canuel; James E. Bauer; R. M. Chambers (Aquatic Sciences, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Synthesis of water soluble copper(II) complexes: crystal structures, DNA binding, oxidative DNA cleavage, and in vitro anticancer studies - Tan Yi Han; Teoh Siang Guan; Muhammad Adnan Iqbal; Rosenani A. Haque; K. Sharmila Rajeswari; Mohamed B. Khadeer Ahamed; A. M. S. Abdul Majid (Medicinal Chemistry Research, 2014)

No fitness cost of glyphosate resistance endowed by massive EPSPS gene amplification in Amaranthus palmeri - Martin M. Vila-Aiub; Sou S. Goh; Todd A. Gaines; Heping Han; Roberto Busi; Qin Yu; Stephen B. Powles (Planta, 2014)

Cellular mechanisms in intermittent hypoxia-induced cardiac damage in vivo - Qian Han; Sze C. Yeung; Mary S. M. Ip; Judith C. W. Mak (Journal of Physiology and Biochemistry, 2014)

Optimization of sono-assisted dilute sulfuric acid process for simultaneous pretreatment and saccharification of rice straw - M. S. U. Rehman; I. Kim; K. H. Kim; J.-I. Han (International Journal of Environmental Science and Technology, 2014)

Keratinocyte growth factor and thiazolidinediones and linolenic acid differentiate characterized mammary fat pad adipose stem cells isolated from prepubertal Korean black goat to epithelial and adipogenic lineage - A. M. M. T Reza; S. Shiwani; N. K. Singh; J. D. Lohakare; S. J. Lee; D. K. Jeong; J. Y. Han; D. Rengaraj; B. W. Lee (In Vitro Cellular & Developmental Biology - Animal, 2014)

Molecular mapping of a stripe rust resistance gene in wheat cultivar Wuhan 2 - X. L. Zhou; D. J. Han; H. L. Gou; Q. L. Wang; Q. D. Zeng; F. P. Yuan; G. M. Zhan; L. L. Huang; Z. S. Kang (Euphytica, 2014)
Stripe rust (or yellow rust), caused by Puccinia striiformis f. sp. tritici , is one of the most destructive diseases of wheat worldwide. Growing resistant cultivars is the best approach to control the disease. To identify and map genes for stripe rust resistance in wheat cultivar ‘Wuhan 2', an F 2 population was developed from a cross between the cultivar and susceptible cultivar Mingxian 169. The parents, 179 F 2 plants and their derived F 2:3 lines were evaluated for responses to Chinese races CYR30 and CYR31 of the pathogen in a greenhouse. A recessive gene for resistance was identified. DNA bulked segregant analysis was applied and resistance gene analog polymorphism (RGAP) and simple sequence repeat (SSR) techniques were used to identify molecular markers linked to the resistance gene. A genetic map consisting of five RGAP and six SSR markers was constructed. The recessive gene, designated Yrwh2 , was located on the short arm of chromosome 3B and flanked by SSR markers Xwmc540 and Xgwm566 at 5.9 and 10.0 cM, respectively. The chromosomal location of the resistance gene and its close marker suggest that the locus is different from previously reported stripe rust resistance genes Yr30 , QYr.ucw - 3BS , Yrns - B1 , YrRub and QYrex.wgp - 3BL previously mapped to chromosome 3B. Yrwh2 and its closely linked markers are potentially useful for developing stripe rust resistance wheat cultivars if used in combination with other genes.

Identification of Quantitative Trait Loci (QTLs) for Fruit Quality Traits in Apple - Sarah M. Potts; M. Awais Khan; Yuepeng Han; Mosbah M. Kushad; Schuyler S. Korban (Plant Molecular Biology Reporter, 2014)

The value of multiple earthquake missions: the EEFIT L’Aquila Earthquake experience - T. Rossetto; D. D’Ayala; F. Gori; R. Persio; J. Han; V. Novelli; S. M. Wilkinson; D. Alexander; M. Hill; S. Stephens; S. Kontoe; G. Elia; et al. (Bulletin of Earthquake Engineering, 2014)

A Novel Approach to Evaluate the Pharmacokinetic Biocomparability of a Monoclonal Antibody Derived from Two Different Cell Lines Using Simultaneous Crossover Design - Chao Han; Thomas S. McIntosh; Brian J. Geist; Trina Jiao; Thomas A. Puchalski; Kenneth M. Goldberg; Tong-Yuan Yang; Charles E. Pendley; Honghui Zhou; Hugh M. Davis (The AAPS Journal, 2014)

Isolation and characterization of two VpYABBY genes from wild Chinese Vitis pseudoreticulata - J. Xiang; R. Q. Liu; T. M. Li; L. J. Han; Y. Zou; T. F. Xu; J. Y. Wei; Y. J. Wang; Y. Xu (Protoplasma, 2013)

Comprehensive hormone profiling of the developing seeds of four grain legumes - Susan M. H. Slater; Hai Ying Yuan; Monika M. Lulsdorf; Albert Vandenberg; L. Irina Zaharia; Xiumei Han; Suzanne R. Abrams (Plant Cell Reports, 2013)

Challenge of weed risk assessment (WRA) for ecological restoration in China: The case of Rhus typhina L. and the new officially released weed risk assessment system - G. M. Wang; J. C. Yang; C. D. Jiang; G. M. Jiang; J. B. Yu; H. B. Shao; G. X. Han; Y. J. Gao (Plant Biosystems, 2013)

Effects of total replacement of dietary fish oil on growth performance and fatty acid compositions of hybrid tilapia (Oreochromis niloticus × O. aureus) - C.-Y. Han; Q.-M. Zheng; L.-N. Feng (Aquaculture International, 2013)

Dissipation pattern and pre-harvest residue limit of abamectin in perilla leaves - Md. Musfiqur Rahman; Tae Woong Na; A. M. Abd El-Aty; Jong-Hyouk Park; M. N. U. Al Mahmud; Angel Yang; Ki Hun Park; Jae-Han Shim (Environmental Monitoring and Assessment, 2013)

Non-trophic Interactions Control Benthic Producers on Intertidal Flats - Serena Donadi; Joëlle Westra; Ellen J. Weerman; Tjisse van der Heide; Els M. van der Zee; Johan van de Koppel; Han Olff; Theunis Piersma; Henk W. van der Veer; Britas Klemens Eriksson (Ecosystems, 2013)

Microbial diversity and dynamics of microbial communities during back-slop soaking of soybeans as determined by PCR–DGGE and molecular cloning - Yinzhuo Yan; Judith Wolkers-Rooijackers; M. J. Robert Nout; Beizhong Han (World Journal of Microbiology and Biotechnology, 2013)

Utilization of Hyperinsulinemia Euglycemia and Intravenous Fat Emulsion Following Poison Center Recommendations - Michael A. Darracq; Stephen L. Thornton; Han M. Do; Dennis Bok; Richard F. Clark; F. Lee Cantrell (Journal of Medical Toxicology, 2013)

Biosorption of methylene blue from aqueous solutions by Typha angustata phytomass - M. Saif Ur Rehman; J.-I. Han (International Journal of Environmental Science and Technology, 2013)

Whole exome sequencing in dominant cataract identifies a new causative factor, CRYBA2, and a variety of novel alleles in known genes - Linda M. Reis; Rebecca C. Tyler; Sanaa Muheisen; Victor Raggio; Leonardo Salviati; Dennis P. Han; Deborah Costakos; Hagith Yonath; Sarah Hall; Patricia Power; Elena V. Semina (Human Genetics, 2013)

Photocatalytic degradation of contaminants of concern with composite NF-TiO2 films under visible and solar light - H. Barndõk; M. Peláez; C. Han; W. E. Platten; P. Campo; D. Hermosilla; A. Blanco; D. D. Dionysiou (Environmental Science and Pollution Research, 2013)

Reconstructing the origin and dispersal patterns of village chickens across E ast A frica: insights from autosomal markers - J. M. Mwacharo; K. Nomura; H. Hanada; J. L. Han; T. Amano; O. Hanotte (Molecular Ecology, 2013)
Unravelling the genetic history of any livestock species is central to understanding the origin, development and expansion of agricultural societies and economies. Domestic village chickens are widespread in Africa. Their close association with, and reliance on, humans for long‐range dispersal makes the species an important biological marker in tracking cultural and trading contacts between human societies and civilizations across time. Archaezoological and linguistic evidence suggest a complex history of arrival and dispersion of the species on the continent, with mitochondrial DNA (mt DNA ) D‐loop analysis revealing the presence of five distinct haplogroups in East African village chickens. It supports the importance of the region in understanding the history of the species and indirectly of human interactions. Here, through a detailed analysis of 30 autosomal microsatellite markers genotyped in 657 village chickens from four East African countries (Kenya, Uganda, Ethiopia and Sudan), we identify three distinct autosomal gene pools ( I , II and III ). Gene pool I is predominantly found in Ethiopia and Sudan, while II and III occur in both Kenya and Uganda. A gradient of admixture for gene pools II and III between the Kenyan coast and Uganda's hinterland ( P = 0.001) is observed, while gene pool I is clearly separated from the other two. We propose that these three gene pools represent genetic signatures of separate events in the history of the continent that relate to the arrival and dispersal of village chickens and humans across the region. Our results provide new insights on the history of chicken husbandry which has been shaped by terrestrial and maritime contacts between ancient and modern civilizations in Asia and East Africa.

Evaluation of organic contamination in urban groundwater surrounding a municipal landfill, Zhoukou, China - D. M. Han; X. X. Tong; M. G. Jin; Emily Hepburn; C. S. Tong; X. F. Song (Environmental Monitoring and Assessment, 2013)

A new caryolane sesquiterpene from Heteropappus altaicus (Willd.) Novopokr. - H. Huang; X.J. Gao; J. Liu; S. Li; Y.F. Han; B.C. Zhou; M. Xia (Natural Product Research, 2013)

Study of chloropropanols in soy sauce by gas chromatography-triple quadrupole mass spectrometry with coupled column separation without derivatisation - X.-M. Xu; H.-W. Wu; H.-L. He; B.-F. Huang; J.-L. Han; Y.-P. Ren (Food Additives & Contaminants: Part A, 2013)

Predator guild does not influence orangutan alarm call rates and combinations - Adriano R. Lameira; Han de Vries; Madeleine E. Hardus; Cedric P. A. Hall; Tatang Mitra-Setia; Berry M. Spruijt; Arik Kershenbaum; Elisabeth H. M. Sterck; Maria van Noordwijk; Carel van Schaik; Serge A. Wich (Behavioral Ecology and Sociobiology, 2013)

Absence of induced resistance in Agaricus bisporus against Lecanicillium fungicola - Roeland L. Berendsen; Niek Schrier; Stefanie I. C. Kalkhove; Luis G. Lugones; Johan J. P. Baars; Carolien Zijlstra; Marjanne de Weerdt; Han A. B. Wösten; Peter A. H. M. Bakker (Antonie van Leeuwenhoek, 2013)

Application of MT3DMS and Geographic Information System to Evaluation of Groundwater Contamination in the Sherwood Sandstone Aquifer, UK - Han Zhang; Wen Lai Xu; Kevin M. Hiscock (Water, Air, & Soil Pollution, 2013)

Erratum to: The interaction of carbon dioxide and hypoxia in the control of cerebral blood flow - Alexandra Mardimae; Dahlia Y. Balaban; Matthew A. Machina; Anne Battisti-Charbonney; Jay S. Han; Rita Katznelson; Leonid L. Minkovich; Ludwik Fedorko; Patricia M. Murphy; Marcin Wasowicz; Finola Naughton; Massimiliano Meineri; et al. (Pflügers Archiv - European Journal of Physiology, 2013)

Cross‐habitat interactions among bivalve species control community structure on intertidal flats - Serena Donadi; Tjisse van der Heide; Els M. van der Zee; Johan S. Eklöf; Johan van de Koppel; Ellen J. Weerman; Theunis Piersma; Han Olff; Britas Klemens Eriksson (Ecology, 2013)
Increasing evidence shows that spatial interactions between sedentary organisms can structure communities and promote landscape complexity in many ecosystems. Here we tested the hypothesis that reef‐forming mussels ( Mytilus edulis L.), a dominant intertidal ecosystem engineer in the Wadden Sea, promote abundances of the burrowing bivalve Cerastoderma edule L. (cockle) in neighboring habitats at relatively long distances coastward from mussel beds. Field surveys within and around three mussel beds showed a peak in cockle densities at 50–100 m toward the coast from the mussel bed, while cockle abundances elsewhere in the study area were very low. Field transplantation of cockles showed higher survival of young cockles (2–3 years old) and increased spat fall coastward of the mussel bed compared to within the bed and to areas without mussels, whereas growth decreased within and coastward of the mussel bed. Our measurements suggest that the observed spatial patterns in cockle numbers resulted from (1) inhibition effects by the mussels close to the beds due to preemptive algal depletion and deteriorated sediment conditions and (2) facilitation effects by the mussels farther away from the beds due to reduction of wave energy. Our results imply that these spatial, scale‐dependent interactions between reef‐forming ecosystem engineers and surrounding communities of sedentary benthic organisms can be an important determinant of the large‐scale community structure in intertidal ecosystems. Understanding this interplay between neighboring communities of sedentary species is therefore essential for effective conservation and restoration of soft‐bottom intertidal communities.

TRAIL death receptor 4 signaling via lysosome fusion and membrane raft clustering in coronary arterial endothelial cells: evidence from ASM knockout mice - Xiang Li; Wei-Qing Han; Krishna M. Boini; Min Xia; Yang Zhang; Pin-Lan Li (Journal of Molecular Medicine, 2013)

Enhanced drought and salt tolerance by expression of AtGSK1 gene in poplar - M. S. Han; E. W. Noh; S. H. Han (Plant Biotechnology Reports, 2013)

Hippopotamus and livestock grazing: influences on riparian vegetation and facilitation of other herbivores in the Mara Region of Kenya - Erustus M. Kanga; Joseph O. Ogutu; Hans-Peter Piepho; Han Olff (Landscape and Ecological Engineering, 2013)

Histidine ligand variants of a flavo-diiron protein: effects on structure and activities - Han Fang; Jonathan D. Caranto; Rosalinda Mendoza; Alexander B. Taylor; P. John Hart; Donald M. Kurtz (JBIC Journal of Biological Inorganic Chemistry, 2012)

Testing the metabolic theory of ecology - Charles A. Price; Joshua S Weitz; Van M. Savage; James Stegen; Andrew Clarke; David A. Coomes; Peter S. Dodds; Rampal S. Etienne; Andrew J. Kerkhoff; Katherine McCulloh; Karl J. Niklas; Han Olff; et al. (Ecology Letters, 2012)
The metabolic theory of ecology (MTE) predicts the effects of body size and temperature on metabolism through considerations of vascular distribution networks and biochemical kinetics. MTE has also been extended to characterise processes from cellular to global levels. MTE has generated both enthusiasm and controversy across a broad range of research areas. However, most efforts that claim to validate or invalidate MTE have focused on testing predictions. We argue that critical evaluation of MTE also requires strong tests of both its theoretical foundations and simplifying assumptions. To this end, we synthesise available information and find that MTE's original derivations require additional assumptions to obtain the full scope of attendant predictions. Moreover, although some of MTE's simplifying assumptions are well supported by data, others are inconsistent with empirical tests and even more remain untested. Further, although many predictions are empirically supported on average, work remains to explain the often large variability in data. We suggest that greater effort be focused on evaluating MTE's underlying theory and simplifying assumptions to help delineate the scope of MTE, generate new theory and shed light on fundamental aspects of biological form and function.

Co-expression of soybean Dicer-like genes in response to stress and development - Shaun J. Curtin; Michael B. Kantar; Han W. Yoon; Adam M. Whaley; Jessica A. Schlueter; Robert M. Stupar (Functional & Integrative Genomics, 2012)

The interaction of carbon dioxide and hypoxia in the control of cerebral blood flow - Alexandra Mardimae; Dahlia Y. Balaban; Matthew A. Machina; Jay S. Han; Rita Katznelson; Leonid L. Minkovich; Ludwik Fedorko; Patricia M. Murphy; Marcin Wasowicz; Finola Naughton; Massimiliano Meineri; Joseph A. Fisher; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Targeting CreERT2 expression to keratin 8-expressing murine simple epithelia using bacterial artificial chromosome transgenesis - Li Zhang; Boyu Zhang; Sang Jun Han; Amy N. Shore; Jeffrey M. Rosen; Francesco J. DeMayo; Li Xin (Transgenic Research, 2012)

Specific herbivore‐induced volatiles defend plants and determine insect community composition in the field - Y. Xiao; Q. Wang; M. Erb; T. C. J. Turlings; L. Ge; L. Hu; J. Li; X. Han; T. Zhang; J. Lu; G. Zhang; Y. Lou (Ecology Letters, 2012)
In response to insect attack, plants release complex blends of volatile compounds. These volatiles serve as foraging cues for herbivores, predators and parasitoids, leading to plant‐mediated interactions within and between trophic levels. Hence, plant volatiles may be important determinants of insect community composition. To test this, we created rice lines that are impaired in the emission of two major signals, S‐ linalool and ( E )‐β‐caryophyllene. We found that inducible S‐ linalool attracted predators and parasitoids as well as chewing herbivores, but repelled the rice brown planthopper Nilaparvata lugens , a major pest. The constitutively produced ( E )‐β‐caryophyllene on the other hand attracted both parasitoids and planthoppers, resulting in an increased herbivore load. Thus, silencing either signal resulted in specific insect assemblages in the field, highlighting the importance of plant volatiles in determining insect community structures. Moreover, the results imply that the manipulation of volatile emissions in crops has great potential for the control of pest populations.

Neuroglial Expression of the MHCI Pathway and PirB Receptor Is Upregulated in the Hippocampus with Advanced Aging - Heather D. VanGuilder Starkey; Colleen A. Van Kirk; Georgina V. Bixler; Caesar G. Imperio; Vijay P. Kale; Jacob M. Serfass; Julie A. Farley; Han Yan; Junie P. Warrington; Song Han; Matthew Mitschelen; William E. Sonntag; et al. (Journal of Molecular Neuroscience, 2012)

Non-steroidal anti-inflammatory drugs, acetaminophen, and risk of skin cancer in the Nurses’ Health Study - J. M. Jeter; J. Han; M. E. Martinez; D. S. Alberts; A. A. Qureshi; D. Feskanich (Cancer Causes & Control, 2012)

Agronomic Considerations for Sweet Sorghum Biofuel Production in the South-Central USA - K. J. Han; W. D. Pitman; M. W. Alison; D. L. Harrell; H. P. Viator; M. E. McCormick; K. A. Gravois; M. Kim; D. F. Day (BioEnergy Research, 2012)

Genetic Diversity and Characterization of a Core Collection of Malus Germplasm Using Simple Sequence Repeats (SSRs) - Sarah M. Potts; Yuepeng Han; M. Awais Khan; Mosbah M. Kushad; A. Lane Rayburn; Schuyler S. Korban (Plant Molecular Biology Reporter, 2012)

Stability and Change of Social Relationship Quality in Captive Chimpanzees (Pan troglodytes) - Sonja E. Koski; Han de Vries; Annette van de Kraats; Elisabeth H. M. Sterck (International Journal of Primatology, 2012)

An invasive grass shows colonization advantages over native grasses under conditions of low resource availability - Yi Han; Yvonne M. Buckley; Jennifer Firn (Plant Ecology, 2012)

Multi-scale Structural and Tensile Mechanical Response of Annulus Fibrosus to Osmotic Loading - Woojin M. Han; Nandan L. Nerurkar; Lachlan J. Smith; Nathan T. Jacobs; Robert L. Mauck; Dawn M. Elliott (Annals of Biomedical Engineering, 2012)

Spatially Extended Habitat Modification by Intertidal Reef-Building Bivalves has Implications for Consumer-Resource Interactions - Els M. van der Zee; Tjisse van der Heide; Serena Donadi; Johan S. Eklöf; Britas Klemens Eriksson; Han Olff; Henk W. van der Veer; Theunis Piersma (Ecosystems, 2012)

Look before you leap - individual variation in social vigilance shapes socio-spatial group properties in an agent-based model - Ellen Evers; Han de Vries; Berry M. Spruijt; Elisabeth H. M. Sterck (Behavioral Ecology and Sociobiology, 2012)

Case report: a p.C618S RET proto-oncogene germline mutation in a large Chinese pedigree with familial medullary thyroid carcinoma - X.-P. Qi; R.-B. Ying; J.-M. Ma; W.-T. Liu; Z.-F. Du; J. Fei; C.-P. Yang; Q.-Z. Song; H.-Y. Jin; Z.-G. Chen; J.-S. Han; J.-Q. Wang; et al. (Familial Cancer, 2012)

Managing invasions at the cost of native habitat? An experimental test of the impact of fire on the invasion of Chromolaena odorata in a South African savanna - Mariska te Beest; Joris P. G. M. Cromsigt; Johan Ngobese; Han Olff (Biological Invasions, 2012)

Application of tyramide signal amplification‐fluorescence in situ hybridisation and flow cytometry to detection of Heterosigma akashiwo (Raphidophyceae) in natural waters - J Lee; T Katano; M Chang; M‐S Han (New Zealand Journal of Marine and Freshwater Research, 2012)
We developed protocols to analyse the cell cycle of Heterosigma akashiwo in the natural phytoplankton assemblage using tyramide signal amplification‐fluorescence in situ hybridisation (TSA‐FISH) and flow cytometry. We determined the optimum probe and formamide concentrations for the species‐specific TSA‐FISH probe to be 0.5 ng µL −1 and 40%, respectively. The probe did not hybridise to non‐target phytoplankton including Chattonella sp., which is closely related to Heterosigma and has high sequence similarity to it. We could successfully identify G1‐ and G2‐phase cells and the diel cell cycle of H. akashiwo not only in the laboratory but also in the field after TSA‐FISH. These results demonstrate that TSA‐FISH for H. akashiwo in natural coastal waters could serve as a powerful tool for understanding their bloom mechanism using flow cytometry.

Effects of Erosion from Mounds of Different Termite Genera on Distinct Functional Grassland Types in an African Savannah - Cleo M. Gosling; Joris P. G. M. Cromsigt; Nokukhanya Mpanza; Han Olff (Ecosystems, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Prevalence and different characteristics of two serotypes of Streptococcus parauberis isolated from the farmed olive flounder, Paralichthys olivaceus (Temminck and Schlegel), in Korea - S Y Han; B K Kang; B J Kang; S P Shin; B H Soen; J M Kim; J H Kim; C H Choresca; J E Han; J W Jun; S C Park (Journal of Fish Diseases, 2011)
The prevalence of two serotypes of Streptococcus parauberis isolated from the olive flounder, Paralichthys olivaceus , was evaluated in a total of 29 isolates between 2003 and 2010 in Korea. Streptococcus parauberis isolates were divided into two serologically distinct types (serotype 1 and serotype 2), except for one strain (S1091), using an agglutination assay with rabbit antiserum, and serotype 1 was identified as the dominant type (24 of 29 isolates) in this study. To identify the characteristics of the two serotypes of S. parauberis , we conducted a biochemical test using the API 20 Strep kit, a transmission electron microscopy (TEM) assay, sequence analysis of 16S‐23S rRNA intergenic spacer region (ISR) and a pathogenicity test. In TEM, both serotypes possessed polysaccharide capsule layers around the cell surface when bacterial cells were treated with a homologous serotype of rabbit antiserum. However, we were unable to discriminate serotype‐specific biochemical characteristics and genetic characteristics of 16S‐23S rRNA ISR between the two serotypes. In the pathogenicity test, the serotype 1 strains induced significantly higher mortality than the serotype 2 strains in olive flounder when experimentally inoculated via the intraperitoneal route.

Multi-dimensional MR spectroscopy: towards a better understanding of hepatic encephalopathy - Manoj K. Sarma; Amir Huda; Rajakumar Nagarajan; Charles H. Hinkin; Neil Wilson; Rakesh K. Gupta; Enrique Frias-Martinez; James Sayre; Barry Guze; Steven-Huy Han; M. Albert Thomas (Metabolic Brain Disease, 2011)

Individual and combined effects of multiple pathogens on Pacific treefrogs - John M. Romansic; Pieter T. J. Johnson; Catherine L. Searle; James E. Johnson; Tate S. Tunstall; Barbara A. Han; Jason R. Rohr; Andrew R. Blaustein (Oecologia, 2011)

Synthesis of an integrated biorefinery via the C–H–O ternary diagram - Douglas Han Shin Tay; Denny Kok Sum Ng; Houssein Kheireddine; Mahmoud M. El-Halwagi (Clean Technologies and Environmental Policy, 2011)

Species-level correlates of susceptibility to the pathogenic amphibian fungus Batrachochytrium dendrobatidis in the United States - Betsy A. Bancroft; Barbara A. Han; Catherine L. Searle; Lindsay M. Biga; Deanna H. Olson; Lee B. Kats; Joshua J. Lawler; Andrew R. Blaustein (Biodiversity and Conservation, 2011)

Severe anisakiasis and cutaneous myxoma in a California yellowtail, Seriola lalandi Valenciennes - M Keller; S Han; K Snekvik (Journal of Fish Diseases, 2011)

Health Risk Assessment of Organochlorine Contaminants in Fish from a Major Lake (Baiyangdian Lake) in North China - G. H. Dai; X. H. Liu; G. Liang; M. Z. Xu; X. Han; L. Shi (Bulletin of Environmental Contamination and Toxicology, 2011)

Increase in Rubisco activity and gene expression due to elevated temperature partially counteracts ultraviolet radiation–induced photoinhibition in the marine diatom Thalassiosira weissflogii - E. Walter Helbling; Anita G. J. Buma; Peter Boelen; Han J. van der Strate; M. Valeria Fiorda Giordanino; Virginia E. Villafañe (Limnology and Oceanography, 2011)
We performed outdoor experiments to evaluate the effect of temperature on photoinhibition properties in the cosmopolitan diatom Thalassiosira weissflogii . Cultures were exposed to solar radiation with or without ultraviolet radiation (UVR, 280–400 nm), UV‐A (320–400 nm), and UV‐B (280–320 nm) at both 20°C and 25°C. Four possible cellular mechanisms involved in UVR stress were simultaneously addressed: carbon incorporation, chlorophyll a fluorescence of photosystem II, xanthophyll cycle activity, and ribulose‐1,5‐biphosphate carboxylase : oxygenase (Rubisco) activity and gene expression. Experiments consisted of daily cycles (i.e., the daylight period) and short‐term incubations (i.e., 1 h centered on local noon). Samples incubated at 25°C had significantly less UVR‐induced inhibition of carbon fixation and effective photochemical quantum yield compared to those incubated at 20°C. At 25°C Rubisco activity and gene expression were significantly higher than at 20°C. The higher Rubisco activity and gene expression were correlated with less dissipation of excess energy, evaluated via non‐photochemical quenching, and the de‐epoxidation state of the xanthophyll pigments, as more photons could be processed. An increase in temperature due to climate change would partially counteract the negative effects of UVR by increasing the response of metabolic pathways, such as those involved in Rubisco. This, in turn, may have important consequences for the ecosystem, as higher production (due to more Rubisco activity) could be expected under a scenario of global warming.

Spatial variations of atmospheric methane concentrations in China - Xiuying Zhang; Hong Jiang; Yueqi Wang; Ying Han; M. Buchwitz; O. Schneising; J. P. Burrows (International Journal of Remote Sensing, 2011)

Increased Bioavailability of Mercury in the Lagoons of Lomé, Togo: The Possible Role of Dredging - Kissao Gnandi; Seunghee Han; M. Hassan Rezaie-Boroon; Magali Porrachia; Dimitri D. Deheyn (Ambio, 2011)

Fine-tuning of the backward erosion piping model through small-scale, medium-scale and IJkdijk experiments - Hans Sellmeijer; Juliana López de la Cruz; Vera M. van Beek; Han Knoeff (European Journal of Environmental and Civil Engineering, 2011)

Observations on the process of backward erosion piping in small-, medium- and full-scale experiments - Vera M. van Beek; Han Knoeff; Hans Sellmeijer (European Journal of Environmental and Civil Engineering, 2011)

Atypical Aeromonas salmonicida infection in the black rockfish, Sebastes schlegeli Hilgendorf , in Korea - H‐J Han; D‐Y Kim; W‐S Kim; C‐S Kim; S‐J Jung; M‐J Oh; D‐H Kim (Journal of Fish Diseases, 2011)
Cultured black rockfish, Sebastes schlegeli , suffered mass mortalities during winter 2008 and spring 2009 in Korea, showing clinical signs of ulcer lesions and haemorrhages over their body surface. The aetiological agent was identified as Aeromonas salmonicida (strains RFAS‐1, ‐2 and ‐3), which is a non‐pigmented, slow‐growing bacterium. Phenotypes of RFAS strains showed variation, while 16S rRNA, gyrB , rpoD , dnaJ and recA gene sequences of all the strains were affiliated to A. salmonicida. In particular, vapA gene sequences of the strains were most closely related to one of the five subspecies of A. salmonicida subsp. masoucida (=KCCM 40239 T ). LD 50 values of RFAS‐1 for intraperitoneal and intramuscular injection were 1.5 × 10 5.25 and 1.5 × 10 6.4 cfu/rockfish, respectively. However, A. salmonicida strains KCCM 40239 T and SAS‐1, which originate from masou and chum salmon, respectively, were not pathogenic to black rockfish. RFAS strains, possessing A‐layer protein on their surface, exhibited β‐haemolytic activity against rockfish erythrocytes and capability to survive in rockfish serum, which seem to be associated with virulence.

Effects of stand age, wildfire and clearcut harvesting on forest floor in boreal mixedwood forests - Bharat M. Shrestha; Han Y. H. Chen (Plant and Soil, 2010)

Nicotinic acetylcholine receptor genes on chromosome 15q25.1 are associated with nicotine and opioid dependence severity - Porat M. Erlich; Stuart N. Hoffman; Margaret Rukstalis; John J. Han; Xin Chu; W. H. Linda Kao; Glenn S. Gerhard; Walter F. Stewart; Joseph A. Boscarino (Human Genetics, 2010)

Leaf habit and woodiness regulate different leaf economy traits at a given nutrient supply - Jenny C. Ordoñez; Peter M. van Bodegom; Jan-Philip M. Witte; Ruud P. Bartholomeus; Han F. van Dobben; Rien Aerts (Ecology, 2010)
The large variation in the relationships between environmental factors and plant traits observed in natural communities exemplifies the alternative solutions that plants have developed in response to the same environmental limitations. Qualitative attributes, such as growth form, woodiness, and leaf habit can be used to approximate these alternative solutions. Here, we quantified the extent to which these attributes affect leaf trait values at a given resource supply level, using measured plant traits from 105 different species (254 observations) distributed across 50 sites in mesic to wet plant communities in The Netherlands. For each site, soil total N, soil total P, and water supply estimates were obtained by field measurements and modeling. Effects of growth forms, woodiness, and leaf habit on relations between leaf traits (SLA, specific leaf area; LNC, leaf nitrogen concentration; and LPC, leaf phosphorus concentration) vs. nutrient and water supply were quantified using maximum‐likelihood methods and Bonferroni post hoc tests. The qualitative attributes explained 8–23% of the variance within sites in leaf traits vs. soil fertility relationships, and therefore they can potentially be used to make better predictions of global patterns of leaf traits in relation to nutrient supply. However, at a given soil fertility, the strength of the effect of each qualitative attribute was not the same for all leaf traits. These differences may imply a differential regulation of the leaf economy traits at a given nutrient supply, in which SLA and LPC seem to be regulated in accordance to changes in plant size and architecture while LNC seems to be primarily regulated at the leaf level by factors related to leaf longevity.

An examination of aspartate decarboxylase and glutamate decarboxylase activity in mosquitoes - Graham Richardson; Haizhen Ding; Tom Rocheleau; George Mayhew; Erin Reddy; Qian Han; Bruce M. Christensen; Jianyong Li (Molecular Biology Reports, 2010)

Master donor viruses A/Leningrad/134/17/57 (H2N2) and B/USSR/60/69 and derived reassortants used in live attenuated influenza vaccine (LAIV) do not display neurovirulent properties in a mouse model - J. Theo M. Voeten; Irina V. Kiseleva; Harrie L. Glansbeek; Stephanie M. C. Basten; Sandra K. M. Drieszen-van der Cruijsen; Larisa G. Rudenko; Han van den Bosch; Jacco G. M. Heldens (Archives of Virology, 2010)

Age-period-cohort analysis of cancers not related to tobacco, screening, or HIV: sex and race differences - Yueh-Ying Han; Gregg E. Dinse; David M. Umbach; Devra L. Davis; Joel L. Weissfeld (Cancer Causes & Control, 2010)

Human Enteric Viruses in Groundwater - S. H. Park; E. J. Kim; T. H. Yun; J. H. Lee; C. K. Kim; Y. H. Seo; S. A. Oh; S. S. Choi; S. J. Cho; M. S. Kim; G. Y. Han; M. Y. Kim; et al. (Food and Environmental Virology, 2010)

Female BRCA mutation carriers with a preference for prophylactic mastectomy are more likely to participate an educational-support group and to proceed with the preferred intervention within 2 years - Karin M. Landsbergen; Judith B. Prins; Yvonne J. L. Kamm; Han G. Brunner; Nicoline Hoogerbrugge (Familial Cancer, 2010)

Population structure of the olive flounder ( Paralichthys olivaceus ) in Korea inferred from microsatellite marker analysis - W.‐J. Kim; K.‐K. Kim; H.‐S. Han; B.‐H. Nam; Y.‐O. Kim; H.‐J. Kong; J.‐K. Noh; M. Yoon (Journal of Fish Biology, 2010)
The population structure of olive flounder Paralichthys olivaceus was estimated using nine polymorphic microsatellite (MS) loci in 459 individuals collected from eight populations, including five wild and three hatchery populations in Korea. Genetic variation in hatchery (mean number of alleles per locus, A = 10·2–12·1; allelic richness, A R = 9·3–10·1; observed heterozygosity, H O = 0·766–0·805) and wild (mean number of alleles per locus, A = 11·8–19·6; allelic richness, A R = 10·9–16·1; observed heterozygosity, H O = 0·820–0·888) samples did not differ significantly, suggesting a sufficient level of genetic variation in these well‐managed hatchery populations, which have not lost a substantial amount of genetic diversity. Neighbour‐joining tree and principal component analyses showed that genetic separation between eastern and pooled western and southern wild populations in Korea was probably influenced by restricted gene flow between regional populations due to the barrier effects of sea currents. The pooled western and southern populations are genetically close, perhaps because larval dispersal may depend on warm currents. One wild population (sample from Wando) was genetically divergent from the main distribution, but it was genetically close to hatchery populations, indicating that the genetic composition of the studied populations may be affected by hydrographic conditions and the release of fish stocks. The estimated genetic population structure and potential applications of MS markers may aid in the proper management of P. olivaceus populations.

Comparison of reproductive development in triploid and diploid female rainbow trout Oncorhynchus mykiss - Y. Han; M. Liu; L. Lan Zhang; B. Simpson; G. Xue Zhang (Journal of Fish Biology, 2010)
The diploid rainbow trout Oncorhynchus mykiss reached sexual maturity 3 years after hatching and its oogenesis underwent four stages, which were oogonia, primary oocyte, secondary oocyte and egg. Reproductive development and hormone changes of 4 to 35 month‐old female O. mykiss were investigated using histological and radioimmunoassay methods in order to provide a theoretical and practical basis for the use of triploid female O. mykiss . The oogonium of the triploid female could develop into the oocytes of the prophase with abortion occurring later; the oogonium was surrounded by stroma cells to form the oogonium cluster and the gonads showed a virilescent tendency when the oogonium clusters were gradually replaced by spermatogenic‐like cytocysts. After 13 months, amounts of gonadotropic hormone (GtH‐I, GtH‐II) and oestradiol (17 β ‐E 2 ) in triploid females were lower than in diploid fish at corresponding time periods, but the amounts of testosterone (T) increased consistently after 21 months and were more than in diploid fish in the corresponding time periods ( P > 0·05). The infertility of triploid females resulted from meiosis failure, which caused developmental abortion of oocytes and oogonium formed cytocysts before the prophase oocytes. The cytocyst formation was due to the lack of the normal interaction of ovum and follicular cells, the development of follicular cells producing steroids were inhibited, the arylate path from T to 17 β ‐E 2 was interrupted, concentration of 17 β ‐E 2 decreased and concentration of T increased in the blood, the content of vitellogenin (Vg) decreased in the liver with a low 17 β ‐E 2 and high T caused to ovaries to show a tendency to be virilescent.

Effect of paraquat on the antioxidative enzyme activities and lipid peroxidation in opium poppy (Papaver somniferum L.) - R. Zhao; P. -Y. Guo; X. -Y. Yuan; J. -Y. Wang; M. -Q. Han (Journal of Plant Diseases and Protection, 2010)

A novel single-nucleotide polymorphism of thevisfatin gene and its associations with performance traits in the chicken - R. L. Han; X. Y. Lan; L. Z. Zhang; G. Ren; Y. J. Jing; M. J. Li; B. Zhang; M. Zhao; Y. K. Guo; X. T. Kang; H. Chen (Journal of Applied Genetics, 2010)

Active reassortment of H9 influenza viruses between wild birds and live-poultry markets in Korea - Ho Jin Moon; Min Suk Song; Deu John M. Cruz; Kuk Jin Park; Philippe Noriel Q. Pascua; Jun Han Lee; Yun Hee Baek; Dong Ho Choi; Young Ki Choi; Chul Joong Kim (Archives of Virology, 2010)

Experimental examination of the effects of ultraviolet-B radiation in combination with other stressors on frog larvae - Catherine Laura Searle; Lisa K. Belden; Betsy A. Bancroft; Barbara A. Han; Lindsay M. Biga; Andrew R. Blaustein (Oecologia, 2010)

Genetic variation in N-acetyltransferases 1 and 2, cigarette smoking, and risk of non-Hodgkin lymphoma - Briseis A. Kilfoy; Tongzhang Zheng; Qing Lan; Xuesong Han; Theodore Holford; David W. Hein; Qin Qin; Brian Leaderer; Lindsay M. Morton; Meredith Yeager; Peter Boyle; Ping Zhao; et al. (Cancer Causes & Control, 2010)

Tradeoffs and thresholds in the effects of nitrogen addition on biodiversity and ecosystem functioning: evidence from inner Mongolia Grasslands - YONGFEI BAI; JIANGUO WU; CHRISTOPHER M. CLARK; SHAHID NAEEM; QINGMIN PAN; JIANHUI HUANG; LIXIA ZHANG; XINGGUO HAN (Global Change Biology, 2010)
Nitrogen (N) deposition is widely considered an environmental problem that leads to biodiversity loss and reduced ecosystem resilience; but, N fertilization has also been used as a management tool for enhancing primary production and ground cover, thereby promoting the restoration of degraded lands. However, empirical evaluation of these contrasting impacts is lacking. We tested the dual effects of N enrichment on biodiversity and ecosystem functioning at different organizational levels (i.e., plant species, functional groups, and community) by adding N at 0, 1.75, 5.25, 10.5, 17.5, and 28.0 g N m −2 yr −1 for four years in two contrasting field sites in Inner Mongolia: an undisturbed mature grassland and a nearby degraded grassland of the same type. N addition had both quantitatively and qualitatively different effects on the two communities. In the mature community, N addition led to a large reduction in species richness, accompanied by increased dominance of early successional annuals and loss of perennial grasses and forbs at all N input rates. In the degraded community, however, N addition increased the productivity and dominance of perennial rhizomatous grasses, with only a slight reduction in species richness and no significant change in annual abundance. The mature grassland was much more sensitive to N‐induced changes in community structure, likely as a result of higher soil moisture accentuating limitation by N alone. Our findings suggest that the critical threshold for N‐induced species loss to mature Eurasian grasslands is below 1.75 g N m −2 yr −1 , and that changes in aboveground biomass, species richness, and plant functional group composition to both mature and degraded ecosystems saturate at N addition rates of approximately 10.5 g N m −2 yr −1 . This work highlights the tradeoffs that exist in assessing the total impact of N deposition on ecosystem function.

Estimated PBDE and PBB Congeners in Soil from an Electronics Waste Disposal Site - H.-M. Wang; Y.-J. Yu; M. Han; S.-W. Yang; Q. li; Y. Yang (Bulletin of Environmental Contamination and Toxicology, 2009)

Jasmine tea consumption and upper gastrointestinal cancer in China - Ying Gao; Nan Hu; XiaoYou Han; Carol Giffen; Ti Ding; Alisa M. Goldstein; Philip R. Taylor (Cancer Causes & Control, 2009)

Genetic testing for Lynch syndrome in the first year of colorectal cancer: a review of the psychological impact - Karin M. Landsbergen; Judith B. Prins; Han G. Brunner; Floris W. Kraaimaat; Nicoline Hoogerbrugge (Familial Cancer, 2009)

Molecular characterization of hepatitis A virus isolated from acute gastroenteritis patients in the Seoul region of Korea - S.-H. Park; E.-J. Kim; J.-H. Lee; S.-S. Choi; M.-S. Kim; S.-S. Jung; G.-Y. Han; H.-S. Yun; D.-S. Chun; S.-S. Oh; H.-S. Kim (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

Physicochemical and Immunological Characterization of N,N,N-Trimethyl Chitosan-Coated Whole Inactivated Influenza Virus Vaccine for Intranasal Administration - Niels Hagenaars; Enrico Mastrobattista; Rolf J. Verheul; Imke Mooren; Harrie L. Glansbeek; Jacco G. M. Heldens; Han van den Bosch; Wim Jiskoot (Pharmaceutical Research, 2009)

Development of Quantum Dot-Mediated Fluorescence Thermometry for Thermal Therapies - Bumsoo Han; Willard L. Hanson; Karim Bensalah; Altug Tuncel; Joshua M. Stern; Jeffrey A. Cadeddu (Annals of Biomedical Engineering, 2009)

Monitoring large herbivore diversity at different scales: comparing direct and indirect methods - Joris P. G. M. Cromsigt; Susan J. van Rensburg; Rampal S. Etienne; Han Olff (Biodiversity and Conservation, 2009)

Informative study designs to identify true parameter–covariate relationships - Phey Yen Han; Carl M. J. Kirkpatrick; Bruce Green (Journal of Pharmacokinetics and Pharmacodynamics, 2009)

Estimation of the gross primary production of an old‐growth temperate mixed forest using eddy covariance and remote sensing - J. B. Wu; X. M. Xiao; D. X. Guan; T. T. Shi; C. J. Jin; S. J. Han (International Journal of Remote Sensing, 2009)

Landscape Planning for Agricultural Nonpoint Source Pollution Reduction III: Assessing Phosphorus and Sediment Reduction Potential - Matthew W. Diebel; Jeffrey T. Maxted; Dale M. Robertson; Seungbong Han; M. Jake Vander Zanden (Environmental Management, 2009)

Resistance to race 2 and cross-resistance to race 1 of Kabatiella caulivora in Trifolium subterraneum and T. purpureum - Hua Li; P. G. H. Nichols; S. Han; K. J. Foster; K. Sivasithamparam; M. J. Barbetti (Australasian Plant Pathology, 2009)

Establishing the foundation for an applied molecular taxonomy of otters in Southeast Asia - Klaus-Peter Koepfli; Budsabong Kanchanasaka; Hiroshi Sasaki; Hélène Jacques; Kristina D. Y. Louie; Toanvong Hoai; Nguyen Xuan Dang; Eli Geffen; Arno Gutleb; Sung-yong Han; Thrine M. Heggberget; Lionel LaFontaine; et al. (Conservation Genetics, 2008)

Neural network determination of cloud attenuation to estimate insolation using MTSAT‐1R data - J.‐M. Yeom; K.‐S. Han; Y.‐S. Kim; J.‐D. Jang (International Journal of Remote Sensing, 2008)

Identification of a recombinant dengue virus type 1 with 3 recombination regions in natural populations in Guangdong province, China - S.-P. Chen; M. Yu; T. Jiang; Y.-Q. Deng; C.-F. Qin; J.-F. Han; E.-D. Qin (Archives of Virology, 2008)

Sources and Properties of Natural Organic Matter (NOM) in Water Along the Dongjiang River (the Source of Hong Kong’s Drinking Water) and Toxicological Assay of Its Chlorination By-Products - Y. Liang; H. C. Hong; L. H. Dong; C. Y. Lan; B. P. Han; M. H. Wong (Archives of Environmental Contamination and Toxicology, 2008)

Radiation-Guided P-Selectin Antibody Targeted to Lung Cancer - G. Hariri; Y. Zhang; A. Fu; Z. Han; M. Brechbiel; M. N. Tantawy; T. E. Peterson; R. Mernaugh; D. Hallahan (Annals of Biomedical Engineering, 2008)

Spatio-temporal variability of Northern Hemipheric Sea Level Pressure (SLP) and precipitation over the mid-to-low reaches of the Yangtze River - Xue Han; Fengying Wei; Yves M. Tourre; Wenjie Dong (Advances in Atmospheric Sciences, 2008)

Quantization analysis of weather radar data with synthetic rainfall - M. Hammond; D. Han (Stochastic Environmental Research and Risk Assessment, 2008)

Agrobacterium-mediated transformation of maize (Zea mays) with Cre-lox site specific recombination cassettes in BIBAC vectors - Juan M. Vega; Weichang Yu; Fangpu Han; Akio Kato; Eric M. Peters; Zhanyuan J. Zhang; James A. Birchler (Plant Molecular Biology, 2008)

Cysts of PRKCSH mutated polycystic liver disease patients lack hepatocystin but express Sec63p - Esmé Waanders; Huib J. E. Croes; Cathy N. Maass; René H. M. Morsche; Hendrikus J. A. A. Geffen; J. Han J. M. Krieken; Jack A. M. Fransen; Joost P. H. Drenth (Histochemistry and Cell Biology, 2008)

Characterization of a Homogentisate Dioxygenase Mutant in Pseudomonas chlororaphis O6 - B. R. Kang; S. H. Han; S. M. Cho; A. J. Anderson; I. S. Kim; S. K. Park; Y. C. Kim (Current Microbiology, 2008)

Genotypic differences in leaf biochemical, physiological and growth responses to ozone in 20 winter wheat cultivars released over the past 60 years - D. K. BISWAS; H. XU; Y. G. LI; J. Z. SUN; X. Z. WANG; X. G. HAN; G. M. JIANG (Global Change Biology, 2008)
Ozone (O 3 ) concentrations in periurban areas in East Asia are sufficiently high to decrease crop yield. However, little is known about the genotypic differences in O 3 sensitivity in winter wheat in relation to year of cultivar release. This paper reports genotypic variations in O 3 sensitivity in 20 winter wheat cultivars released over the past 60 years in China highlighting O 3 ‐induced mechanisms. Wheat plants were exposed to elevated O 3 (82 ppb O 3 , 7 h day −1 ) or charcoal‐filtered air ( 3 ) for 21 days in open top chambers. Responses to O 3 were assessed by the levels of antioxidative activities, protein alteration, membrane lipid peroxidation, gas exchange, leaf chlorophyll, dark respiration and growth. We found that O 3 significantly reduced foliar ascorbate (−14%) and soluble protein (−22%), but increased peroxidase activity (+46%) and malondialdehyde (+38%). Elevated O 3 depressed light saturated net photosynthetic rate (−24%), stomatal conductance (−8%) and total chlorophyll (−11%), while stimulated dark respiration (+28%) and intercellular CO 2 concentration (+39%). O 3 also reduced overall plant growth, but to a greater extent in root (−32%) than in shoot (−17%) biomass. There was significant genotypic variation in potential sensitivity to O 3 that did not correlate to observed O 3 tolerance. Sensitivity to O 3 in cultivars of winter wheat progressed with year of release and correlated with stomatal conductance and dark respiration in O 3 ‐exposed plants. O 3 ‐induced loss in photosynthetic rate was attributed primarily to impaired activity of mesophyll cells and loss of integrity of cellular membrane as evidenced by increased intercellular CO 2 concentration and lipid peroxidation. Our findings demonstrated that higher sensitivity to O 3 in the more recently released cultivars was induced by higher stomatal conductance, larger reduction in antioxidative capacity and lower levels of dark respiration leading to higher oxidative damage to proteins and integrity of cellular membranes.

Sex Differences in the Steepness of Dominance Hierarchies in Captive Bonobo Groups - Jeroen M. G. Stevens; Hilde Vervaecke; Han de Vries; Linda van Elsacker (International Journal of Primatology, 2007)

Characteristics of reactive nitrogen compounds and other relevant trace gases in the atmosphere at urban and rural areas of Korea during May–June, 2004 - Z.-H. Shon; G. Lee; S.-K. Song; M. Lee; J. Han; D. Lee (Journal of Atmospheric Chemistry, 2007)

Utilization of seagrass habitats by juvenile groupers and snappers in Banten Bay, Banten Province, Indonesia - Siti Nuraini; Eira C. Carballo; Wim L. T. van Densen; Marcel A. M. Machiels; Han J. Lindeboom; Leopold A. J. Nagelkerke (Hydrobiologia, 2007)

Monitoring of Aerial Pollutants Emitted from Swine Houses in Korea - Ki Y. Kim; Han J. Ko; Hyeon T. Kim; Yoon S. Kim; Young M. Roh; Cheol M. Lee; Chi N. Kim (Environmental Monitoring and Assessment, 2007)

Changes of chemical and nutrient composition of porcine blood during fermentation by Aspergillus oryzae - J. Z. Wang; M. Zhang; F. Z. Ren; B. Z. Han; L. Wang; S. W. Chen; A. Humera (World Journal of Microbiology and Biotechnology, 2007)

Aggression and dominance in matched groups of subadult Icelandic horses (Equus caballus) - Hilde Vervaecke; Jeroen M. G. Stevens; Harold Vandemoortele; Hrefna Sigurjónsdóttir; Han De Vries (Journal of Ethology, 2007)

Gene expression profiling reveals two separate mechanisms regulating apoptosis in rectal carcinomas in vivo - Elza C. de Bruin; Simone van de Pas; Cornelis J. H. van de Velde; J. Han J. M. van Krieken; Lucy T. C. Peltenburg; Corrie A. M. Marijnen; Jan Paul Medema (Apoptosis, 2007)

Terrestrial carbon pools in southeast and south-central United States - Fengxiang X. Han; M. John Plodinec; Yi Su; David L. Monts; Zhongpei Li (Climatic Change, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Intragenic deletion in the LARGE gene causes Walker-Warburg syndrome - Jeroen van Reeuwijk; Prabhjit K. Grewal; Mustafa A. M. Salih; Daniel Beltrán-Valero de Bernabé; Jenny M. McLaughlan; Caroline B. Michielse; Ralf Herrmann; Jane E. Hewitt; Alice Steinbrecher; Mohamed Z. Seidahmed; Mohamed M. Shaheed; Abdullah Abomelha; et al. (Human Genetics, 2007)

Permeabilization of the plasma membrane by Ebola virus GP2 - Ziying Han; Jillian M. Licata; Jason Paragas; Ronald N. Harty (Virus Genes, 2007)

Estimating afternoon MODIS land surface temperatures (LST) based on morning MODIS overpass, location and elevation information - N. C. Coops; D. C. Duro; M. A. Wulder; T. Han (International Journal of Remote Sensing, 2007)

Distinct chromosomal distributions of highly repetitive sequences in maize - Jonathan C. Lamb; Julie M. Meyer; Blake Corcoran; Akio Kato; Fangpu Han; James A. Birchler (Chromosome Research, 2007)

Pathogenicity of Edwardsiella tarda to olive flounder, Paralichthys olivaceus (Temminck & Schlegel) - H‐J Han; D‐H Kim; D‐C Lee; S‐M Kim; S‐I Park (Journal of Fish Diseases, 2006)
The LD 50 and cytotoxic and enzymatic activities of both cells and extracellular products (ECPs) of eight Edwardsiella tarda strains were determined and their bacterial superoxide dismutase gene (sodB) and catalase gene (katB) were sequenced. Strains were also examined for their ability to resist the immune responses of olive flounder, Paralichthys olivaceus . LD 50 values of strains (FSW910410, KE1, 2, 3, 4, 5 and 6) in olive flounder ranged between 10 2.5 and 10 5.3 cfu (colony forming units) per fish. Unlike the avirulent strain SU100 (LD 50 ≥ 10 7 ), all pathogenic strains were able to survive in flounder serum and head kidney leucocytes (except for KE2). The virulent strains possessed type I sodB and katB, whereas SU100 had type II sodB but not katB. However, there was no difference between avirulent and virulent strains in haemolytic and cytotoxic activities. The results of this study demonstrated that the ability of E. tarda to resist complement activity and phagocytosis is conferred by its superoxide dismutase and catalase, which thus play an essential role in the pathogenicity of this bacterium. In addition genotyping of sodB and kat B proved to be a very useful tool to distinguish virulent from avirulent strains.

Evolution of an intronic microsatellite polymorphism in Toll-like receptor 2 among primates - Jae-Joon Yim; Amelia A. Adams; Ju Han Kim; Steven M. Holland (Immunogenetics, 2006)

Detection and identification of avian, duck, and goose reoviruses by RT-PCR: goose and duck reoviruses are part of the same genogroup in the genus Orthoreovirus - Y. Zhang; M. Liu; O. Shuidong; Q. L. Hu; D. C. Guo; H. Y. Chen; Z. Han (Archives of Virology, 2006)

Extent and pattern of DNA methylation alteration in rice lines derived from introgressive hybridization of rice and Zizania latifolia Griseb - Z. Y. Dong; Y. M. Wang; Z. J. Zhang; Y. Shen; X. Y. Lin; X. F. Ou; F. P. Han; B. Liu (Theoretical and Applied Genetics, 2006)

Social structures in Pan paniscus: testing the female bonding hypothesis - Jeroen M. G. Stevens; Hilde Vervaecke; Han De Vries; Linda Van Elsacker (Primates, 2006)

Herbivore impact on grassland plant diversity depends on habitat productivity and herbivore size - Elisabeth S. Bakker; Mark E. Ritchie; Han Olff; Daniel G. Milchunas; Johannes M. H. Knops (Ecology Letters, 2006)
Mammalian herbivores can have pronounced effects on plant diversity but are currently declining in many productive ecosystems through direct extirpation, habitat loss and fragmentation, while being simultaneously introduced as livestock in other, often unproductive, ecosystems that lacked such species during recent evolutionary times. The biodiversity consequences of these changes are still poorly understood. We experimentally separated the effects of primary productivity and herbivores of different body size on plant species richness across a 10‐fold productivity gradient using a 7‐year field experiment at seven grassland sites in North America and Europe. We show that assemblages including large herbivores increased plant diversity at higher productivity but decreased diversity at low productivity, while small herbivores did not have consistent effects along the productivity gradient. The recognition of these large‐scale, cross‐site patterns in herbivore effects is important for the development of appropriate biodiversity conservation strategies.

Antidepressant-like effects of PDE4 inhibitors mediated by the high-affinity rolipram binding state (HARBS) of the phosphodiesterase-4 enzyme (PDE4) in rats - Han-Ting Zhang; Yu Zhao; Ying Huang; Chengjun Deng; Allen T. Hopper; Michael De Vivo; Gregory M. Rose; James M. O’Donnell (Psychopharmacology, 2006)

Radon distribution in groundwater of Taiwan - Y. L. Han; M. C. Tom Kuo; K. C. Fan; C. J. Chiang; Y. P. Lee (Hydrogeology Journal, 2006)

Delineating the northern part of the Socotra Basin, offshore Korea, using marine magnetics - M. Suh; T. F. Abdallatif; J. Han; S. Choi; J. Oh (Geo-Marine Letters, 2005)

To the article “Tissue-specific changes in heme oxygenase activity and level of nonprotein Thiols in C57Bl/6 mice after whole-body γ-irradiation”, Vol. 140, No. 3, pp. 341–344 (2005) - Ensu Han; A. G. Platonov; M. Ya. Akhalaya; Ji Yon Son; Ji Yon An; Yon Suk Yun (Bulletin of Experimental Biology and Medicine, 2005)

Global gene expression analysis revealed an unsuspected deo operon under the control of molybdate sensor, ModE protein, in Escherichia coli - Han Tao; Adnan Hasona; Phi M. Do; L.O. Ingram; K.T. Shanmugam (Archives of Microbiology, 2005)

Interaction between the antidepressant-like behavioral effects of beta adrenergic agonists and the cyclic AMP PDE inhibitor rolipram in rats - Han-Ting Zhang; Ying Huang; Kathleen Mishler; Sandra C. Roerig; James M. O'Donnell (Psychopharmacology, 2005)

The influence of muscle type and dystrophin deficiency on murine expression profiles - Judith N. Haslett; Peter B. Kang; Mei Han; Alvin T. Kho; Despina Sanoudou; Jay M. Volinski; Alan H. Beggs; Isaac S. Kohane; Louis M. Kunkel (Mammalian Genome, 2005)

Interspecific Variation in Susceptibility of Frog Tadpoles to the Pathogenic Fungus Batrachochytrium dendrobatidis - ANDREW R. BLAUSTEIN; JOHN M. ROMANSIC; ERIN A. SCHEESSELE; BARBARA A. HAN; ALLAN P. PESSIER; JOYCE E. LONGCORE (Conservation Biology, 2005)
As part of an overall biodiversity crisis many amphibian populations are in decline throughout the world. Numerous causes have been invoked to explain these declines. These include habitat destruction, climate change, increasing levels of ultraviolet radiation, environmental contamination, and the introduction of non‐native species and diseases. Several types of pathogens have been implicated in contributing to amphibian population declines: viruses, bacteria, oomycetes, and fungi. One particular fungus, the chytridiomycete Batrachochytrium dendrobatidis may have caused amphibian population declines in several regions. This pathogen causes chytridiomycosis, which is fatal to newly metamorphic and adult amphibians of certain species. We present experimental evidence that larval stages may also be susceptible to exposure to Batrachochytrium . There was, however, differential sensitivity to B. dendrobatidis in larvae we examined. In laboratory experiments, larval western toads ( Bufo boreas ) exposed to B. dendrobatidis experienced increased mortality and behaviors that suggested they were affected by exposure compared with unexposed control tadpoles. Larvae of Cascades frogs ( Rana cascadae ), bullfrogs ( R. catesbeiana ), and Pacific treefrogs ( Hyla regilla ) did not die after exposure to Batrachochytrium and appeared to behave normally. R. cascadae larvae exposed to B. dendrobatidis , however, showed an increase incidence in mouthpart abnormalities, a characteristic effect of chytridiomycosis, compared with unexposed controls. These results show that Batrachochytrium can negatively affect some species of amphibians at the larval stage and not others. The implications of interspecific variation in susceptibility to fungal infection are broad.

Tissue-Specific Changes in Heme Oxygenase Activity and Level of Nonprotein Thiols in C57Bl/6 Mice after Whole-Body γ-Irradiation - Ensu Han; A. G. Platonov; M. Ya. Akhalaya; Ji Yon Son; Ji Yon An; Yon Suk Yun (Bulletin of Experimental Biology and Medicine, 2005)

Effects of the novel PDE4 inhibitors MEM1018 and MEM1091 on memory in the radial-arm maze and inhibitory avoidance tests in rats - Han-Ting Zhang; Ying Huang; Neesha U. Suvarna; Chengjun Deng; Alicia M. Crissman; Allen T. Hopper; Michael De Vivo; Gregory M. Rose; James M. O’Donnell (Psychopharmacology, 2005)

Mutational analysis of OGG1, MYH, MTH1 in FAP, HNPCC and sporadic colorectal cancer patients: R154H OGG1 polymorphism is associated with sporadic colorectal cancer patients - I.-J. Kim; J.-L. Ku; H. C. Kang; J.-H. Park; K.-A. Yoon; Y. Shin; H.-W. Park; S. G. Jang; S.-K. Lim; S. Y. Han; Y.-K. Shin; M. R. Lee; et al. (Human Genetics, 2004)

Use of Pi5(t) markers in marker-assisted selection to screen for cultivars with resistance to Magnaporthe grisea - G. Yi; S.-K. Lee; Y.-K. Hong; Y.-C. Cho; M.-H. Nam; S.-C. Kim; S.-S. Han; G.-L. Wang; T.-R. Hahn; P.C. Ronald; J.-S. Jeon (Theoretical and Applied Genetics, 2004)

Experimental investigation of the mammary gland tumour phantom for multifrequency microwave radio-thermometers - J. W. Lee; S. M. Lee; K. S. Kim; W. T. Han; G. Yoon; L. A. Pasmanik; I. A. Ulyanichev; A. V. Troitsky (Medical & Biological Engineering & Computing, 2004)

Bacterial enteritis and the development of the larval digestive tract in olive flounder, Paralichthys olivaceus (Temminck & Schlegel) - D‐H Kim; H‐J Han; S‐M Kim; D‐C Lee; S‐I Park (Journal of Fish Diseases, 2004)
Three bacterial isolates obtained from diseased olive flounder larvae, Paralichthys olivaceus , were identified as Vibrio ichthyoenteri based on the results of phenotypic characterization and 16S rRNA gene sequencing studies. Bacterial enteritis was reproduced in 16 and 22 days post‐hatch (dph) larvae by administering brine shrimp nauplii, Artemia salina , dosed with the environmental isolates and reference strains of V. ichthyoenteri . To investigate the effect of the disease on development of the stomach, a pepsin activity assay and reverse transcription‐polymerase chain reaction (RT‐PCR) analysis of the expression of the pepsinogen gene were performed. Expression of olive flounder pepsinogen was detected from 30‐dph larvae and the increased level of pepsin activity coincided with reduced susceptibility to the disease. Growth rates of V. ichthyoenteri , V. anguillarum and Edwardsiella tarda were tested in artificial stomach conditions using HCl and porcine pepsin. All the strains of V. ichthyoenteri were inhibited by low pH conditions which corresponded with an increase in pepsin levels. This suggests that differentiation of the stomach in olive flounder larvae and juveniles, an essential physiological development, also provides the host with a non‐immunological defence mechanism.

Estimates of CO 2 uptake and release among European forests based on eddy covariance data - Albert I. J. M. Van Dijk; A. J. (HAN) Dolman (Global Change Biology, 2004)
The net ecosystem exchange (NEE) of forests represents the balance of gross primary productivity (GPP) and respiration (R). Methods to estimate these two components from eddy covariance flux measurements are usually based on a functional relationship between respiration and temperature that is calibrated for night‐time (respiration) fluxes and subsequently extrapolated using daytime temperature measurements. However, respiration fluxes originate from different parts of the ecosystem, each of which experiences its own course of temperature. Moreover, if the temperature–respiration function is fitted to combined data from different stages of biological development or seasons, a spurious temperature effect may be included that will lead to overestimation of the direct effect of temperature and therefore to overestimates of daytime respiration. We used the EUROFLUX eddy covariance data set for 15 European forests and pooled data per site, month and for conditions of low and sufficient soil moisture, respectively. We found that using air temperature (measured above the canopy) rather than soil temperature (measured 5 cm below the surface) yielded the most reliable and consistent exponential ( Q 10 ) temperature–respiration relationship. A fundamental difference in air temperature‐based Q 10 values for different sites, times of year or soil moisture conditions could not be established; all were in the range 1.6–2.5. However, base respiration ( R 0 , i.e. respiration rate scaled to 0°C) did vary significantly among sites and over the course of the year, with increased base respiration rates during the growing season. We used the overall mean Q 10 of 2.0 to estimate annual GPP and R. Testing suggested that the uncertainty in total GPP and R associated with the method of separation was generally well within 15%. For the sites investigated, we found a positive relationship between GPP and R, indicating that there is a latitudinal trend in NEE because the absolute decrease in GPP towards the pole is greater than in R.

Fine mapping of a malting-quality QTL complex near the chromosome 4H S telomere in barley - W. Gao; J. A. Clancy; F. Han; B. L. Jones; A. Budde; D. M. Wesenberg; A. Kleinhofs; S. E. Ullrich (Theoretical and Applied Genetics, 2004)

Identification and molecular modelling of a mutation in the motor head domain of myosin VIIA in a family with autosomal dominant hearing impairment (DFNA11) - Mirjam W. J. Luijendijk; Erwin van Wijk; Anne M. L. C. Bischoff; Elmar Krieger; Patrick L. M. Huygen; Ronald J. E. Pennings; Han G. Brunner; Cor W. R. J. Cremers; Frans P. M. Cremers; Hannie Kremer (Human Genetics, 2004)

Activation of a rice endogenous retrotransposon Tos17 in tissue culture is accompanied by cytosine demethylation and causes heritable alteration in methylation pattern of flanking genomic regions - Z. L. Liu; F. P. Han; M. Tan; X. H. Shan; Y. Z. Dong; X. Z. Wang; G. Fedak; S. Hao; Bao Liu (Theoretical and Applied Genetics, 2004)

Role of the second coordination sphere residue tyrosine 179 in substrate affinity and catalytic activity of phenylalanine hydroxylase - Jérôme Zoidakis; Mui Sam; Alon Volner; Andrew Han; Kim Vu; Mahdi M. Abu-Omar (JBIC Journal of Biological Inorganic Chemistry, 2004)

Development of Oligonucleotide Primers for the Detection of Harmful Microcystis in Water - J.-E. Cho; S.-W. Bang; M.-S. Han (Bulletin of Environmental Contamination and Toxicology, 2004)

Block Estimating of Spatial Yield Data and its Uncertainty - Shufeng Han; Sally M. Schneider; Robert G. Evans; Joan R. Davenport (Precision Agriculture, 2004)

p16 Expression in Squamous Lesions of the Female Genital Tract - Mary M. Finegan; Aaron C. Han; Mitchell I. Edelson; Norman G. Rosenblum (Journal of Molecular Histology, 2004)

Arsenic Accumulation and Acute Toxicity in Aquacultural Juvenile Milkfish ( Chanos chanos ) from Blackfoot Disease Area in Taiwan - M.-C. Lin; H.-H. Cheng; H.-Y. Lin; Y.-C. Chen; Y.-P. Chen; G.-P. Chang-Chien; Y.-H. Chou; C.-M. Liao; C.-F. Dai; B.-C. Han; C.-W. Liu (Bulletin of Environmental Contamination and Toxicology, 2004)

Mid-Century Ensemble Regional Climate Change Scenarios for the Western United States - L. Ruby Leung; Yun Qian; Xindi Bian; Warren M. Washington; Jongil Han; John O. Roads (Climatic Change, 2004)

Effect of temperature on the pathogenicity of entomopathogenic nematodes (Steinernema and Heterorhabditis spp.) to Delia radicum - S. Chen; J. Li; X. Han; M. Moens (BioControl, 2003)

Antagonism of the antidepressant-like effects of clenbuterol by central administration of ?-adrenergic antagonists in rats - Han-Ting Zhang; Ying Huang; James M. O'Donnell (Psychopharmacology, 2003)

Assessment of global industrial-age anthropogenic arsenic contamination - Fengxiang X. Han; Yi Su; David L. Monts; M. John Plodinec; Amos Banin; Glover E. Triplett (The Science of Nature, 2003)

Novel types of mutation in the choroideremia (CHM) gene: a full-length L1 insertion and an intronic mutation activating a cryptic exon - José A. J. M. van den Hurk; Dorien J. R. van de Pol; Bernd Wissinger; Marc A. van Driel; Lies H. Hoefsloot; Ilse J. de Wijs; L. Ingeborgh van den Born; John R. Heckenlively; Han G. Brunner; Eberhart Zrenner; Hans-Hilger Ropers; Frans P. M. Cremers (Human Genetics, 2003)

Recognition and implication of tectonic loading-induced reheating in the northern Variscan front (Belgium and northern France), based on an illite Kbler index and oxygen isotope study - G. Han; J. Yans; M. Goudalier; F. Lacquement; R. M. Corfield; J. L. Mansy; F. Boulvain; A. Prat (International Journal of Earth Sciences, 2003)

Effects of fish introduction on the length of the tail of cryptomonads in mesocosm experiments - B. H. Kim; M.-S. Han; N. Takamura (Oecologia, 2003)

Development of Linum flavum hairy root cultures for production of coniferin - Han-wei Lin; Kian H. Kwok; Pauline M. Doran (Biotechnology Letters, 2003)

Degradation of Ethoprophos in Three Physicochemically Different Soils Treated with Composted Manure and Chemical Fertilizer - S.-H. Yoo; K.-H. Han; C.-S. Kim; H.-M. Ro; S.-M. Lee (Bulletin of Environmental Contamination and Toxicology, 2003)

Characterization of genotype II Rubella virus strains - D.-P. Zheng; Y. M. Zhou; K. Zhao; Y.-R. Han; T. K. Frey (Archives of Virology, 2003)

Industrial age anthropogenic inputs of heavy metals into the pedosphere - Fengxiang X. Han; Amos Banin; Yi Su; David L. Monts; John M. Plodinec; William L. Kingery; Glover E. Triplett (The Science of Nature, 2002)

Perturbations of Population Growth in a Microcosm by Industrial Metal Plating and Ice Cream Mills Wastewater and Landfill Leachate - S.-U. Wui; K. Cho; Y. Inamori; J.-S. Lee; M.-S. Han; J.-B. Lee (Bulletin of Environmental Contamination and Toxicology, 2002)

Cadmium-Induced Apoptosis in H9c2, A7r5, and C6-Glial Cell - M. K. Choi; B. H. Kim; Y. Y. Chung; M. S. Han (Bulletin of Environmental Contamination and Toxicology, 2002)

Pathogenicity and vaccine efficacy of a thymidine kinase gene deleted infectious laryngotracheitis virus expressing the green fluorescent protein gene - M. G. Han; C. H. Kweon; I. P. Mo; S. J. Kim (Archives of Virology, 2002)

FURTHER CHARACTERIZATION OF BC3H1 MYOGENIC CELLS REVEALS LACK OF P53 ACTIVITY AND UNDEREXPRESSION OF SEVERAL P53 REGULATED AND EXTRACELLULAR MATRIX–ASSOCIATED GENE PRODUCTS - SANDRA B. SHARP; MARIA VILLALVAZO; MICKEY HUANG; RODOLFO GONZALEZ; IRANIA ALARCON; MATTHEW BAHAMONDE; DIANE M. D'AGOSTIN; SAGAR DAMLE; ALEX ESPINOSA; SEOG J. HAN; JESSICA LIU; PAULA NAVARRO; et al. (In Vitro Cellular & Developmental Biology - Animal, 2002)

Comparison of the effects of isoproterenol administered into the hippocampus, frontal cortex, or amygdala on behavior of rats maintained by differential reinforcement of low response rate - Han-Ting Zhang; Sandra A. Frith; John Wilkins; James M. O'Donnell (Psychopharmacology, 2001)

Identification of Arabidopsis proteins that interact with the cauliflower mosaic virus (CaMV) movement protein - Zhong Huang; Vyacheslav M. Andrianov; Yu Han; Stephen H. Howell (Plant Molecular Biology, 2001)

Workshop on Bioanalytical Methods Validation for Macromolecules: Summary Report - Krys J. Miller; Ronald R. Bowsher; Abbie Celniker; Jacqueline Gibbons; Shalini Gupta; Jean W. Lee; Steve J. Swanson; Wendell C. Smith; Russell S. Weiner; Daan J. A. Crommelin; Ira Das; Binodh S. DeSilva; et al. (Pharmaceutical Research, 2001)

Origin of laminated diatom ooze in King George Basin sediments from Bransfield Strait, Antarctica - H. I. Yoon; B. K. Park; M. W. Han; B. K. Khim; Y. Kim; C. Y. Kang (Geosciences Journal, 2001)

New Method to Calculate the N 2 Evolution from Mixed Venous Blood During the N 2 Washout - Decai Han; Duen-Ren Jeng; Julio C. Cruz; Xavier F. Flores; J. M. Mallea (Annals of Biomedical Engineering, 2001)

Hydroxyproline-rich glycoproteins expressed during stress responses in cassava - Yuanhuai Han; Rocío Gómez-Vásquez; Kim Reilly; Hongying Li; Joe Tohme; Richard M. Cooper; John R. Beeching (Euphytica, 2001)

Sequence diversity and interrelationships among isolates of satsuma dwarf-related viruses - T. Iwanami; Y. Kondo; M. Kobayashi; S. S. Han; A. V. Karasev (Archives of Virology, 2001)

Physiological responses that account for the increased power output in speed skating using klapskates - Eveline A. M. Heijnsdijk; Jos J. de Koning; Gert de Groot; Maarten F. Bobbert; Han Houdijk (European Journal of Applied Physiology, 2000)

Angiotensin II induces gene transcription through cell-type-dependent effects on the nuclear factor-κB (NF-κB) transcription factor - Allan R. Brasier; M. Jamaluddin; Youqui Han; Cam Patterson; Marschall S. Runge (Molecular and Cellular Biochemistry, 2000)

An integrated genetic map of Populus deltoides based on amplified fragment length polymorphisms - R. L. Wu; Y. F. Han; J. J. Hu; J. J. Fang; L. Li; M. L. Li; Z. -B. Zeng (Theoretical and Applied Genetics, 2000)

Effects of rolipram on scopolamine-induced impairment of working and reference memory in the radial-arm maze tests in rats - Han-Ting Zhang; James M. O'Donnell (Psychopharmacology, 2000)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

Host effect on genetic variation of Marssonina brunnea pathogenic to poplars - Z. M. Han; T. M. Yin; C. D. Li; M. R. Huang; R.L. Wu (Theoretical and Applied Genetics, 2000)

The Orientation of the Phosphorescence Dipole Moment of Erythrosine B Within Its Molecular Frame - M. P. Lettinga; E. M. Klarenbeek; Han Zuilhof; M. A. M. J. van Zandvoort (Journal of Fluorescence, 1999)

Roles of cyclin D1 and related genes in growth inhibition, senescence and apoptosis - E. K.-H. Han; S.-C. Ng; N. Arber; M. Begemann; I. B. Weinstein (Apoptosis, 1999)

An ensemble forecast of the South China Sea monsoon - T. N. Krishnamurti; Mukul Tewari; Ed Bensman; Wei Han; Zhan Zhang; William K. M. Lau (Advances in Atmospheric Sciences, 1999)

Molecular characterization of germline mutations in the BRCA1 and BRCA2 genes from breast cancer families in Taiwan - Steven Shoei-Lung Li; H.-M. Tseng; Tsui-Ping Yang; Chia-Han Liu; Shiuh-Jen Teng; Hung-Wen Huang; L.-M. Chen; Hsiao-Wei Kao; Jimmy H. Chen; Jau-Neng Tseng; Angela Chen; Ming-Feng Hou; et al. (Human Genetics, 1999)

Isolation and mapping of the rabbit DM genes - E. Hermel; M. Han; Bishop Hague; Thomas Kindt; John J. Monaco (Immunogenetics, 1999)

Optimization of AFLP fingerprinting of organisms with a large-sized genome: a study on Alstroemeria spp. - T. H. Han; H. J. van Eck; M. J. De Jeu; E. Jacobsen (Theoretical and Applied Genetics, 1999)

Evidence for Overlapping Substrate Specificity Between Large Neutral Amino Acid (LNAA) and Dipeptide (hPEPTl) Transporters for PD 158473, an NMDA Antagonist - Narayanan Surendran; Kuang-Ming Y. Covitz; Hyo-kyung Han; Wolfgang Sadee; Doo-Man Oh; Gordon L. Amidon; Rufus M. Williamson; Christopher F. Bigge; Barbra H. Stewart (Pharmaceutical Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Refined mapping of the gene for autosomal dominant retinitis pigmentosa (RP17) on chromosome 17q22 - A. I. den Hollander; S. D. van der Velde-Visser; Alfred J. L. G. Pinckers; Carel B. Hoyng; Han G. Brunner; Frans P. M. Cremers (Human Genetics, 1999)

Expression of bvgAS of Bordetella pertussis represses flagellar biosynthesis of Escherichia coli - Y. W. Han; M. A. Uhl; Seog Joon Han; W. Shi (Archives of Microbiology, 1999)

Detection and quantitation of a sodium-dependent sulfate cotransporter (NaSi-1) by sandwich-type enzyme-linked immunosorbent assay - Kazuko Sagawa; Debra C. DuBois; Bing Han; Richard R. Almon; Jürg Biber; Heini Murer; M. E. Morris (Pflügers Archiv - European Journal of Physiology, 1998)

Enhanced salidroside production in liquid-cultivated compact callus aggregates of Rhodiola sachalinensis: manipulation of plant growth regulators and sucrose - J. F. Xu; P. Q. Ying; A. M. Han; Z. G. Su (Plant Cell, Tissue and Organ Culture (PCTOC), 1998)

Interleukin-13 increases prostaglandin E2 (PGE2) production by normal human polymorphonuclear neutrophils by enhancing cyclooxygenase 2 (COX-2) gene expression - C.-L. Yu; M.-H. Huang; Y.-Y. Kung; C.-Y. Tsai; Y.-Y. Tsai; S.-T. Tsai; D.-F. Huang; K.-H. Sun; S.-H. Han; H.-S. Yu (Inflammation Research, 1998)

Influence of Different Fat Emulsion-Based Intravenous Formulations on the Pharmacokinetics and Pharmacodynamics of Propofol - Eugene H. Cox; Catherijne A. J. Knibbe; Victorine S. Koster; Mariska W. E. Langemeijer; Erica E. Tukker; Rogier Lange; Paul F. M. Kuks; Han J. M. Langemeijer; Loraine Lie-A-Huen; Meindert Danhof (Pharmaceutical Research, 1998)

A comparative molecular analysis of four rat smooth muscle cell lines - Anthony B. Firulli; David Han; Louise Kelly-Roloff; Victor E. Koteliansky; Stephen M. Schwartz; Eric N. Olson; Joseph M. Miano (In Vitro Cellular & Developmental Biology - Animal, 1998)

Strategies for the improvement of salidroside production in cell suspension cultures of Rhodiola sachalinensis - J. F. Xu; C. B. Liu; A. M. Han; P. S. Feng; Z. G. Su (Plant Cell Reports, 1998)

Rock-Shells ( Thais clavigera ) as an Indicator of As, Cu, and Zn Contamination on the Putai Coast of the Black-Foot Disease Area in Taiwan - B. C. Han; W. L. Jeng; M. S. Jeng; L. T. Kao; P. J. Meng; Y. L. Huang (Archives of Environmental Contamination and Toxicology, 1997)

Fine structure mapping of the barley chromosome-1 centromere region containing malting-quality QTLs - F. Han; S. E. Ullrich; A. Kleinhofs; B. L. Jones; P. M. Hayes; D. M. Wesenberg (Theoretical and Applied Genetics, 1997)

Murine Hn1 on Chromosome 11 is expressed in hemopoietic and brain tissues - Wozhan Tang; Yong-Hong Lai; Xiao-Dong Han; Peter M. C. Wong; Luanne L. Peters; David H. K. Chui (Mammalian Genome, 1997)

The longitudinal development of running economy in males and females aged between 13 and 27 years: The Amsterdam Growth and Health Study - Geertje A. M. Arins; Willem van Mechelen; Han C. G. Kemper; Jos W. R. Twisk; Willem van Mechelen (European Journal of Applied Physiology, 1997)

Cysteine ligand vibrations are responsible for the complex resonance Raman spectrum of azurin - Colin R. Andrew; Jane Han; Tanneke den Blaauwen; Gertie van Pouderoyen; Erik Vijgenboom; Gerard W. Canters; Thomas M. Loehr; J. Sanders-Loehr (JBIC Journal of Biological Inorganic Chemistry, 1997)

Effect of EHS matrix on expression of transgenes in HC11 cells - T. H. Lee; M. G. Baik; W. B. Im; C. S. Lee; Y. M. Han; S. J. Kim; K. K. Lee; Y. J. Choi (In Vitro Cellular & Developmental Biology - Animal, 1997)

Human Papillomavirus is More Prevalent in First Trimester Spontaneously Aborted Products of Conception Compared to Elective Specimens - P L Hermonat; L Han; P J Wendel; J G Quirk; S Stern; C L Lowery; T M Rechtin (Virus Genes, 1997)

Numerical bifurcation analysis of distance-dependent on-center off-surround shunting neural networks - Maartje E. J. Raijmakers; Han L. J. van der Maas; Peter C. M. Molenaar (Biological Cybernetics, 1996)

Insoluble hydrophobin complexes in the walls of Schizophyllum commune and other filamentous fungi - Onno M. H. de Vries; M. Peter Fekkes; Han A. B. Wösten; Joseph G. H. Wessels (Archives of Microbiology, 1993)

Development of a computer model to predict strains in the individual fibers of a ligament across the ligamentous occipito-atlanto-axial (C0-C1-C2) complex - Vijay K. Goel; Toru M. Yamanishi; Han Chang (Annals of Biomedical Engineering, 1992)

Nucleotide sequence of the human? 1-globin gene - J. M. Gonzalez-Redondo; I. S. Han; Y. -C. Gu; T. H. J. Huisman (Biochemical Genetics, 1988)

Regulation of amidase formation in mutants from Pseudomonas aeruginosa PAO lacking glutamine synthetase activity - Dick B. Janssen; Patricia M. Herst; Han M. L. J. Joosten; Chris van der Drift (Archives of Microbiology, 1982)

Nitrogen control in Pseudomonas aeruginosa: A role for glutamine in the regulation of the synthesis of NADP-dependent glutamate dehydrogenase, urease and histidase - Dick B. Janssen; Patricia M. Herst; Han M. L. J. Joosten; Chris van der Drift (Archives of Microbiology, 1981)